Novel Azithromycin-Based Re-Dispersible Mucoadhesive Gargle for Effective Management of Bacterial Throat Infections: In Vitro and In Vivo Characterization - Debaprasad Dash; Kapil Raju Shah; Ajit Mishra; Jitu Halder; Rakesh Kumar Sahoo; Tushar Kanti Rajwar; Deepak Pradhan; Ritu Mahanty; Bibhanwita Satpathy; Ivy Saha; Priyanka Dash; Chandan Das; et al. (Journal of Pharmaceutical Innovation, 2027)

Multi-residue pesticide contamination in marketed rice and recommended mitigation techniques by household washing and cooking to reduce dietary risks - Vipin Pratap; Glenn Vincent Ong; Iegem Lean Laudencia; Priyabrata Roy; Ashish Yadav; Hari Narain Singh; Deepak Kumar Verma; Rhowell Tiozon; Nese Sreenivasulu (Food Control, 2026)

Immobilization of β-galactosidase on aminosilane activated mesoporous silicon dioxide nanoparticles for galactooligosaccharides production - S. Supreetha; C.T. Manoj Kumar; M.H. Sathish Kumar; Deepak; N. Laxmana Naik (Food and Humanity, 2026)

Development of graphene oxide-modified bismuth oxide nanomaterials for electrochemical and light-activated catalytic applications - Amika; Deepak Kumar; Dinesh Kumar; Azad Qayoom Malik; Bhawna; Nabisab Mujawar Mubarak; Mohamed Aly Saad Aly (Environmental Nanotechnology, Monitoring & Management, 2026)

Preclinical evaluation of route-dependent immune responses following repeated administration of a Klebsiella pneumoniae lytic phage cocktail in rats - Sonam Rastogi; Mayank Gangwar; Sudhir Kumar Singh; Alka Shukla; Digvijay Singh; Vandana Rastogi; Deepak Kumar; Pooja Sachdeva; Gopal Nath (Molecular Biology Reports, 2026)

Decoding PARP roles in breast cancer therapy resistance - Mohammad Abohassan; Farag M. Altalbawy; Majid S. Jabir; Thikra F. Hasan; Ashishkumar Kyada; Deepak Nathiya; Parjinder Kaur; M. Ravi Kumar; Munthar Kadhim Abosaoda; Muhammad Shahid Iqbal (Molecular Biology Reports, 2026)

Development and characterization of NB-ARC gene-derived SSRs in wheat (Triticum aestivum L.) - Dinesh Arya; Pradeep Singh; Vikas Fandade; Deepak Das; Jitendra Kumar; Bishakha Biswakarma; Joy Roy (Molecular Biology Reports, 2026)

Omics-based insights into skin ulcerative disease in sea cucumbers: a systematic review - Deepak Ganesh; Vijay Subbiah Kumar; Guneswar Sethi; Nurzafirah Mazlan (Molecular Biology Reports, 2026)

Comprehensive transcriptomic analysis highlights immune and cell-cycle dysregulation in Diamond-Blackfan Anaemia - Isha Goel; Ashikh Seethy; Karthikeyan Pethusamy; Deepak Kumar; Ruby Dhar; Tulika Seth; Subhradip Karmakar (Molecular Genetics and Genomics, 2026)

First report of whole genome sequence of a Mycobacterium bovis (3/86Rv) strain isolated from a cow in India - Rishendra Verma; Ravi Kumar Gandham; Karikalan Mathesh; Deepak Kumar (Brazilian Journal of Microbiology, 2026)

An explainable deep learning-integrated decision support system for field diagnosis and management of botrytis grey mold in castor - G. Jadesha; Yamanura Madival; R. Mohan Kumar; Anurag Dhole; H.C. Lohithaswa; Mallana Gowda Mallikarjuna; K.B. Palanna; D. Deepak (Computers and Electronics in Agriculture, 2026)

Association of body surface temperature with environmental indices and rectal temperature in sub-tropical goats maintained in psychrometric chamber - Srashti Dixit; Rajneesh Sirohi; Brijesh Yadav; Mamta; Ajay Kumar; Yajuvendra Singh; Chandan Kumar; Vishakha Singh; Mohammad Danish; Deepak Kumar (Small Ruminant Research, 2026)

Endohyphal bacterial symbiosis is associated with altered metabolite profiles and stress adaptation in Trichoderma atrobrunneum PEI1: Integrative metagenomic and metabolomic insights - Pramod Kumar Sahu; Krishna Nanda Dhal; Deepak Singla; Niharika Rai; Aditya Kumar Gautam; Nidhi Rai; Astha Pandey; Amrita Gupta; Madhu Yadav; Pankaj Kumar Maurya; Manish Roy; Vivek Kumar; et al. (Physiological and Molecular Plant Pathology, 2026)

Host-mediated variation in insect biology, feeding efficiency and defensive phytochemicals underlying resistance of poplar clones to Clostera cupreata (Butler, 1881) - Arvind Kumar; Jitendra Kumar; Tanmaya Kumar Bhoi; Deepak Kumar Mahanta (Phytoparasitica, 2026)

Antidepressant activity of liposomal Humulus lupulus L. Chloroform fraction: involvement of monoaminergic neurotransmission and redox-linked signalling in a chronic restraint stress mouse model - Sarika; Sunil Puri; Jatinder Singh Chera; H. Lalhlenmawia; Anshul Attri; Sudarshan Kumar; Deepak kumar (South African Journal of Botany, 2026)

Abiotic stress hormesis in tomato fruit: Determining hormetic doses from stress dose - Ripening response relationships - Deepak Kumar Jha; Bhimanagouda S. Patil; Joseph Arul; Yves Desjardins (Postharvest Biology and Technology, 2026)

A hybrid self organizing map-analytic hierarchy process framework for robust spatiotemporal groundwater quality assessment using long-term hydro-chemical data - Deepak Kumar; Vinod Kumar Tripathi; Vijay Kumar Singh; Pavan Kumar Harode (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

CFD modelling and experimental study of NMC hydroxide in a stirrer tank reactor: Modelling parameter study for nucleation, growth and agglomeration - Deepak Kumar; Milinkumar T. Shah; Daniele Marchisio; Vishnu Pareek; Jacques Eksteen (Hydrometallurgy, 2026)

A focus on microplastics in daily life eateries: identification by FT-IR, AFM, pyrolysis GC/MS and microscopic studies - Anupama Sharma; Girish Chandra Sharma; Neeraj Kumar; Bhumi Chaturvedi; Sourav Debnath; Mahaveer Singh; Deepak Nathiya; Balvir Singh Tomar (Food Research International, 2026)

Microwave-assisted non-destructive recycling of cathode active materials and aluminium foil from spent lithium-ion batteries - Umang Singh; Deepak Pant; Anand Giri; Pavitra V. Kumar (Waste Management, 2026)

Phytochemical characterization and EGFR-directed antineoplastic potential of Bergenia ciliata leaf fractions against lung and breast cancer - Krittika Mukherjee; Shekhar Kumar; Monu Kumar Shukla; Vinay Chauhan; Arun Kumar; Uma Ranjan Lal; Deepak Kumar (South African Journal of Botany, 2026)

Rapid SERS-machine learning–enabled virulence profiling of Acinetobacter baumannii for environmental surveillance - Phularida Amulraj; Karpagavalli Palpandi; Sri Surya Charan Kondeti; Jayasree Kumar; Ajinkya Deepa Deepak Anjikar; Hemanth Noothalapati; Rajapandiyan Panneerselvam; Jayaseelan Murugaiyan (Journal of Hazardous Materials, 2026)

Culinary Tourism Experiences as a strategic driver of destination revisit intention and sustainable brand image - Rajiv Ruliya; Deepak Kumar; Pardeep Khatkar; Ankush Ambardar; Megha Gupta Ambardar (International Journal of Gastronomy and Food Science, 2026)

Bacillus licheniformis from acidic soil as an efficient Al3+ biosorbent: Isolation, characterization, and biosorption evaluation - Shilpee Dhali; Taznim Hossain; Deepak Kumar Patra; Sukanta Kumar Pradhan; Chinmay Pradhan (International Biodeterioration & Biodegradation, 2026)

All 2D2D Mo0.5W0.5S2-Ti3C2Tx asymmetric micro-supercapacitors — Pathway for superior and flexible high-energy storage devices - Animesh Mandal; Nikita Dey; Deepak Kumar Sahu; Prasanta Kumar Guha; Samit Kumar Ray (Chemical Engineering Journal, 2026)

Gene expression and metabolic regulation of carotenoid and withanolide biosynthetic pathways in Withania somnifera with emphasis on FPPS-mediated regulation - Rimjim Gupta; Deepak Sharma; Anuj Sharma; Anusha Patil; Dinesh A. Nagegowda; Sanjana Kaul; Manoj Kumar Dhar (Protoplasma, 2026)

Antibacterial Efficacy of Recombinant Endolysin S.AgEndo1332 in Combination with Antibiotics against Mastitis-Associated S. aureus in a Mouse Mastitis Model - Richa Sarkar; Ravi Kant Agrawal; Abhilash S. Goud; Thanksy S. Akkara; Kajal Bankoti; Keshav Kumar; Mrinalini Saini; Jaideep Singh; Gaurav Kumar Sharma; Vidya Singh; Deepak Kumar; Bhoj Raj Singh (Probiotics and Antimicrobial Proteins, 2026)

Pyramiding of Multiple QTL for Drought and Submergence Tolerance for Infusing Climate-Resilience in Rice Variety Samba Mahsuri - Priyanka Jain; Riti Thapar Kapoor; Manish Kumar; Neera Yadav; Mukta Rani; Rekha Joshi; Vandana Rai; Deepak Singh Bisht; Kishor Gaikwad; Nagendra Kumar Singh (Indian Journal of Genetics and Plant Breeding, 2026)

Immunization with PLGA-encapsulated recombinant staphylococcal enterotoxin C confers protection against intramammary Staphylococcus aureus challenge in a murine mastitis model - Desh Deepak; Preena Prasanna; Radhika Vaidya; Syed Atif Ali; Nongthombam Boby; Banaja Kanta Pati; Ujjwal Kumar De; Med Ram Verma; Monalisa Sahoo; Pallab Chaudhury; Reena Mukherjee (Antonie van Leeuwenhoek, 2026)

AMBMP Hydrochloride Reverses STZ-Induced Alzheimer-Type Dementia Associated with Wnt/β-catenin/TLR4 Signaling - Palak Kalra; Deepak Chaturvedi; Amit Kumar; Amarjot Kaur Grewal; Heena Khan; Varinder Singh; Thakur Gurjeet Singh; Tanveer Singh; Sheikh F. Ahmad; Sabry M. Attia (NeuroMolecular Medicine, 2026)

Ecological niche modelling reveals climatic determinants and future distribution of the entomopathogenic fungus Metarhizium anisopliae (Metschn.) Sorokin - Deepak Kumar Mahanta; Tanmaya Kumar Bhoi; Charishma Krishnappa (International Journal of Tropical Insect Science, 2026)

Development of biomimetic mouldable osseous scaffold engineered from bioactive decellularized extracellular matrix-polymer-gel composite: a potential bone substitute - Prarthana R; Rekha Pathak; Deepak Kumar; Vinodhkumar Obli Rajendran; KS Kamalesh; T. Saikumar; Bhanu Pratap Singh; Rohit Kumar (Cell and Tissue Banking, 2026)

Shatavarin IV from Asparagus curillus roots exhibits antidiabetic activity in STZ-induced rats - Anoop Singh Negi; Veerma Ram; Ankit Kumar; Ankush Sundriyal; Ruchi Badoni Semwal; Deepak Kumar Semwal (Natural Product Research, 2026)

Rationalisation of extractive protocols for Picrorhiza kurroa Royle ex Benth. through chemoprofiling and greenness assessment: assessing variable hydroalcoholic solvents and phytochemicals interplay - Kalyan Hazra; Deepak Kumar; Sudipto Debnath; Jyoti Dahiya; Manoj Raturi; Preeti Sharma; Ajay Kumar Meena; Ravindra Singh (Natural Product Research, 2026)

Association of κ-casein gene polymorphisms with milk yield, composition, and udder conformation traits in indigenous Harnali and Munjal sheep breeds of India - Deepak Malik; Ankit Magotra; Pushpa Sindhu; Pradeep Chaudhary; Devesh Kumar Yadav (Small Ruminant Research, 2026)

Damping-controlled lock-in and smooth lock-out in vortex-induced vibrations of tandem diamond cylinders - Deepak Kumar; Kumar Sourav; Chhote Lal Shah (Ocean Engineering, 2026)

Numerical and experimental investigation of a Coandă-effect-based hydraulic collector for deep-sea polymetallic nodules - Amudha K.; Deepak Kumar; Gopkumar K.; Balaji R.; Rajiv Sharma (Ocean Engineering, 2026)

Optimized training functions for recurrent neural network based model predictive control of multi-agent system - Piyush Chaubey; Anilkumar Markana; Dhaval Vyas; Deepak Kumar Goyal (Next Research, 2026)

Fatigue life prediction of titanium alloy knee implant using XFEM - Deepak Kumar; Rina Maiti (Next Research, 2026)

Crustal structure and anomalies in the northern Indian-Eurasian collision zone using surface wave tomography - Deepak Kumar; Satish Maurya; G. Suresh; M.L. Sharma; S.C. Gupta (Journal of Asian Earth Sciences, 2026)

Uttarkashi-strain based goatpox vaccine provides inadequate protection against lumpy skin disease in cattle - Ram Kumar; Deepak Kumar Sharma; Shweta Dhanda; Assim Verma; Subhash Kachhawaha; Rajesh Singathia; Sitaram Gupta; Abhishek Gaurav; Manisha Mathur; Dinesh Jain; T. Riyesh; Naveen Kumar; et al. (Veterinary Research Communications, 2026)

Electrifying Sagar Island, West Bengal, India: advancing multiple SDGs through integrated coastal policy and sustainable development - Satyendra Kumar; Selvin Pitchaikani J; Deepak Samuel V; Ramesh R (Journal of Coastal Conservation, 2026)

Research trends and knowledge gaps in earthquake-induced landslides in Nepal: a bibliometric review - Birendra Kumar Bohara; Janardan Joshi; Toran Prasad Bhatt; Kishan Datta Bhatta; Deepak Raj Bhatta; Nayan Singh Saud (Innovative Infrastructure Solutions, 2026)

Multiple gene detection of ‘Candidatus Phytoplasma australiasiaticum’ related strain associated with stem fasciation in Brassica napus L - Shivani Gupta; Ashok Kumar Singh; Deepak Kumar; Ravinder Kumar; Govind Pratap Rao (Indian Phytopathology, 2026)

Fungal Endophytes Promote Wheat (Triticum aestivum L. PBW-343) Growth and Enhance Salt Tolerance Through Improvement of Ascorbate Glutathione Cycle and Gene Expression - Priyanka Prajapati; Prashasti Pandey; Deepak Kumar; Ravindra Nath Kharwar (Journal of Plant Growth Regulation, 2026)

Altitudinal Climatic Variation Shapes Soil Microbial and Enzymatic Functioning Through Nutrient-mediated Pathways in Western Himalayan Agroforestry Systems - Deepak Kumar Mishra; Ujjwal Kumar; Kusum Arunachalam (Journal of Soil Science and Plant Nutrition, 2026)

Sleep Deprivation and Fatigue in Commercial Aviation: Circadian Biology, Operational Risk and Fatigue Management in Global and Indian Aviation - Velayudhan Mohan Kumar; Hruda Nanda Mallick; Kamalesh K. Gulia; Deepak Shrivastava; Manvir Bhatia (Sleep and Vigilance, 2026)

Freshwater recharge–driven remediation of coastal saline aquifer: Insights from hydrogeological and hydrochemical analysis - Brijesh Kumar Yadav; Akansha Keshariya; Deepak Tripathi; Apoorv Verma (Regional Studies in Marine Science, 2026)

Fish-inspired locomotion in robotics: Biology, hydrodynamics, and machine learning - Ashish Sharma; Mayank Kumar Singh; Deepak Sachan; Jagadeesh Kadiyam (Ocean Engineering, 2026)

Computer vision-based soil clod distribution mapping after primary tillage - Deepak Kumar; Narendra Singh Chandel; Dilip Jat; A.K. Raul; Karan Singh; Abhishek Upadhyay; Mahmoud Okasha; Prakhar Patidar; Manoj Kumar (Journal of Terramechanics, 2026)

Exploration of self-cleaning and bactericidal properties of the fine micro-architectured wings of hemipteran planthopper, leafhopper, and spine soldier bug - Deepak Kumar Panda; Monalisa Mishra (BioSystems, 2026)

Gestational deltamethrin exposure exacerbates post-traumatic epileptiform activity and social deficits, diminishing the therapeutic efficacy of curcumin in rats - Kamendra Kumar; Prince Kumar; Pavan Kumar; Deepak Sharma (Metabolic Brain Disease, 2026)

Spatiotemporal dynamics of Indian concurrent day night heatwaves across different warming targets - Deepak Kumar Prajapat; Mahender Choudhary; Saurabh Singh; Sajid Ullah; Wafa Saleh Alkhuraiji; Mohamed Zhran (Meteorology and Atmospheric Physics, 2026)

Biomarkers of stress memory and genomic plasticity in plants: from epigenetic imprints to predictive resilience - Madhusmita Nayak; Deepak Kumar Patra (Environmental Geochemistry and Health, 2026)

Exploring the potential health risks of groundwater arsenic and its spatial distribution in three districts (Patna, Bhojpur and Saran) of Bihar, India - Parimal Kumar Khan; Pankaj Kumar; Anupma Kumari; Deepak Kumar Jha; Farha Ashique; Amod Kumar (Environmental Geochemistry and Health, 2026)

North Atlantic circulation and climate variability during the last glacial maximum and the last interglacial: insights from CMIP6/PMIP4 climate models - Deepak Kumar Chinnaswamy; Sebastian Wagner; Michael Hein; Marie-Luise Kapsch; Antje Schwalb (Climate Dynamics, 2026)
The Last Glacial Maximum (LGM) and Last Interglacial (LIG) provide insights into the response of the North Atlantic–European climate variability to strongly contrasting boundary conditions. Using six CMIP6/PMIP4 models, we compare temperature–precipitation patterns, atmospheric circulation, and variability, with emphasis on the North Atlantic Oscillation (NAO). Across climate states, the leading modes of wintertime sea-level pressure variability remain recognisable, indicating a robust dynamical structure. However, their amplitude, explained variance, and spatial positioning exhibit state dependence. During the LGM, extensive ice sheets were associated with a stronger and more spatially confined NAO dipole, southward-displaced pressure centres, and reorganised circulation patterns, reinforcing colder and drier European conditions with enhanced seasonality. The LIG exhibits a weaker NAO expression with westward-shifted pressure centres, a more zonal circulation, northward-shifted warm sea surface temperatures, and enhanced seasonality. NAO-related interannual atmosphere–ocean coupling persists across climate states, with limitations in capturing low-frequency variability within the available simulation lengths. Summer variability is substantially weaker and more heterogeneous across all periods, with the NAO losing dominance often to the East Atlantic pattern during the LGM. Inter-model differences increase considerably under LGM and LIG conditions compared to the pre-industrial period (PI), underscoring the importance of multi-model approaches and an improved representation of key processes when investigating climate variability in extreme climate states.

Prioritizing Sleep, Improving Health: A Draft for National Sleep Health Policy of India - Ravi Gupta; Abhishek Goyal; Deepak Shrivastava; Hrudananda Mallick; Kamlesh Gulia; Karuna Datta; Lokesh Kumar Saini; Manvir Bhatia; Nasreen Akhtar; Niraj Kumar; Ravi Yadav; S.R. Pandi-Perumal; et al. (Sleep and Vigilance, 2026)

Chemistry and pharmacology of vulpinic acid: The journey of a lichen metabolite from traditional poison to modern drug lead - Ruchi Badoni Semwal; Shivam Nautiyal; Deepak Kumar Semwal (Phytochemistry Letters, 2026)

Bioproduction of polyhydroxybutyrate-co-polylactic acid (3HB-co-LA) from dairy co-product acid whey - Rachel Rovinsky; Robert E. Mejia; Nikkia L. Kohn; Gundeep Kaur; Ethan Seng; Zheng Rong Yee; Linjing Jia; Patricia Q. Tran; Brian G. Fox; Deepak Kumar; Erica L.-W. Majumder (Bioresource Technology Reports, 2026)

Statistical optimisation of steam pretreatment and enzymatic hydrolysis for enhanced sugar recovery and bioethanol production from composite food waste - Bishakha Thakur; Raman Soni; Deepak Kumar Rahi; Sanjeev Kumar Soni (Bioresource Technology Reports, 2026)

Design and Development of Myco-Mediated Bioremediation System for the Treatment of Runoff and Grey Water - Anupam Barh; Uday Mandal; J. M. S. Tomar; Deepak Singh; Varun Chauhan; Sudheer Kumar Annepu; Rama Pal; M. Muruganandam; Trisha Roy; A. C. Rathore; A. K. Gupta; Devideen Yadav; et al. (Water, Air, & Soil Pollution, 2026)

Investigation of the Mount Ruang volcanic eruption in Indonesia: a case study - Aniket Patel; Som Kumar Sharma; Ruchita Shah; Dharmendra Kumar Kamat; Prashant Kumar; Kondapalli Niranjan Kumar; Nupoor A. Chotaliya; Deepak Kumar Kar (Natural Hazards, 2026)

Towards a context-aware framework for cellular senescence - Arnab Nath; Parul Mehrotra; Chiranjib Bhattacharyya; Deepak Kumar Saini (Biogerontology, 2026)

Interactive Effects of Elevated CO2, Temperature, and Weed Competition on Mungbean - Dasari Sreekanth; Deepak Vishwanath Pawar; Rajeev Kumar; Shobha Sondhia; P. K. Singh; J. S. Mishra; Ankita Sinha; Subhash Chander; Nagaraju Mukkamula; B. Kiran Kumar (Agricultural Research, 2026)

Drivers of Productivity and Profitability in Major Edible Oilseeds: Insights from CACP Data in India - Mulla Areef; Deepak Kumar (Agricultural Research, 2026)

Engineering properties of Himalayan rocks: a comprehensive review across tectono-stratigraphic zones - Bikash Kumar Ram; Divyanshoo Singh; Hemant Kumar Singh; Vikram Gupta; Deepak Amban Mishra; Sandeep Kumar (Journal of Earth System Science, 2026)

24-Epibrassinolide Protects Against Sclerotia Stem Rot and Alternaria Leaf Spot in Brassica juncea L - Shashi Shekhar; Rashmi Chaudhary; Deepak Kumar; Prashasti Pandey; Ravi Rajwanshi; Anjana Rustagi (Journal of Plant Growth Regulation, 2026)

High-Throughput Phenotyping for Assessing Drought Responses of Novel Citrus Rootstock Genotypes - Pilathottathil Kuzhiyil Anagha; Radha Mohan Sharma; Anil Kumar Dubey; Amit Kumar Goswami; Sudhir Kumar; Shailendra Jha; Amrender Kumar; Deepak (Journal of Plant Growth Regulation, 2026)

The effect of silymarin and nano zinc supplementation on growth, immunity, antioxidant, and metabolic hormone status of Murrah buffalo calves - Deepak Singh; Dev Saran Sahu; Gulab Chandra; Satya Prakash Yadav; Debashis Roy; Rakesh Kumar Singh; Devesh Kumar Yadav; Ahmad Fahim; Prem Sagar Maurya; Pankaj Kumar Maurya; Karunesh Kumar Dubey (Animal Feed Science and Technology, 2026)

Rosmarinic acid as a potential GSK3β inhibitor for autism spectrum disorder: insights from an integrative in silico study - Priya Joon; Saumya Bansal; Jesil Mathew Aranjani; Anil Kumar; Deepak Deepak (In Silico Pharmacology, 2026)

Targeting retinal degeneration: zeaxanthin dipalmitate from Lycium barbarum L. prevents A2E photooxidation under blue light - Deepak Basyal; Shiva Kumar Bhandari; Hye Jin Kim (Natural Product Research, 2026)

Field-deployable CRISPR-cas variants for rapid on-site detection of plant pathogens - Himanshu Saini; Jyoti Yadav; Sharad Pandey; Anand Kumar; Deepak Nanda; Sharad Sachan; Jeevan Jyoti Kaushik (Plant Science, 2026)

Optimization of NREL S-810 wind turbine airfoil for enhanced lift and efficiency using an improved genetic algorithm for low Reynolds number - Deepak Kumar; Qazi Shahzad Ali; Majid Ali; Sehar Shakir; Ammar Mushtaq; Khurram Mehboob (Ocean Engineering, 2026)

Human reproductive exposure to microplastics: A multi-technique analytical study of menstrual and amniotic fluids - Girish Chandra Sharma; Neeraj Kumar; Damini Devrukhkar; Rahul Mulchandji Joshi; Sourav Debnath; Bhumi Chaturvedi; Sumit Rajotiya; Shivang Mishra; Anupama Sharma; Mahaveer Singh; Deepak Nathiya; Balvir Singh Tomar (NanoImpact, 2026)

The nano-revolution in food preservation: A review of advanced silver nanoparticle packaging - Kaustubh Singh; Shraddha Prakash; Deepak Choudhury; Digvir S. Jayas; Muskan Kumari; Rakesh K. Singh; Rupali Koundal; Anil Kumar Chauhan (Food Control, 2026)

A finite element investigation into the in-plane load bearing behaviour of traditional timber-dry stone (Kath-Kuni) Masonry Walls - Hisham Tariq; Deepak Kumar; Ashutosh Kumar; Vasilis Sarhosis (Engineering Structures, 2026)

The future of global Ramsar wetlands under intensifying precipitation extremes: Arid regions as emerging hotspots - Deepak Mishra; Nakka Naveen Kumar; Shekhar Singh; Manish Kumar Goyal (Environmental Impact Assessment Review, 2026)

Operational and embodied emissions in life cycle analysis of Biopolymers in Northeastern United States buildings - Seyedehniloufar Mousavi; Tristan Brown; Robert W. Malmsheimer; Deepak Kumar; Paul Crovella (Bioresource Technology, 2026)

Integrating omics and artificial intelligence with plant tissue culture: pathways to next-generation crop improvement - Himanshu Saini; Jyoti Yadav; Anand Kumar; Sharad Sachan; Shalu Vyas; Atin Kumar; Deepak Nanda; P. R. Jeyaramraja (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Inhalation dose and seasonal variability in indoor radon, thoron, and their progeny in the sub-mountainous Dhauladhar region of Himachal Pradesh, NW Indian Himalaya - Anand Giri; Meera Goswami; Deepak Pant; Manoj Kumar; Kulamani Parida (Environmental Geochemistry and Health, 2026)

Response of Strawberry (Fragaria × ananassa Duch.) to Plant Density and Column Size in a Vertical Soilless Cultivation System - Vikas Kumar Sharma; A. K. Godara; Deepak Kaushik; Krishan Kant Meena; Sushil Sharma; Adesh Kumar; Arvind Malik; Prince (Applied Fruit Science, 2026)

Investigating the role of FKBP4 in testis germ cell tumor via integrated in silico approach - Deepak Sahni; Bhupendra Kumar; Saumya Porwal; Ashutosh Kumar Arya; Md. Sohail Akhtar; Akhilendra Pratap Bharati (In Silico Pharmacology, 2026)

Grass root litter and soil carbon quality contrarily control Q10 of labile and recalcitrant carbon pools in a semi-arid inceptisol - Vikas Kumar Singhal; Avijit Ghosh; Amit K. Singh; Ranjan Bhattcahryya; Yogeshwar Singh; Sourav Kumar; Deepak Ojha; Arun K. Shukla (Plant and Soil, 2026)

Structure-based virtual screening and in vivo validation of antiviral agents targeting WSSV thymidine kinase in Penaeus vannamei - Jishu Banerjee; Gulshan Kumar; K. Kumanan; E. Suresh; Shiv Kumar Yadav; Deepak Agarwal (Aquaculture, 2026)

Cellulose nanocrystals from forest residues: An integrated techno-economic analysis and life cycle assessment - Rahul Prasad Bangalore Ashok; Richard Bergman; Md Shahadat Hossain; Deepak Kumar; Prakash Nepal; Troy Runge (Resources, Conservation and Recycling, 2026)

Late Holocene vegetation dynamics, fire regimes, and human impact in Southern Brazil: A multi-proxy palaeoecological record from the Matematico Lake - Antonia Lena Reinhardt; Philip Riris; Barnabas Harris; Deepak Kumar Jha; Gisele Leite de Lima Primam; Soraia Girardi Bauermann; Kasun Gayantha; Rachel Rudd; Patrick Roberts; Hermann Behling (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

From soil stress to sustainable solutions: A bibliometric and systematic review of plant growth promoting rhizobacteria in climate-resilient agriculture - Deepak Kumar; Meenakshi Suhag; Deepak Malik (European Journal of Agronomy, 2026)

Long-term ecological recovery of a minespoil watershed: Hydrological, vegetation, and carbon stock assessment - Jag Mohan Singh Tomar; Anupam Barh; Raj Kumar; Deepak Singh; Ranjeet Singh; Dinesh Jinger; R.K. Singh; Rajesh Kaushal; Sneha Dobhal; M. Madhu (Ecological Engineering, 2026)

Effect of strategic supplementations of antioxidant multiminerals and vitamins to transitional buffaloes on serum biochemistry, non-esterified fatty acid and calf health - Desh Deepak; Ujjwal Kumar De; Tarun Kumar Sarkar; Gulab Chandra; Varun Kumar Sarkar (Tropical Animal Health and Production, 2026)

Tail-raising and head-turning as predictive behavioural indicators of calving in Murrah buffaloes - Deepak Chopra; Arun Kumar Misra; T. K. Mohanty; Rubina K. Baithalu; Indu Devi; Chinmayee Sahu; Simran Kamboj; Birender Singh; Pratibha Jareda; Prachi Chandrakar (Tropical Animal Health and Production, 2026)

Genome-wide association mapping of rice bran oil content and γ-oryzanol reveals candidate genes for lipid biosynthesis and transport - Samrath Baghel; Parmeshwar Kumar Sahu; Ravi Raj Singh Patel; Poonam Gajanan Bhad; Sayaji Mehetre; Bikram Kishore Das; Girish Chandel; Latif Ahmad Peer; Deepak Sharma; Suvendu Mondal (Planta, 2026)

A novel QTL discovered for grain protein content without grain weight penalty in wheat (Triticum aestivum L.) - Vikas Fandade; Ankita Mishra; Deepak Das; Vinita Sharma; Prashant Kumar; Akansha Madhawan; Dalwinder Singh; Jitendra Kumar; Pradeep Singh; Shrikant Mantri; Shailendra Sharma; Manoj Oak; et al. (Physiology and Molecular Biology of Plants, 2026)

Spatiotemporal assessment of extreme rainfall events in the Wainganga river basin using CMIP6 climate models - Gupta Abhishek Rajkumar; Manish Kumar Nema; Deepak Khare (Natural Hazards, 2026)

Release Kinetics of Major Plant Nutrients from a Seaweed Extract-Based Product and Its Effect on Soil Fertility and Wheat Productivity in an Acid Soil of North-Eastern Hill Region of India - Bijan Kumar Mondal; Abir Dey; MC Meena; Debarup Das; Archana Singh; Shivani Nagar; Prasenjit Ray; PK Upadhyay; Deepak Bamel; Amit Kumar Dash; Krishna Kumar Mourya; Narender Yadava; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Physiological and molecular profiling of drought-tolerant finger millet genotypes from Koraput region of South Odisha - Aloukika Panda; Sangram K. Lenka; Deepak Kumar; Debabrata Panda (Journal of Plant Biochemistry and Biotechnology, 2026)

Correction to: Unraveling the novel sources of resistance in rice landraces against an emerging bakanae disease through phenotypic, biochemical, and gene expression studies - Shashi Pandey; Ayush Raj Singh; Asif Bashir Shikari; Gaurav Kumar Yadav; S. Gopala Krishnan; Ashok Kumar Singh; Soumya Sharma; Sapna Sharma; Ranjith K. Ellur; Prolay K. Bhowmick; Deepak Ganjewala; Bishnu Maya Bashyal (Cereal Research Communications, 2026)

Unraveling the novel sources of resistance in rice landraces against an emerging bakanae disease through phenotypic, biochemical, and gene expression studies - Shashi Pandey; Ayush Raj Singh; Asif Bashir Shikari; Gaurav Kumar Yadav; S. Gopala Krishnan; Ashok Kumar Singh; Soumya Sharma; Sapna Sharma; Ranjith K. Ellur; Prolay K. Bhowmick; Deepak Ganjewala; Bishnu Maya Bashyal (Cereal Research Communications, 2026)

A Graphene Oxide-Enhanced Five-Layer Plasmonic Biosensor: Design and Theoretical Analysis for Ultrasensitive Molecular Detection - Deepak Sahu; Chakresh Kumar; Ghanendra Kumar (Cell Biochemistry and Biophysics, 2026)

Pilot Fatigue and the Window of Circadian Low - Velayudhan Mohan Kumar; Hruda Nanda Mallick; Deepak Shrivastava; Manvir Bhatia; Ravi Gupta; Kamalesh K. Gulia (Sleep and Vigilance, 2026)

Antioxidant, antibacterial and antibiofilm activities of Pittosporum napaulense (DC.) against drug-resistant Staphylococcus aureus and Shigella sp - Sajna Sameekshya Hota; Dibya Ranjan Sahoo; Subhaswaraj Pattnaik; Monika Mishra; Tapasa Mishra; Tanuja Sahu; Baishali Basundhara Naik; Malayamarutham Kalyankumarraju; Amit Kumar Dixit; Deepak Lamba; Sanjaya Kumar Y. R.; Rabinarayan Acharya; et al. (Natural Product Research, 2026)

Long-term fate of contaminants in landfill-recovered soil: Evidence from leaching experiments and numerical modelling - Deepak Kumar Haritwal; Pranjal Singh; G.V. Ramana; Manoj Datta (Science of The Total Environment, 2026)

PFAS in commercially available organic amendments and food-contact paper products - Maryam Saffari Aman; Douglas J. Daley; Yaqi You; Deepak Kumar; Chang Geun Yoo (Science of The Total Environment, 2026)

More than just flavour and fragrance – the chemistry and pharmacological potential of anethole - Ruchi Badoni Semwal; Deepak Kumar Semwal; Ankit Kumar; Maxleene Sandasi; Alvaro Viljoen (Phytochemistry, 2026)

Investigating the planform dynamics and LULC changes with predictive insights in a Sub-Himalayan Transboundary River Basin, India - Jiarul Alam; Deepak Kumar Mandal; Jahurul Mandal; Harekrishna Manna; Sanjoy Barman; Anoop Kumar Shukla (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Insights into the biodiversity, mechanisms and plant growth-promoting effects of Bradyrhizobium and its potential in sustainable agriculture: A review - Roohi SHARMA; Deepak KUMAR; Nitika KAPOOR; Puja OHRI (Pedosphere, 2026)

Incorporating Behavioural Haematological Biochemical and Pathophysiological Markers to Gauge the Detrimental Consequences of Altered Water Chemistry - Anuj Kumar; Deepak Kumar Dwivedi; Anil Kumar Meena; Saurabh Mishra; Vinod Kumar Verma (Water, Air, & Soil Pollution, 2026)

Forest Residue-Derived Thermoresponsive Nanocellulose Adsorbent for Efficient Removal of Short- and Long-Chain PFAS from Water - Md Shahadat Hossain; Thomas Stuart; Aditi Verma; Robert Cheatham; Toufiq Reza; Bandaru Ramarao; Troy Runge; Deepak Kumar (Water, Air, & Soil Pollution, 2026)

Temporal Modulation of Physiological and Biochemical Mechanisms Enhances Drought Tolerance Across Developmental Stages in Field Pea (Pisum sativum L.) - Amit Sharma; Ravika Sheoran; Rajesh Yadav; Pawan Kumar; Kavita Dhaka; Deepak Kaushik; Jyoti Duhan; Naresh (Journal of Plant Growth Regulation, 2026)

Whether Dye-Based Methods Are Ready for Microalbuminuria Detection: A Review of Research in the Field - Monu Kumari; Deepak Kumar; Rajasri Bhattacharyya; Dibyajyoti Banerjee (Indian Journal of Clinical Biochemistry, 2026)

System optimization practices for profitable and agro-ecologically sustainable agriculture in North-Western Indo-Gangetic Plains - Radheshyam; Shankar Lal Jat; Mangi Lal Jat; Hanuman Sahay Jat; Aditya Kumar Singh; Deep Mohan Mahala; Chiter Mal Parihar; Rajbir Singh; Deepak Bijarniya; Kailash Chandra Kalvaniya; Smruti Ranjan Padhan (Agricultural Systems, 2026)

Therapeutic potential of Bergenia ciliata against lung cancer: an integrative molecular docking, ADMET, and molecular dynamics approach - Krittika Mukherjee; Sounok Sengupta; Ajay Kumar Singh; Rajiv Tonk; Shavkatjon Azizov; R. P. Rajwade; Deepak Kumar (In Silico Pharmacology, 2026)

KIF14 in cancer biology: implications for diagnosis and therapy - Ashok Kumar Bishoyi; Shaker Al-Hasnaawei; Subbulakshmi Ganesan; Aman Shankhyan; Anima Nanda; Aashna Sinha; Subhashree Ray; Deepak Nathiya (Clinical & Experimental Metastasis, 2026)

Deciphering the antimicrobial resistomes and microbiome landscape of open drain wastewater using metagenomics in a progressive Indian state - Shubham Kumar; Sejal Matra; Vinay Rajput; Harshada Ghode; Deepak Rathore; Shailendra Kumar; Sanjay Kamble; Syed Dastager; Abhay Bajaj; Asifa Qureshi; Atya Kapley; Mahesh Dharne (Environmental Research, 2026)

Valorization of lignin to produce nanofibers of industrial importance - Deepak Sharma; Neha Sharma; Lohith Kumar Dasarahally Huligowda; Mridul Umesh; Preeti Sharma; Pritha Chakraborty; Suma Sarojini; Charumathi Jayachandran; Ritu Pasrija; Vinay Kumar (Bioresource Technology, 2026)

Assessing wind energy potential during monsoon deep depressions using WRF Multi-Physics Ensemble over Odisha - Shakti Sagar Srivastav; Sandeep Pattnaik; Deepak Kumar; Anshul Sisodiya (Theoretical and Applied Climatology, 2026)

Nrf2–Keap1 Pathway and NLRP3 Inflammasome in Parkinson’s Disease: Mechanistic Crosstalk and Therapeutic Implications - Ridhi Jain; Lalitkumar Vora; Deepak Nathiya; Dharmendra Kumar Khatri (Molecular Neurobiology, 2026)
Neurodegenerative disorders such as Parkinson’s disease (PD) are characterized by the progressive degeneration of dopaminergic neurons, which is driven primarily by oxidative stress and chronic neuroinflammation. Central to the cellular antioxidant defense system is the nuclear factor erythroid 2–related factor 2 (Nrf2)–Kelch-like ECH-associated protein 1 (Keap1) pathway, which mitigates oxidative damage and preserves mitochondrial integrity. Concurrently, the NOD-like receptor pyrin domain-containing protein 3 (NLRP3) inflammasome acts as a key mediator of innate immune responses and has been increasingly implicated in neuroinflammatory cascades leading to neuronal loss in PD. Emerging evidence indicates a mechanistic interplay between the Nrf2–Keap1 axis and the NLRP3 inflammasome, wherein Nrf2 activation not only counteracts oxidative stress but also suppresses NLRP3-mediated inflammatory signaling. A comprehensive overview of the molecular crosstalk between the Nrf2 and NLRP3 pathways in the pathogenesis of PD, with emphasis on how impaired Nrf2 signaling exacerbates NLRP3 inflammasome activation, is provided. The preclinical and clinical findings on pharmacological agents that activate Nrf2 or inhibit NLRP3 as potential neuroprotective strategies in PD are also discussed. A growing body of evidence underscores the dual therapeutic benefit of targeting oxidative stress and inflammation via Nrf2 inducers and NLRP3 inhibitors. Nonetheless, obstacles such as restricted blood–brain barrier permeability, unintended effects, and variable clinical trial outcomes hinder the application of these findings in clinical settings. The advancement of disease-modifying therapies for PD hinges on continuous research aimed at deepening the mechanistic understanding of the Nrf2–NLRP3 axis and refining pharmacological strategies.

Insights into the Versatile Role of Extracellular Vesicles in the Treatment of CNS Disorders - Koushik Jana; Somnath Ghosh; Pijus Parua; Biplab Debnath; Jitu Halder; Rakesh Kumar Sahoo; Vineet Kumar Rai; Deepak Pradhan; Priyanka Dash; Chandan Das; Biswakanth Kar; Goutam Ghosh; et al. (Molecular Neurobiology, 2026)

Induced genetic variability and biochemical amelioration in vegetable soybean [Glycine max (L.) Merrill] using gamma rays and EMS treatments - Vishva Deepak Chaturvedi; Piyush Kumar Singh; Aparajita Dwivedi; Vedna Kumari (Euphytica, 2026)

Correction: Sustainable management of near‑field blast‑induced ground vibration for elevating limestone extraction potential in Indian mines‑ A case study - Aditya Rana; Arvind Kumar Gond; Saikat Banerjee; Deepak Kumar Tiwari; C. Sawmliana (Environmental Geochemistry and Health, 2026)

Lantana camara L. invasions alter belowground microbial symbiotic network and soil physicochemical characteristics, thereby inhibiting the growth of a native plant Ocimum sanctum L. - Pooja Shukla; Deepak Kumar; Utkarsh Talukdar; Gaurav Pal; Kanchan Kumar; Raghvendra Singh; Satish K. Verma (Symbiosis, 2026)

Field and microstructural evidence of coeval mafic–felsic magma mixing and mingling in the evolution of Neoarchean Berach granitoids, Aravalli craton, NW India - Bhagirathi Panigrahi; Ch Narshimha; Santosh Kumar; Deepak C Srivastava (Journal of Earth System Science, 2025)

Sleep Loss is Injurious to Health: A Wake-up Call for All - Hruda Nanda Mallick; Deepak Shrivastava; Manvir Bhatia; V. Mohan Kumar (Sleep and Vigilance, 2025)

Ai-powered decision-support system for maize Turcicum Leaf Blight: Novel ensemble models for disease forecasting with integrated fungicide advisory - G. Jadesha; Anupkumar M Bongale; H.C. Lohithaswa; N.B. Prakash; M.K.Prasanna Kumar; D. Deepak; Shreyans S Gadekar; Anurag Dhole; Yamanura Madival; R.Mohan Kumar; Deepak Dharrao (Computers and Electronics in Agriculture, 2025)

Ensemble Learning Based Method for Contingency Classification and Ranking in a Large Power System - Dheeraj Kumar Dhaked; Deepak Kumar Goyal; V.L. Narayanan; Yatinda Gopal; Dinesh Birla (Next Research, 2025)

RTD study through self-rotating liquid distributing stirrer in a continuous stirred tank for a liquid-liquid system - Lipika Das Samanta; Ankita Mazumder; Deepak Kumar Samal (Next Research, 2025)

Improved GA-ANN based optimized bio-deinking strategy for laccase produced from Trametes versicolor GGRK18, and its gene co-expression network analysis - Guddu Kumar Gupta; Tallon Coxe; Eetika Chot; Rajeev Kumar Kapoor; Deepak Chhabra; Nishi Kant Bhardwaj; Rajeev K. Azad; Pratyoosh Shukla (Journal of Environmental Chemical Engineering, 2025)

Valorization of papaya peel into value-added Khajure: A nutritional and physico-chemical characterization - Deepak Joshi; Neetu Dobhal; Nishant Kumar; Nutan Kaushik (Food and Humanity, 2025)

Bioethanol production from shrub willow (Salix spp.) using a low severity pretreatment and detoxification-free fermentation by engineered Saccharomyces cerevisiae - Kalyani Ananthakrishnan; Timothy A. Volk; Yong-Su Jin; Ankita Juneja; Obste Therasme; Deepak Kumar (Bioresource Technology Reports, 2025)

Production of natural food flavour (+)-γ-decalactone from castor oil through bio-chemical process with compiling the safety aspects - Naziya Syed; Shivani Chaturvedi; Suman Singh; Prashant Kumar; Deepak Kumar; Nitin Srivastava; Mohd. Faizan Husain; Praveen Kumar Sharma; Kavita Singh; Chandra Kant; Ashween Deepak Nannaware; Chandan Singh Chanotiya; et al. (Bioresource Technology Reports, 2025)

Bioactive compounds of Ganoderma species: molecular mechanisms and therapeutic potential in cancer and metabolic disorders - Aman Sharma; Divyesh Suvedi; Anand Kumar; Sonali Khanal; Rachna Verma; Dinesh Kumar; Deepak Kumar; Ashwani Tapwal; Vinod Kumar; Lukas Peter (World Journal of Microbiology and Biotechnology, 2025)

Low-Cost Adsorbents: A Sustainable Strategy for Emerging Contaminant Mitigation - Deepak Kumar; Jyoti Rani; Krishan Kumar Selwal (Water, Air, & Soil Pollution, 2025)

Wetlands in Transition: Understanding the Changes for Sustainable Conservation Practices Over the Indian Subcontinent - Neelam Chaudhary; Siddhant Gupta; Deepak Kumar Kannaujia; Sunita Verma (Wetlands, 2025)

Antibacterial, anti-biofilm and anti-virulence activity of biosynthesized silver nanoparticles against drug-resistant Staphylococcus aureus - Jaideep Singh; Ravi Kant Agrawal; Kajal Bankoti; Richa Sarkar; Mrinalini Saini; Keshav Kashyap; Deepak Kumar; Gaurav Kumar Sharma; Prabhat Nath Jha; Sonali Jain; Bhoj Raj Singh (Veterinary Research Communications, 2025)

Genome-wide identification of phospholipase A genes and effect on lipid content under abiotic stress in bread wheat (Triticum aestivum L.) - Akansha Madhawan; Prashant Kumar; Pulkit Sharma; Manisha Godara; Deepak Das; Abhishek Bhandawat; Rupam Kumar Bhunia; Joy Roy (Plant Physiology Reports, 2025)

Genomics assisted mapping of earliness in pea (Pisum sativum L.) - Parteek Kumar; Saurabh Yadav; Manisha Rani; Deepika Narang; Deepak Singla; Rajinder Kumar Dhall; Parveen Chhuneja; Priti Sharma (Molecular Biology Reports, 2025)

A pentatricopeptide repeat protein restores fertility in Moricandia arvensis based cytoplasmic male sterility system in Brassica juncea - Deepak Singh Bisht; Nitin Kumar; Anshul Watts; Rohit Chamola; Vajinder Kumar; Priyanka Jain; Manish Kumar; Balwant Singh Adhikari; Siddanna Savadi; Shripad Ramachandra Bhat (Molecular Genetics and Genomics, 2025)

Introgression of submergence tolerance QTL (SUB1) into mega rice variety ADT (R) 46 through marker assisted back crossing (MABC) approach - Thirumeni Saminadane; Karthick Jothiganapathy; Paramasivam Krishnaswamy; Nadaradjan Subbarayan; Premkumar Adhimoolam; Vandna Rai; Deepak Singh Bisht; Nagendra Kumar Singh; Rakesh Kumar Singh; Uma Shankar Singh; Abdelbagi Ismail (Journal of Plant Biochemistry and Biotechnology, 2025)

Advancements in CRISPR/Cas technology for generating herbicide tolerant crops: a comprehensive review - Dasari Sreekanth; Deepak Vishwanath Pawar; I. K. Sahadeo; Rajeev Kumar; P. S. Basavaraj; Survi Mahesh; C. R. Chethan; Satendra K. Mangrauthia; Shobha Sondhia; P. K. Singh; J. S. Mishra (Journal of Plant Biochemistry and Biotechnology, 2025)

Sustainable management of near-field blast-induced ground vibration for elevating limestone extraction potential in Indian mines- A case study - Aditya Rana; Arvind Kumar Gond; Saikat Banerjee; Deepak Kumar Tiwari; C. Sawmliana (Environmental Geochemistry and Health, 2025)

Effect of heating-liquid nitrogen cooling cycles on the physical properties and tensile strength of basalt - Bikash Kumar Ram; Rajeswar Das; Deepak Amban Mishra; Ranjan Pramanik; Himangshu Kakati; Rajat Jain (Bulletin of Engineering Geology and the Environment, 2025)

Integrated algal bioremediation and ZnS/Cu nanocatalyzed biodiesel synthesis for sustainable bioenergy recovery - Nguyen Van Minh; Shanmugavel Kuppusamy; Deepak K; Krishnamoorthy Ramalingam; Shivendu Saxena; Ranganathaswamy Madihalli Kenchappa; Jayant Kumar Nath (Algal Research, 2025)

Hyperspectral image denoising through hybrid spectral transformer network - Dhirendra Prasad Yadav; Deepak Kumar; Anand Singh Jalal; Bhisham Sharma (Advances in Space Research, 2025)

RNA interference (RNAi) for insect pest management: understanding mechanisms, strategies, challenges and future prospects - Deepak Kumar Mahanta; J. Komal; Tanmaya Kumar Bhoi; Ipsita Samal; Sangeeta Dash; Sumit Jangra (Biologia Futura, 2025)

Impact of Mulching on Yield, Quality, and Nutrient Content in Fruit Crops: A Review - Mohni Parmar; Deepak Singh; Pankaj Maida; Ram Kumar Rai; Khushboo Tandon; Anita Kerketta (Applied Fruit Science, 2025)

Impact of Micronutrients on Flowering, Yield, and Fruit Quality Attributes of Strawberry (Fragaria × ananassa Duch) cv. Camarosa Under Open Field Conditions - Yogendra Singh; Govind Gupta; Ujwal Virkhare; Mukul Kumar; Prajwal Nimbulkar; Suman Kumari; Yogita Chouhan; Harshit Jangid; Suresh Chandra Gurjar; Om Prakash Lodha; Deepak Kher (Applied Fruit Science, 2025)

Exogenous Calcium Chloride and Chitosan Improved Postharvest Quality and Storability of Mango cv. ‘Mallika’ - Nishant Arya; Kumari Karuna; Ruby Rani; Abhay Mankar; Roopendra Kumar; Deepak Kumar (Applied Fruit Science, 2025)

Journey from phytomolecules to bioactive molecules: a phytopharmacological exploration of botanicals and standardised extract of Picrorhiza kurroa - Kalyan Hazra; Deepak Kumar; Sudipto Debnath; Tushar Kanti Mandal; Preeti Sharma; Ajay Kumar Meena (Natural Product Research, 2025)

Correction: Adsorption-desorption behaviour of arsenic on naturally occurring clay-organic complexes in an Alfisol and Inceptisol - Deepak; Ruma Das; Debasis Golui; Nayan Ahmed; Ram Swaroop Bana; Amrit Kumar Jha; Siba Prasad Datta (Environmental Sustainability, 2025)

UPLC-QTOF-MS based targeted metabolomics to unravel the hepatoprotective marker compounds of Swertia chirayita - Dhriti Verma; Saloni Thakur; Hitesh Shrimal; Satish Kumar; Joydeep Das; Biswatrish Sarkar; Deepak N. Kapoor; Prashanta Kumar Deb (Natural Product Research, 2025)

A novel framework for measuring natural attenuation in the unsaturated zone below MSW dumpsites - Pranjal Singh; Deepak Kumar Haritwal; GV Ramana; Manoj Datta (Waste Management, 2025)

Biosensor to detect and analyze food quality: Integrating chemical sensors with nanotechnology - Deepak Kumar; Rishabha Malviya (Trends in Food Science & Technology, 2025)

Zero mortality in 2024: Retrospective assessment of snakebite cases and their effective management at Demow rural community health centre, Sivasagar, Assam, India - Amit Talukdar; Prasenjit Roy; Jayaditya Purkayastha; Simanta Jyoti Taye; Deepak Agarwalla; Ruma Shyam; Hridoy Baruah; Rentu Kumar Gam; Gaurav Choudhary; Rajib Jangid; Anurag Borthakur; Surajit Giri; et al. (Toxicon, 2025)

Predicting filter cake thickness in drilling fluids using machine learning techniques - Minghui Ou; Mohammed Al-Bahrani; Raman Kumar; Ashutosh Pattanaik; Hrushikesh Sarangi; Deepak Gupta; V. Naga Bhushana Rao; Mamurakhon Toshpulatova; Vikasdeep Singh Mann; Heyder Mhohamdi; Usama S. Altimari; Aseel Smerat; et al. (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Bioprocessing kodo millet: Effects of germination and fermentation on nutritional composition, anti-nutrients, and functional bioactives - Priyanka Dash; Anshika Priyadarsani Sahoo; Chandan Das; Vineet Kumar Rai; Jitu Halder; Rakesh Kumar Sahoo; Deepak Pradhan; Tushar Kanti Rajwar; Biswakanth Kar; Goutam Ghosh; Goutam Rath (Journal of Cereal Science, 2025)

Applying stacked ensemble methods to predict future rainfall based on historical weather data - Deepak Sharma; Preeti Gulia; Nasib Singh Gill; Aliya Aleryani; Prashant Kumar Shukla; Piyush Kumar Shukla (Theoretical and Applied Climatology, 2025)

Loss-of-function of VrMYB104 in Mungbean hampers growth and multiple adaptive responses under waterlogging stress - Prashasti Pandey; Shivani Kashaudhan; Siddharth Maurya; Deepak Kumar (Plant Cell Reports, 2025)

Exploring Exosome-Based Approaches for Early Diagnosis and Treatment of Neurodegenerative Diseases - Vibhav Varshney; Baneen C. Gabble; Ashok Kumar Bishoyi; Pooja Varma; Sarraa Ahmad Qahtan; Aditya Kashyap; Rajashree Panigrahi; Deepak Nathiya; Ashish Singh Chauhan (Molecular Neurobiology, 2025)

Anti-inflammatory potential of telmisartan compared to other antihypertensives: secondary outcomes from a randomized trial - Simi Bridjit Gomaz; Jaykaran Charan; Amal Mohandas; Pravesh Aggarwal; Deepak Kumar; Dharmveer Yadav; Ravindra Shukla; Sneha Ambwani; Rimple Jeet Kaur (Inflammopharmacology, 2025)

A remote sensing algorithmic framework for characterizing chromophoric dissolved organic matter in lagoon-estuarine systems - Ishan D. Joshi; Abhishek Kumar; Sambit Singh; Susmita Raulo; Tamoghna Acharyya; Deepak R. Mishra (Science of The Total Environment, 2025)

Geochronology and geochemical characteristics of sulphides from Tianzuo hydrothermal field (63°32ʹ E), South West Indian Ridge - Parijat Roy; Koushick Sen; Surya Prakash L.; V. Yu Kuznetsov; Fedor Maksimov; Deepak Kumar; S.S. Sawant; Deepak Kumar Agarwal; Srinivas Rao A.; P. John Kurian (Marine and Petroleum Geology, 2025)

Innovative food safety strategy: Eugenol nanoemulsion with lactobacillus derived post-biotic biopolymer for biofilm inhibition on food and contact surfaces - Sangeeta Balyan; Vikas Dadwal; Deepak Kumar Jha; Bhimanagouda S. Patil (Food Control, 2025)

PINTO: Physics-informed transformer neural operator for learning generalized solutions of partial differential equations for any initial and boundary condition - Sumanth Kumar Boya; Deepak N. Subramani (Computer Physics Communications, 2025)

Unlocking the potential of sodium-ion batteries: Synthesizing sodium iron silicate cathodes using aliphatic diols - Lalit Kumar Singh; Deepak Verma; Wonjoong Yoon; Anith Dzhanxinah Mohd Sarofil; Mingony Kim; Sambedan Jena; Kyung Yoon Chung; Jaehoon Kim (Chemical Engineering Journal, 2025)

Advancements in Magnetic Nanoparticles for Microplastic Removal: A Magnetic Solution to Microplastic Pollution - Riya Goel; Avinash Sharma; Abija James; Deepak Kumar; Yashika Dhir; Sunny Dhir; Ankur Kaushal; Shagun Gupta; Deepak Kala; Naveen Kumar Kaushik; Md Salik Noorani; Rupak Nagraik (Water, Air, & Soil Pollution, 2025)

Grain arsenic accumulation is independent of agronomic traits in rice under field conditions - Parminder Singh Saini; Manish Pandey; Samrath Baghel; Suraj Patil; Parmeshwar Kumar Sahu; Vinay Kumar; Bikram Kishore Das; Deepak Sharma; Ashish Kumar Srivastava (Physiology and Molecular Biology of Plants, 2025)
Arsenic (As) is a toxic environmental pollutant and a group-1 carcinogen, posing serious concern for human health. Rice and rice-based food products are considered as one of the major sources for As contamination into the human food-chain. Hence, world-wide concerted research efforts are going on, either to identify and/or develop low-As accumulating rice genotypes. The present study evaluated the natural accessions of rice, comprising of landraces and farmer’s varieties, under the naturally As-contaminated sites of Chhattisgarh, India, which is well-known for its richness in terms of rice production as well as varietal diversity. The wide-range spectrum of grain-As was obtained in 120 selected genotypes, with 90 and 81 accessions having As-accumulation above the WHO permissible limit for white (0.2 mg kg −1 ) and brown (0.3 mg kg −1 ) rice, respectively. The lowest grain-As accumulation among the varieties was seen in cultivated varieties (Badsabhog Sel 1 and Bahadur Sel 1) and landraces (Bastul and Kanaklata), which can be either cultivated or used as suitable donor in breeding programs. Among different agronomic traits, the plant height was identified as most-responsive parameter for assessing As-toxicity. The comparative assessment of agro-morphological traits although showed variations under naturally As-contaminated site; however, no significant correlation was seen in terms of grain-As accumulation, indicating the complexity for on-site field screening of low As-accumulating genotypes. Taken together, the results identified the potential low-As accumulating genotypes and highlighted the grain-As accumulation, as a complex multi-genic trait.

Preclinical evaluation of sodium copper chlorophyllin: safety, pharmacokinetics, and therapeutic potential in breast cancer chemotherapy and cyclophosphamide-induced bladder toxicity - Neha Ramani; Raghavendra S. Patwardhan; Rahul Checker; Babita Singh; Shruti Morjaria; Binita K. Kumar; Murari Gurjar; Vikram Gota; Deepak Sharma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Myo-inositol Reduces Drought-Induced Oxidative Damage and Improves Mungbean Photosynthetic Efficiency and Antioxidant Machinery - Tirth Bhargav Bhai Patel; Khushboo; Pramod Kumar Saroj; Neelam Prabha Negi; Meenakshi Raina; Prashasti Pandey; Ravi Rajwanshi; Deepak Kumar (Journal of Plant Growth Regulation, 2025)

Seaweed extract-based biostimulants alleviate nutrient stress and enhance productivity and grain quality of wheat through efficient use of fertilizers nutrients under sub-optimal NPK application - Bijan Kumar Mondal; Abir Dey; M. C. Meena; Debarup Das; Archana Singh; Shivani Nagar; Prasenjit Ray; P. K. Upadhyay; Deepak Bamel; Amit Kumar Dash; Krishna Kumar Mourya; Narender Yadava; et al. (Journal of Applied Phycology, 2025)

Phyto-pharmacognostical characterisation, residual analysis of unexplored high altitude Himalayan species Iris kashmiriana Baker rhizome and antimicrobial potential of essential oil - Susmita Roy; Sreya Dutta; Deepak Kumar; Ayan Samadder; Rajosik Bose; Shyam Baboo Prasad; Ajay Kumar Meena; Gajji Babu; Kalyan Hazra (Natural Product Research, 2025)

Geospatial evaluation of urban marginal lands for the forestry development in Northern India - Sheikh Adil Edrisi; Vivek Verma; Deepak Kumar (Environment, Development and Sustainability, 2025)

Adsorption-desorption behaviour of arsenic on naturally occurring clay-organic complexes in an Alfisol and Inceptisol - Deepak; Ruma Das; Debasis Golui; Nayan Ahmed; Ram Swaroop Bana; Amrit Kumar Jha; Siba Prasad Datta (Environmental Sustainability, 2025)

Changing land use and land cover dynamics in Chhilchhila Wildlife Sanctuary, Haryana, India: a winter migratory bird study - Piyush Goyal; Deepak Rai; Sandeep Kumar (Environmental Monitoring and Assessment, 2025)

Change point detection of processes using graph neural differential convolutional network with contrastive loss - Umang Goswami; Deepak Kumar; Hariprasad Kodamana; Manojkumar Ramteke (Process Safety and Environmental Protection, 2025)

MLTSDC: Multi Level Transformer Based Sugarcane Disease Classifier - Shyam Singh Rajput; Deepak Rai; Harsh Nandan Verma; Rohan Kumar Choudhary; Shivam; Shyam Shankar Dwivedi (Physiological and Molecular Plant Pathology, 2025)

New insight into the shallow sub-surface for geothermal prospection of Puga valley, Ladakh, India from electrical resistivity tomography - Dewashish Kumar; Arun Kumar Ojha; Ved Prakash Maurya; M. Satyanarayanan; Ratnakar Dhakate; Prakash Kumar; Deepak Kumar; Jitendra Singh Rathore (Geothermics, 2025)

Microfluidization based nano/sub-micron curcumin formulations for food and nutraceuticals: Physico-functional characteristics and safety aspects - Kiran Verma; Ayon Tarafdar; Deepak Kumar; T.P. Sari; Prarabdh C. Badgujar; Sunil Pareek; Elham Assadpour; Seid Mahdi Jafari (Food Chemistry, 2025)

Unravelling the physicochemical and antioxidant profiles of guava genotypes across developmental stages and seasonality - M.R. Chandana; Amit Kumar Goswami; Virendra Singh Rana; Chavlesh Kumar; Sanjay Kumar Singh; Suneha Goswami; Deepak Singh Bisht; Viswanathan Chinnusamy; Gyan Prakash Mishra; Jigni Mishra; Jadhav Parth Janardhan; M.K. Sushravya (Food Bioscience, 2025)

Quantifying contamination risks: Groundwater vulnerability assessment at an MSW dumpsite with advanced profiling tools - Pranjal Singh; Deepak Kumar Haritwal; G.V. Ramana; Manoj Datta (Environmental Pollution, 2025)

Epidemiological profile and factors associated with the delay in initiation of post exposure prophylaxis of animal bite cases at the tertiary care hospital, New Delhi: a hospital based study - Ishant Kumar; Debashish Parmar; Sanjeet Panesar; Deepak Dhamnetiya (VirusDisease, 2025)

Non-abundance of Cellulose and Lignin in Crop Residue Biomass Increases Decomposability and Lowers Temperature Sensitivity of the Process and Helps in Labile Soil Organic Carbon build-up - Deepak Bamel; Abir Dey; Bijan Kumar Mondal; Ranjan Bhattacharyya; Debarup Das; Shrila Das; Tapas Kumar Das; Amit Kumar Dash (Journal of Soil Science and Plant Nutrition, 2025)

Soil Carbon and Nutrient Cycling Regulated by Fine Roots Distribution and Dynamics in Teak (Tectona grandis L.)-Based Agroforestry System in Semi-Arid Central India - Asha Ram; Shubham Choure; Inder Dev; Naresh Kumar; Deepak Singh; Dhiraj Kumar; Sovan Debnath; S. Suresh Ramanan; Ashutosh Dwivedi; Raju Kumar; Sanjana Maurya; Subhash Babu; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Effect of Phalaris minor and Medicago denticulata on Wheat Growth and Yield Under Drought Stress: Physiological and Biochemical Insights - Dasari Sreekanth; Deepak Vishwanath Pawar; P. S. Basavaraj; Rajeev Kumar; Survi Mahesh; C. R. Chethan; A. Jamaludheen; Shobha Sondhia; P. K. Singh; J. S. Mishra (Journal of Plant Growth Regulation, 2025)

An Economical Industrially Feasible Approach for Denim Biobleaching: Reusing of Laccase and Mediator for Multiple Cycles - Sunena Jassal; Rahul Warmoota; Anupama Sharma; Sarita Sheoran; Deepak Kumar; Naveen Gupta (Indian Journal of Microbiology, 2025)

Microneedle patches: the next frontier in cardiovascular care - Simran Deep Kaur; Shivanshu Choudhary; Santimoy Sen; Deepak B. Pemmaraju; Sachin Kumar Singh; Deepak N. Kapoor (Drug Delivery and Translational Research, 2025)

Extracting urban patterns in undulating landscapes from SAR data with thresholding approach - Noyingbeni Kikon; Deepak Kumar; Syed Ashfaq Ahmed (Applied Geomatics, 2025)
Urban footprint extraction is used for the extraction or classification of various land use classes like water bodies, urban areas, vegetation, and others over any region. But this is quite difficult to perform in the hilly terrains. The work recognises the optimal threshold value for the extraction of urban features is based on the coherence properties of the processed SAR dataset. The work utilises two Sentinel-1 A satellite images acquired on 7th January 2020 and 31st January 2020 respectively. The work of urban footprint is accomplished with (a) the creation of a coherence image with a pair of SAR imageries; (b) further pre-processing of the coherence image to apply multi-looking and terrain correction; (c) the derived coherence image is stacked to create a false colour composite image to provide an input for feature extraction; (d) feature extraction is performed by masking out the urban areas at different thresholds levels. The results of the extracted urban footprint are authenticated with a comparison to the optical dataset. Some sample locations are selected for validating the results from Google Earth historical imagery. Results indicate that the urban features extracted at a threshold value of 0.5 provide improved results in comparison to the threshold values of 0.4, 0.6, and 0.7. The pixels of urban features at a coherence threshold of 0.5 are lying at the same position where urban areas are present. The work can be further propagated for the identification and monitoring of other urban features regardless of any weather conditions for several other applications.

Spatial modelling of soil erosion in sub-tropical region of Central India using AHP and geospatial approach - Ashwini Suryawanshi; Gangalakunta P. Obi Reddy; Nirmal Kumar; Benukantha Das; Deepak Mohekar; Roshan R. Wakode; Burhan U. Choudhury; Meesala Siva Shankar Nagaraju (Environmental Monitoring and Assessment, 2025)

New paleomagnetic data from the Ladakh Molasse Group provide a Late Oligocene (26.5 Ma) age for the first post India–Asia collision continental sediments: Biostratigraphic implications - Wasim Abass Wazir; Rajeev Patnaik; Mohammad Arif; Sarvendra P Singh; Binita Phartiyal; Chris Gilbert; Ramesh Kumar Sehgal; Deepak Choudhary; Rohit Kumar; Mohd Ali Wazir (Journal of Earth System Science, 2025)

Understanding Bihar’s climate risks: a district-level assessment of climate trends, projections, exposure, hazards, and vulnerability - Shashidhar Kumar Jha; Saransh Bajpai; Mani Bhushan Jha; Hemant Kumar; Deepak Kumar Raj (Environmental Monitoring and Assessment, 2025)

In vitro and in silico anti-Alzheimer study of rutin embedded with zinc chloride loaded bovine serum albumin nanoparticles - Bibhanwita Satpathy; Ivy Saha; Jitu Halder; Tushar Kanti Rajwar; Vineet Kumar Rai; Deepak Pradhan; Ajit Mishra; Ritu Mahanty; Priyanka Dash; Chandan Das; Biswakanth Kar; Goutam Ghosh; et al. (Tissue and Cell, 2025)

Escitalopram, an antidepressant, stimulates steroidogenesis in mouse Leydig cells - Pramila Kulhari; Bodhana Dhole; Saloni Verma; Moses Azaraiah Jala; Pramod Kumar; Deepak Pandey; Pradeep Kumar Chaturvedi; Surabhi Gupta (Reproductive Toxicology, 2025)

Decoding late Quaternary paleoclimatic signatures from the western Bay of Bengal: A multiproxy approach - Nayana V. Haridas; Upasana S. Banerji; D. Padmalal; K. Maya; P. John Kurian; Ravi Bhushan; Ankur J. Dabhi; Deepak Kumar Agarwal; A.K. Sudheer; Ruta B. Limaye; K.P.N. Kumaran (Quaternary International, 2025)

Corrigendum to “Lithospheric structure beneath the Upper Indus Basin and its adjacent regions from inversion of surface wave dispersion” [Physics of the Earth and Planetary Interiors Volume 362, May 2025, 107345] - Deepak Kumar; G. Suresh; M.L. Sharma; Siddharth Dey; S.C. Gupta (Physics of the Earth and Planetary Interiors, 2025)

Late Holocene rapid terrestrialization of abandoned channels and vulnerability in the Himalayan Foreland basin area in India - Jiarul Alam; Deepak Kumar Mandal; Sanjoy Barman; Pankaj Singha (Journal of Cleaner Production, 2025)

Seasonal Incidence of Schizotetranychus krungthepensis Naing & Auger on Sugarcane: Correlation with Weather Parameters and Crop Impact - Arshpreet Singh; Manmeet Brar Bhullar; Rajinder Kumar; Paramjit Kaur; Mayur Deepak Wabhitkar (Sugar Tech, 2025)

Gut Microbiota-Based Interventions for Parkinson’s Disease: Neuroprotective Mechanisms and Current Perspective - Deepak Kumar; Mahendra Bishnoi; Kanthi Kiran Kondepudi; Shyam Sunder Sharma (Probiotics and Antimicrobial Proteins, 2025)

Beneficial Effect of Synbiotic Combination of Limosilactobacillus fermentum FS-10, Lactiplantibacillus plantarum Lp1-IC and Short-Chain Fructooligosaccharides in Colitis Murine Model - Radha Pujari; Deepak Jadhav; Ashvini Angal; Jaserah Syed; Ashok Kumar Dubey (Probiotics and Antimicrobial Proteins, 2025)

Development and Optimization of Setraconazole Invasomes, Gels, and Films for Enhanced Transdermal Delivery and Topical Fungal Treatment - Dibya Sundar Panda; Deepak Kumar Dash; Riya Vaiswade; Gayatri Gupta; Ranjan kumar Giri; Ameeduzzafar zafar; Omar Awad Alsaidan; Shaliputra P. Magar (Journal of Pharmaceutical Innovation, 2025)

French Type Vertical Flow Constructed Wetland as a Sustainable Solution for Domestic Sewage Treatment - Shivraj Anand; Deepak Gupta; Chhavi Siwach; Jens Nowak; Heribert Rustige; Virendra Kumar Mishra (Environmental Management, 2025)

Thermophiles in nanosized biocalcification: a novel approach for heavy metal remediation - Sujata Negi; Shagun Sharma; Deepak Pant; Sonali Sharma; Kalpana Chauhan; Anand Giri; Manoj Kumar; Kulamani Parida (BioMetals, 2025)

Transcriptional assessment of pro-inflammatory and immune markers in the endometrium of bitches affected with CEH-Pyometra - Ajeet Kumar; Deepak Kumar; J.K. Prasad; Ajeet Kumar; Amrita Behera; Alok Kumar (Animal Reproduction Science, 2025)

The Impact of Quality of Sleep and Effect of Sleep Apnea on Periodontal Health - Swathi Devarajan; P. Sreelakshmi; Divya Kumar; Deepak Moses Ravindran; Dhanadivya Krishnakumar; S. K. Balaji (Sleep and Vigilance, 2025)

A review of biofuels and bioenergy production as a sustainable alternative: opportunities, challenges and future perspectives - Rajat Singh; Ashish Gaur; Priyanka Soni; Rajul Jain; Gaurav Pant; Deepak Kumar; Gaurav Kumar; SZM Shamshuddin; Nabisab Mujawar Mubarak; Mohammad Hadi Dehghani; Suhas; Khalid Ansari (Journal of Environmental Health Science and Engineering, 2025)

Morpho-cultural variability, pathogenicity and molecular identification of Phytophthora cajani isolates causing blight disease of pigeonpea in India - Raj K. Mishra; Abhishek Bohra; Deepak Kumar; A.K. Parihar; K.K. Hazra; Sonika Pandey; Monika Mishra; Satheesh Naik SJ; Nidhi Kumari; D. Datta; Smita Tiwari; Naimuddin; et al. (Physiological and Molecular Plant Pathology, 2025)

Plant secondary metabolites in defense against phytopathogens: Mechanisms, biosynthesis, and applications - Punet Kumar; Deepak Kumar; Sushma Pal; Sangam Singh (Physiological and Molecular Plant Pathology, 2025)

Recovery of valuable metals from spent lithium ion battery: Technologies, sustainability, and challenges in India - Neeraj Kumar; Ashutosh Mishra; Deepak Kumar (Minerals Engineering, 2025)

Trends and advances in liposome formulation technology with an emphasis on ensuring safety and quality in food and drug applications - Pawan Prabhakar; Soubhagya Tripathy; Deepak Kumar Verma; Smita Singh; Mamta Thakur; Amit Kumar Singh; Prem Prakash Srivastav; Mamoni Banerjee; Ami R. Patel; Mónica L. Chávez González; Gemilang Lara Utama; José Sandoval-Cortés; et al. (Food Bioscience, 2025)

Lactobacillus-derived exopolysaccharide nanoemulsions for essential oils Delivery: Improving bioaccessibility, gastrointestinal stability, and prebiotic function - Sangeeta Balyan; Vikas Dadwal; Samikshya Bhattarai; Deepak Kumar Jha; Bhimanagouda S. Patil (Food Bioscience, 2025)

Deformation dynamics and hazard of slow-moving landslides: The 2023 Joshimath event, Uttarakhand Himalaya - Prohelika Dalal; Manoj Hari; Yuankun Xu; Batakrushna Senapati; Param Gautam; Deepak Kumar Tiwari; Roland Bürgmann; Bhaskar Kundu (Engineering Geology, 2025)

Seed inhabiting bacterial endophyte Bacillus amyloliquefaciens (SS7) defends sorghum Sudan grass seedlings from a phytopathogen Rhizoctonia solani - Kanchan Kumar; Deepak Kumar; Gaurav Pal; Satish K. Verma (World Journal of Microbiology and Biotechnology, 2025)

Slope stability assessment of the section along Balipara–Charduar–Tawang Road, Arunachal Pradesh, India - Deepak Kumar Singh; Amit Kumar Verma; Rahul Kumar Verma; T N Singh (Journal of Earth System Science, 2025)

Molecular docking and molecular dynamics simulation studies of thiazole-coumarin and thiazole-triazole conjugates against Mpro and ACE2 receptor for SARS COV-2 - Deepak Mishra; Ram Singh; Nupur S. Munjal; Naresh Kumar; Prashant Kumar; Poonam; Sandeep Sharma (In Silico Pharmacology, 2025)

INCOIS air-sea Flux Reference System onboard ORV Sagar Nidhi: overview and initial results - B. Praveen Kumar; Abhijith Raj; Asish K. Sasidharan; N. Sureshkumar; A. A. Gnanaraj; Deepak Sankar; K. Ramasundaram; Venkata Jampana; E. Pattabhi Rama Rao (Frontiers in Marine Science, 2025)
Accurate estimation of air-sea fluxes is essential for advancing ocean modeling, observational studies, and understanding air-sea interactions. To address this need, the Indian National Centre for Ocean Information Services (INCOIS) developed and deployed a Flux Reference System (INCOIS-FRS) onboard ORV Sagar Nidhi . This article provides an overview of the system, its components, data acquisition methods, flux computation techniques, and preliminary results. The INCOIS-FRS integrates an Eddy Covariance Flux System (ECFS) and an Automated Weather Station (AWS). The ECFS collects high-frequency (20 Hz) data to directly estimate the latent heat flux (LHF), sensible heat flux (SHF), and momentum flux (τ) using the Eddy Covariance (EC) method. The AWS records meteorological and oceanic variables at 1 Hz, enabling flux estimates using the COARE 3.5 algorithm. A spectrally flat Class-A pyranometer and a pyrgeometer provide climate-grade measurements of downward shortwave and longwave radiation, which, combined with EC-derived SHF and LHF, yield the net heat flux. This article presents preliminary results inferred from data collected by INCOIS-FRS during a cruise in the Arabian Sea from 1–16 July 2023. Data from this system are useful for validating model outputs and satellite observations, refining flux parameterizations, marine boundary layer studies, and improving air-sea interaction models. INCOIS-FRS represents a first step toward equipping more oceanographic platforms, both crewed and uncrewed, with flux reference units. Future plans include expanding such deployments to enhance observational coverage and support research on air-sea fluxes across the Indian Ocean and other regions.

Erratum to: “Aromatic crops cultivation a promising option in Indian agricultural system to support circular economy: A sustainable approach” [Sustainable. Chem. Pharm. 42, (2024), 101863 - Suman Singh; Poornendra Mishra; Shivam Singh Chauhan; R.K. Lal; Prasant Kumar Rout; Ashween Deepak Nannaware (Sustainable Chemistry and Pharmacy, 2025)

Molecular characterization of a begomovirus associated with yellow mosaic disease of Acalypha indica - Sunil Kumar; Deepak Kumar; Olawale Arogundade; Supriya Chakraborty (VirusDisease, 2025)

Genetic parameters estimate of milk yield and composition of Bhadawari buffalo in India - Badri Prasad Kushwaha; Sultan Singh; Krishna Kunwar Singh; Deepak Upadhyay; Pooja Tamboli; Tirtha Kumar Datta; Sylvia Lalhmingmawii; Indrajit Gayari; Ajoy Mandal (Tropical Animal Health and Production, 2025)

Elucidating the interactive effects of drought, weeds, and herbicides on the physiological, biochemical, and yield characteristics of rice - Dasari Sreekanth; Deepak Vishwanath Pawar; Survi Mahesh; C. R. Chethan; Shobha Sondhia; P. K. Singh; J. S. Mishra; Nagaraju Mukkamula; B. Kiran Kumar; P. S. Basavaraj (Plant and Soil, 2025)

Assessing landslide velocity scales with acoustic emission active waveguides for early warning system - Deepak Kumar; Ajit K. Mahapatro; Sushil Kumar Singh (Natural Hazards, 2025)

Plant Defense Hormones: Thermoregulation and Their Role in Plant Adaptive Immunity - Zahoor Ahmad Mir; Sajad Ali; Subaya Manzoor; Divya Sharma; Deepak Sharma; Anshika Tyagi; Ab Waheed Wani; Sundeep Kumar; Belay T. Ayele (Journal of Plant Growth Regulation, 2025)

Nematicidal activity of green synthesized silver nanoparticles using Parthenium hysterophorus and their impact on morphology and photosynthetic pigments of citrus plants - Jigmet Yangchan; Dixit Sharma; Mohd Ali; Deepak Sharma; Pankaj Thakur; Dharminder Kumar; Alka Rana; Sunil Kumar (Journal of Plant Diseases and Protection, 2025)

Screening and association studies of morphological traits with sheath blight resistance in rice (Oryza sativa L.) genotypes - Mansi Mishra; B. S. Chethana; C. A. Deepak; Aditya Kukreti; Shashi Kumar Gupta (Indian Phytopathology, 2025)

Morphological variability and genetic diversity assessment of agronomic traits in cowpea (Vigna unguiculata (L.) Walp.) core collection using multivariate analysis - Divya Chaudhary; Padmavati Ganpat Gore; Dhammaprakash Pandhari Wankhede; Deepak Khanderao Patil; Shashi Bhushan Choudhary; Annabathula Mohan Rao; Raj Kumar Gautam; Gyanendra Pratap Singh; Kuldeep Tripathi (Genetic Resources and Crop Evolution, 2025)

Predictive Role of Serotonin Receptor (5HTR2A) and Dopamine Receptor (DRD2) gene polymorphisms in risperidone-induced weight gain and hyperprolactinemia in patients with schizophrenia - Alladi Charanraj Goud; Ravi Philip Rajkumar; Deepak Gopal Shewade; Luxitaa Goenka; Suresh Kumar Srinivasamurthy (European Journal of Clinical Pharmacology, 2025)

Intelligent growth of holy basil: an iot-based hydroponics system empowered by the CRL-SHS Algorithm - T. Kumaragurubaran; Rahul Chiranjeevi; Elangovan D; Deepak Kumar K (Earth Science Informatics, 2025)

Formononetin exerts synergistic action with artesunate against multi-drug-resistant P. falciparum arresting ring-to-schizont transition by inducing reactive oxygen species - Saurabh Kumar; Deepak Singh Kapkoti; Pooja Rani Mina; Ajeet Kumar Verma; Parmanand Kumar; Ramdas; Karuna Shanker; Rajendra Singh Bhakuni; Anirban Pal; Mahendra P. Darokar (Archives of Microbiology, 2025)

Assessment of traditional knowledge on dye-yielding plants in the Jaunpur region of the Uttarakhand Himalayas - Shivam Nautiyal; Deepak Kumar Semwal; Ruchi Badoni Semwal (Vegetos, 2025)

Enhanced indole-3-acetic acid production by Enterobacter hormaechei APSB3 through heuristic artificial neural network and particle swarm optimisation - Aditya Sharma; Guddu Kumar Gupta; Deepak Chhabra; Piyush Pandey; Pratyoosh Shukla (Environmental Sustainability, 2025)

Lithospheric structure beneath the Upper Indus Basin and its adjacent regions from inversion of surface wave dispersion - Deepak Kumar; G. Suresh; M.L. Sharma; Siddharth Dey; S.C. Gupta (Physics of the Earth and Planetary Interiors, 2025)

Hybrid AI models for thermal imaging and analysis of neurological disorders using thermoplasmonics - Y. Ravi Kumar; M. Vanitha; KDV Prasad; Kanchan Bala; Deepak Gupta; P. Venkateswara rao (Journal of Thermal Biology, 2025)

Application of high-resolution site characterisation tools and sampling methods for assessing microplastic migration beneath MSW dumpsites - Deepak Kumar Haritwal; Pranjal Singh; G.V. Ramana; Manoj Datta (Journal of Hazardous Materials, 2025)

A novel duplex qPCR-HRMA technique for simultaneous detection of Listeria monocytogenes and Salmonella typhimurium in meat products - G. Ajay; M.R. Vishnuraj; N. Aravind Kumar; Anusha Chauhan; Deepak B. Rawool; S.B. Barbuddhe (Food Chemistry, 2025)

A Geoinformatics-Based Comparative Study of Multi-Criteria Decision Making Approaches of Groundwater Potential Zoning in Ken Basin, India - Deepak Patle; Manoj Kumar Awasthi; Shailesh Kumar Sharma; Yogesh Kishore Tiwari (Journal of the Indian Society of Remote Sensing, 2025)

Evaluation of genotype × environment interactions for seed yield in field pea (Pisum sativum L.) genotypes using multivariate analysis model - Amit Sharma; Rajesh Yadav; Ravika Sheoran; Pawan Kumar; Deepak Kaushik; Kavita Dhaka; Nikhil Gangadharaiah; Arpit Sharma (Euphytica, 2025)

Tectonic evolution of the Greater Himalayan Sequence and its associated fault systems in space and time: a monazite perspective - Md. Sunny Hussain; Purbajyoti Phukon; Pranjit Kalita; A. Krishnakanta Singh; Deepak Kumar; Himangshu Saikia (International Geology Review, 2025)

Multi-Agent Reinforcement Learning for task allocation in the Internet of Vehicles: Exploring benefits and paving the future - Inam Ullah; Sushil Kumar Singh; Deepak Adhikari; Habib Khan; Weiwei Jiang; Xiaoshan Bai (Swarm and Evolutionary Computation, 2025)

Time series forecasting of microalgae cultivation for a sustainable wastewater treatment - Karthikeyan Meenatchi Sundaram; Deepak Kumar; Jintae Lee; Selvaraj Barathi; Karthik Rajendran (Process Safety and Environmental Protection, 2025)

Flow dynamics and bed morphology in a narrow channels: A comparative study of experimental and numerical approaches to velocity distribution - Pritam Kumar; Vangapandu Deepak; Anurag Sharma (Geomorphology, 2025)

Retraction notice to “Resource recovery and biorefinery potential of apple orchard waste in the circular bioeconomy” [Bioresour. Technol. 321 (2021) 124496] - Shiyi Qin; Balendu Shekher Giri; Anil Kumar Patel; Taner Sar; Huimin Liu; Hongyu Chen; Ankita Juneja; Deepak Kumar; Zengqiang Zhang; Mukesh Kumar Awasthi; Mohammad J. Taherzadeh (Bioresource Technology, 2025)

Retraction notice to “Recent advances in lignocellulosic and algal biomass pretreatment and its biorefinery approaches for biochemicals and bioenergy conversion” [Bioresource Technol. 367 (2023) 128281] - Yue Zhang; Zheli Ding; Md Shahadat Hossain; Rupesh Maurya; Yulu Yang; Vijai Singh; Deepak Kumar; El-Sayed Salama; Xinwei Sun; Raveendran Sindhu; Parameswaran Binod; Zengqiang Zhang; et al. (Bioresource Technology, 2025)

Bias correction of satellite precipitation estimates using Mumbai-MESONET observations: A Random Forest approach - Deepak Singh Bisht; D. Preveen Kumar; K. Amarjyothi; Upal Saha (Atmospheric Research, 2025)

QbD-Based Optimization of Fast Dissolving Sublingual Tablets of Valsartan - Ishan Dubey; Deepak Joshi; Amrut Walvekar; Pankaj Kumar Pandey; Pallavi Singh Chouhan (Journal of Pharmaceutical Innovation, 2025)

Artificial Intelligence: Preface, Applications and Future Perspective in Relation to Pharmaceutical Sector - Supriya Singh; Sanket Kumar; Sheikh Shahnawaz Quadir; Saloni Bhandari; Bhuvanesh Baniya; Garima Joshi; C. P. Jain; Deepak Choudhary (Journal of Pharmaceutical Innovation, 2025)

Experimental simulation of under sodium ultrasonic imaging in a sodium cooled fast breeder reactor using a scaled down model of the core - Deepak Patel; Anish Kumar (Annals of Nuclear Energy, 2025)

Characterization of multichannel SDD X-ray spectrometer with ASIC readout - Nishant Singh; M. Shanmugam; Arpit Patel; Sushil Kumar; Deepak K. Painkra; Tinkal Ladiya; S. Vadawale (Advances in Space Research, 2025)

Postharvest Physiology of Mango Crops: Understanding Ripening, Quality, and Storage Strategies - Kuldeep; Ashok Kumar Singh; Mandeep Rawat; Shivam; Gopal Mani; Rakhi Gautam; Rishabh Raj; Imamuddin Shah; Ankit Kumar Pandey; Deepak Maurya; Sampurna Nand Singh; Vinay Kumar (Applied Fruit Science, 2025)

Biogenic Amino Acid Cross-Linked Hyaluronic Acid Nanoparticles Containing Dexamethasone for the Treatment of Dry Eye Syndrome - Ajit Mishra; Jitu Halder; Ivy Saha; Vineet Kumar Rai; Ritu Mahanty; Deepak Pradhan; Priyanka Dash; Chandan Das; Tushar Kanti Rajwar; Bibhanwita Satpathy; Salim Manoharadas; Muralidhar Tata; et al. (AAPS PharmSciTech, 2025)

Switchable rasorber/absorber with T-A-T response for 5G applications - Neeharika Verma; Deepak Rathore; Laxmikant Dewangan; Shrey Anant Sandiman; Nipun Kumar Mishra (Next Research, 2025)

Enhanced interfacial evaporation with wind-driven rotating sailboat-style evaporators - Mohammadjavad Palimi; Tanay Kumar; Shane Stark; Kehinde Kassim; Hongyang Wu; Deepak Panchal; Hongying Zhao; Xuehua Zhang (Chemical Engineering Journal, 2025)

Removal of Crystal Violet, Methyl Orange, Methylene Blue and Rhodamine B by Nanocomposite Containing Endophytic-Mediated AgNP - Vivek Singh; Kavita Rani; Amrinder Singh; Deepak Kumar Malik (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2025)

Drought induced alterations in the physiological traits of novel citrus hybrids - Anagha Pilathottathil Kuzhiyil; Radha Mohan Sharma; Anil Kumar Dubey; Amit Kumar Goswami; Sudhir Kumar; Shailendra Jha; Amrender Kumar; Deepak Yadav; Mude Ramya Sree (Plant Physiology Reports, 2025)

Synthesis, In-Silico Molecular Docking Studies, and In-Vitro Antimicrobial Evaluation of Isatin Scaffolds bearing 1, 2, 3-Triazoles using Click Chemistry - Ritesh Anand; Nisha Yadav; Deeksha Mudgal; Simran Jindal; Sunak Sengupta; Deepak Kumar; Jay Singh; Nagendra Kumar Panday; Vivek Mishra (Indian Journal of Microbiology, 2025)

Advancements and Challenges in Roof-Top Harvested Rainwater Filtration: A Review - Sakshi Gupta; Prabhash Kumar Mishra; Deepak Khare (Environmental Processes, 2025)

Widespread monsoon extreme rainfall events over central Indian region: influence of dynamics and thermodynamics - Deepak Pandidurai; Raju Attada; Rohit Chakraborty; Amita Kumari; Prashant Kumar (Climate Dynamics, 2025)

Discerning double coseismic travelling ionospheric disturbances following the April 2024 Hualien earthquake, from GNSS TEC - Sayak Ray; Bhaskar Kundu; Sambit Sahoo; Deepak Kumar Tiwari (Advances in Space Research, 2025)

Framework for site specific leachate limits in MSW dumpsites: Integration of high-resolution site characterization and contaminant transport modeling - Pranjal Singh; Deepak Kumar Haritwal; G.V. Ramana; Manoj Datta (Chemosphere, 2025)

Microplastics influencing aquatic environment and human health: A review of source, determination, distribution, removal, degradation, management strategy and future perspective - Pawan Kumar; Anil Kumar; Deepak Kumar; Kalp Bhusan Prajapati; Ambrish Kumar Mahajan; Deepak Pant; Anoop Yadav; Anand Giri; Satish Manda; Soniya Bhandari; Richa Panjla (Journal of Environmental Management, 2025)

How grasses stabilize soil organic carbon in aggregates of semi-arid ecologically restored land: Evidence from 13C natural abundance - Vikas Kumar Singhal; Avijit Ghosh; Amit K. Singh; Yogeshwar Singh; Siddhartha Sankar Biswas; Deepak Ojha; Ranjan Bhattacharyya (CATENA, 2025)

Comprehensive in-silico characterization and expression pattern of calmodulin genes under various abiotic and biotic stresses in Indian mustard (Brassica juncea) - Prashasti Pandey; Garima Rai; Anchal Garg; Deepak Kumar (Physiology and Molecular Biology of Plants, 2025)

Application of Casein Micelles for Targeting Huntington’s Disease in Experimental Zebrafish Model - Deepak Nagdiya; Sanchit Arora; Vishal Kumar; Dinesh Kumar; Arti Singh; Charan Singh (Molecular Neurobiology, 2025)

SARS-CoV-2: A synergy to the Alzheimer’s disease - Khaja Moinuddin Shaik; Deepak Kumar; Pirangi Srikanth; Sukhendu Nandi (Journal of NeuroVirology, 2025)

A sustainable solution: mitigating aquatic herbicide contamination through natural product interventions - Madhumitha Vijayanand; Praveen Kumar Issac; Manikandan Velayutham; Paramasivam Deepak; Nathiya Thiyagarajulu; Mir Waqas Alam; Ajay Guru (Aquaculture International, 2025)

Pleural Fluid Calprotectin Levels in Benign and Malignant Pleural Effusions and Its Significance in Predicting Success of Pleurodesis in Malignant Pleural Effusions - Amartya Chakraborti; Nishant Kumar Chauhan; Naveen Dutt; Mithu Banerjee; Ravisekhar Gadepalli; Deepak Vedant; M. K. Garg; Gopal Durgeshwar; Hariharan Iyer (Indian Journal of Clinical Biochemistry, 2025)

Emerging drifts big data analytics and environment sustainability (EBAES) - Ashok Kumar Singh; Rupesh Kumar; Deepak Bangwal (Environmental Science and Pollution Research, 2025)

Eugenol attenuates aluminium-induced neurotoxicity in rats by inhibiting the activation of STAT3 and NF-кB - Chandra Prakash; Jyoti Tyagi; Kumari Vandana Singh; Gautam Kumar; Deepak Sharma (Metabolic Brain Disease, 2025)

Cover crop and herbicides can control purple nutsedge (Cyperus rotundus L.) and increase crop yields in conservation agriculture-based crop rotations - C.P. Nath; Narendra Kumar; Asik Dutta; K.K. Hazra; C.S. Praharaj; Deepak Kumar; G.P. Dixit (Crop Protection, 2025)

Potential health, environmental implication of microplastics: A review on its detection - Bhawana Yadav; Payal Gupta; Vinay Kumar; Mridul Umesh; Deepak Sharma; Jithin Thomas; Suraj Kumar Bhagat (Journal of Contaminant Hydrology, 2025)

Amine functionalized TiO2-based eco-friendly thin-film nanocomposite membranes for efficient pharmaceutical micropollutant removal - Diksha Yadav; Shreya Sen Sarma; Deepak Kumar; Pravin G. Ingole (Chemical Engineering Journal, 2025)

Enhancing salicylic acid levels by its exogenous pretreatment to mitigate Fusarium oxysporum-induced biotic stress in Vigna mungo: defense pathways insights - Lucky Duhan; Deepak Kumar; Ritu Pasrija (Plant Cell Reports, 2025)

Synthesis of tetrahydro-β-carboline analogs with N11 modifications and study of their antimalarial activities - Deepak Kumar; Cherish Prashar; Vandana Vandana; Kailash C. Pandey; Dipti Vaya; Tejpal Singh Chundawat (Medicinal Chemistry Research, 2025)

Geostatistical Kriging Interpolation for Spatial Enhancement of MODIS Land Surface Temperature Imagery - Kul Vaibhav Sharma; Vijendra Kumar; Deepak Kumar Prajapat; Aneesh Mathew; Lilesh Gautam (Journal of the Indian Society of Remote Sensing, 2025)

Biochemical conversion of municipal solid waste to biofuels and bioproducts: a review - Meenu Hans; Deepika Umrao; Mozhiarasi Velusamy; Deepak Kumar; Sachin Kumar (Environmental Science and Pollution Research, 2024)

Bibliometric analysis of invasive fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) - Ipsita Samal; Tanmaya Kumar Bhoi; Deepak Kumar Mahanta; Jaladanki Komal (Biologia, 2024)

Phytophagous probiotic foods: Exploring the intersection of characteristics, quality implications, health benefits, and market dynamics - Alaa Kareem Niamah; Shayma Thyab Gddoa Al-Sahlany; Hussein Katai Abdul-Sada; Pawan Prabhakar; Soubhagya Tripathy; Basant Kumar Dadrwal; Smita Singh; Deepak Kumar Verma; Alok Kumar Gupta; Rakesh Mohan Shukla; Mamta Thakur; Ami R. Patel; et al. (Trends in Food Science & Technology, 2024)

Molecular and serological screening of coxiellosis in bovines with reproductive disorders in dairy farms - Neha Parmar; Satyaveer Singh Malik; Manesh Kumar; Jay Prakash Yadav; V.K. Vinod; M.S. Sivaprasad; Brijesh Kumar; Jess Vergis; E.S. Sanjumon; Sukhadeo Baliram Barbuddhe; Deepak Bhiwa Rawool (The Veterinary Journal, 2024)

Evaluation of the anti-arthritic properties of Litsea glutinosa (L.) C.B. Rob Bark: An integrated analysis utilizing in-silico, in-vitro, and in-vivo approaches, along with identification of major compounds - Priyanka Dash; Biswakanth Kar; Goutam Ghosh; Vineet Kumar Rai; Chandan Das; Deepak Pradhan; Tushar Kanti Rajwar; Jitu Halder; Debasmita Dubey; Salim Manoharadas; Prachi Rani Sahu; Goutam Rath (South African Journal of Botany, 2024)

Aromatic crops cultivation a promising option in Indian agricultural system to support circular economy: A sustainable approach - Suman Singh; Poornendra Mishra; Shivam Singh Chauhan; R.K. Lal; Prasant Kumar Rout; Ashween Deepak Nannaware (Sustainable Chemistry and Pharmacy, 2024)

Five years of conservation tillage and weed management in a rice-chickpea rotation of northern Gangetic Plains of India: Weed growth, yield benefits and economic profitability - C.P. Nath; Narendra Kumar; K.K. Hazra; Asik Dutta; C.S. Praharaj; Raghavendra Singh; S.S. Singh; R.P. Dubey; Suman Sen; G.P. Dixit; Deepak Kumar (Soil and Tillage Research, 2024)

Advanced characterisation of groundwater contamination at a dumpsite: Methodology and assessment - Case study of a municipal solid waste dumpsite in India - Deepak Kumar Haritwal; Pranjal Singh; Gunturi Venkata Ramana; Manoj Datta (Science of The Total Environment, 2024)

MFC-mediated wastewater treatment technology and bioelectricity generation: Future perspectives with SDGs 7 & 13 - Richa Kothari; Atin Kumar Pathak; Har Mohan Singh; Kajol Goria; Zaheer Ud Din Sheikh; Anu Bharti; Shubham Raina; Rachna; Anita Singh; Bhaskar Singh; Veeramuthu Ashok Kumar; Ashok Pandey; et al. (Process Safety and Environmental Protection, 2024)

Antibiotic resistance in the Ganga River: Investigation of antibiotic resistant bacteria and antibiotic resistance genes, and public health risk assessment - Deepak Kumar Prasad; Rishabh Shukla; Shaikh Ziauddin Ahammad (Journal of Environmental Chemical Engineering, 2024)

Nutraceutical tablets: Manufacturing processes, quality assurance, and effects on human health - Muhammad Faisal Manzoor; Sakhawat Riaz; Deepak Kumar Verma; Muhammad Waseem; Gulden Goksen; Anwar Ali; Xin-An Zeng (Food Research International, 2024)

Soy protein-polyphenols conjugates interaction mechanism, characterization, techno-functional and biological properties: An updated review - Muhammad Faisal Manzoor; Xin-An Zeng; Muhammad Waseem; Rabia Siddique; Muhammad Rizwan Javed; Deepak Kumar Verma; Murtaza Ali (Food Chemistry, 2024)

Tasar Silkworm Pupae oil: A potential therapeutic and edible lipid source to mitigate the oxidative stress and cholesterol complications associated with diabetes - Devika Srivastava; Prashant Pandey; Deepak Kumar Tripathi; Jagat Pal Yadav; Bulbul Ali; Vandana Singh; Abhishek Verma; Akash Mishra; Dinesh Kumar; Abha Mishra; Paruvathanahalli Siddalingam Rajinikanth; Krishna Mohan Poluri; et al. (Food and Humanity, 2024)

Pharmaceuticals and personal care products and heavy metals in the Ganga River, India: Distribution, ecological and human health risk assessment - Deepak Kumar Prasad; Rishabh Shukla; Shaikh Ziauddin Ahammad (Environmental Research, 2024)

Multivalent cation substitution boosted sodium-ion storage in NASICON-type iron-phospho-sulphate cathodes - Sharad Dnyanu Pinjari; Ravi Chandra Dutta; Saikumar Parshanaboina; Purandas Mudavath; Subhajit Singha; Deepak Dubal; Xijue Wang; John Bell; Ashok Kumar Nanjundan; Rohit Ranganathan Gaddam (Chemical Engineering Journal, 2024)

Improved fermentation strategies for enhancing polyhydroxybutyrate production from paper mill fiber rejects - Linjing Jia; Gundeep Kaur; Ankita Juneja; Erica L.-W. Majumder; Bandaru V. Ramarao; Deepak Kumar (Bioresource Technology Reports, 2024)

Simulating and predicting surface water quality for drinking and bathing purposes through combined approach of PCA, entropy-based WQI, and stochastic models - Supriya Chaudhary; Abinayarajam Duraiyarasan; Deepak Gupta; Virendra Kumar Mishra (Stochastic Environmental Research and Risk Assessment, 2024)

TLR-4: a promising target for chemotherapy-induced peripheral neuropathy - Nagendra Babu; Anagha Gadepalli; Akhilesh; Dilip Sharma; Anurag Kumar Singh; Deepak Chouhan; Somesh Agrawal; Vinod Tiwari (Molecular Biology Reports, 2024)

Milk exosomal microRNA profiling identified miR-375 and miR-199-5p for regulation of immune response during subclinical mastitis of crossbred cattle - Sudarshan Mahala; Amit Kumar; Hari Om Pandey; Shikha Saxena; Shivani Khanna; Manoj Kumar; Deepak Kumar; Ujjwal Kumar De; Ashwni Kumar Pandey; Triveni Dutt (Molecular Biology Reports, 2024)

Genome-wide association study identified QTLs and genes underlying early seedling vigour in aus rice (Oryza sativa L.) - Firos T. M. Basha; Puranjoy Sar; Prolay K. Bhowmick; Anima Mahato; Deepak S. Bisht; Mir A. Iquebal; Koushik Chakraborty; Amrita Banerjee; Bibhash C. Verma; Debarati Bhaduri; Jitendra Kumar; Umakanta Ngangkham; et al. (Molecular Genetics and Genomics, 2024)

In-silico identification and exploration of small molecule coumarin-1,2,3-triazole hybrids as potential EGFR inhibitors for targeting lung cancer - Sunil Kumar; Iqra Ali; Faheem Abbas; Faiza Shafiq; Ashok Kumar Yadav; Manjunath D. Ghate; Deepak Kumar (Molecular Diversity, 2024)

Advances in the understanding of heat shock proteins and their functions in reducing abiotic stress in plants - Ria Mukhopadhyay; Priyanka Boro; Kapudeep Karmakar; Prajjwal Pradhan; Riman Saha Chowdhury; Bimal Das; Rupsanatan Mandal; Deepak Kumar (Journal of Plant Biochemistry and Biotechnology, 2024)

Gastroprotective Efficacy of Prebiotic-based Oral Formulation of Amoxicillin - Shashi Supriya; Vineet Kumar Rai; Deepak Pradhan; Jitu Halder; Tushar Kanti Rajwar; Ritu Mahanty; Ivy Saha; Priyanka Dash; Chandan Dash; Saroj Kumar Rout; Jameel Al-Tamimi; Hossan Ebaid; et al. (Journal of Pharmaceutical Innovation, 2024)

Convective structures of salt fingers at a neutrally buoyant density interface - Deepak Kumar Singh; O. P. Singh; K. M. Nihaal; U. S. Mahabaleshwar (Environmental Fluid Mechanics, 2024)

Identification of terminal heat-tolerant and foliar disease-resistant fortified genotypes in wheat (Triticum aestivum L.) - Rounak Kumar; Chandra Shekhar Azad; Tirthartha Chattopadhyay; Pradeep Kumar Bhati; Om Prakash Gangwar; Subodh Kumar; Pramod Prasad; Deepak Baranwal (Cereal Research Communications, 2024)

Climate Impact Prediction: Whale-Optimized Conv-XGBoost with Remote Sensing and Sociological Data - R. Jayakarthik; Chandrashekhara K.T; O. Sampath; Deepak Kumar; Laxmi Biban; Jnaneshwar Pai Maroor; S. N. Lakshmi Malluvalasa (Remote Sensing in Earth Systems Sciences, 2024)

An improved DNA extraction method in okra for rapid PCR detection of Okra enation leaf curl virus from diverse Indian regions - Ankit Kumar; Jyoti Singh; Deepak Panwar; Anupma Singh; Ravi Singh Thapa; Rakesh Kumar; Dharmendra Pratap (Archives of Microbiology, 2024)

Soft computing techniques for predicting vegetation dynamics in Delhi - Deepak Kumar Raj; T Gopikrishnan (Journal of Earth System Science, 2024)

Microplastic migration from landfill-mined soil through earth filling operations and ecological risk assessment: a case study in New Delhi, India - Deepak Kumar Haritwal; Pranjal Singh; Gunturi Venkata Ramana; Manoj Datta (Environmental Science and Pollution Research, 2024)

Evidence in Reaching Consensus in Usage of Mandibular Advancement Device for Pre- and Post-obstructive Sleep Apnea Treatment with Blood and Salivary Inflammatory Biomarkers Profiles - Thakur Prasad Chaturvedi; Pooja Priyadarshani; Vipul Kumar Sharma; Ishita Shrivastava; Deepak Singh; Surendra Pratap Mishra; Navneet Kumar Dubey (Sleep and Vigilance, 2024)

Biotic factors as key determinants for ovarian and oothecal developmental plasticity of a tortoise beetle - Ruchita Shivprakash Tiwari; Lankesh Yashwant Bhaisare; Shivani Pathak; Bhupendra Kumar; Desh Deepak Chaudhary (Zoology, 2024)

Electrical conductivity profiling for rapid contamination assessment in unsaturated zones: A case study of an MSW landfill - Pranjal Singh; Deepak Kumar Haritwal; Sanchay Seth; G.V. Ramana; Manoj Datta (Science of The Total Environment, 2024)

Toxicological impacts of plastic microfibers from face masks on Artemia salina: An environmental assessment using Box-Behnken design - Devlina Das Pramanik; Armeena Sharma; Deepak Kumar Das; Arindam Pramanik; Paul Kay; Francisco M. Goycoolea (Marine Environmental Research, 2024)

Comparative Preclinical Pharmacokinetics and Disposition of Favipiravir Following Pulmonary and Oral Administration as Potential Adjunct Therapy Against Airborne RNA Viruses - Venkata Siva Reddy Devireddy; Hasham Shafi; Sonia Verma; Sanjay Singh; J. V. U. S. Chakradhar; Naresh Kothuri; Himanshu Bansode; Sunil Kumar Raman; Deepak Sharma; Lubna Azmi; Rahul Kumar Verma; Amit Misra (Pharmaceutical Research, 2024)

Identification of suitable sites for different artificial groundwater recharge structures for sustainable water resources management in Ken River Basin - Deepak Patle; Sourabh Nema; Manoj Kumar Awasthi; Shailesh Kumar Sharma (Environment, Development and Sustainability, 2024)

Long Non-Coding RNAs in Non-Alcoholic Fatty Liver Disease; Friends or Foes? - Sina Kalantari Soltanieh; Sahar Khastar; Irwanjot Kaur; Abhishek Kumar; Jaya Bansal; Ata Fateh; Deepak Nathiya; Beneen Husseen; Mansour Rajabivahid; Mahmoud Dehghani-Ghorbi; Reza Akhavan-Sigari (Cell Biochemistry and Biophysics, 2024)

Docetaxel-tethered di-Carboxylic Acid Derivatised Fullerenes: A Promising Drug Delivery Approach for Breast Cancer - Charu Misra; Jasleen Kaur; Manish Kumar; Lokesh Kaushik; Deepak Chitkara; Simran Preet; Muhammad Wahajuddin; Kaisar Raza (AAPS PharmSciTech, 2024)

Unveiling pollutants in Sonipat district, Haryana: Exploring seasonal, spatial and meteorological patterns - Diksha; Maya Kumari; Varun Narayan Mishra; Deepak Kumar; Pradeep Kumar; Hazem Ghassan Abdo (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Underwater visual surveillance: A comprehensive survey - Deepak Kumar Rout; Meghna Kapoor; Badri Narayan Subudhi; Veerakumar Thangaraj; Vinit Jakhetiya; Ankur Bansal (Ocean Engineering, 2024)

Improved ammonia gas adsorption of surface engineered WS2 nanoflakes - Sandip De; Manoj K. Rajbhar; Ashima Rawat; Deepak Kumar Sahoo; Durga Madhab Pani; Ravindra Pandey; Shyamal Chatterjee (Journal of Environmental Chemical Engineering, 2024)

Lab-on-a-chip device for food quality control and safety - Syed Mansha Rafiq; Reshab Majumder; Deepak Joshi; Aamir Hussain Dar; Kshirod Kumar Dash; Vinay Kumar Pandey; Urba Shafi Sidiqi (Food Control, 2024)

Antiparkinson potential of khellin on rotenone-induced Parkinson's disease in a zebrafish model: targeting MAO, inflammatory, and oxidative stress markers with molecular docking, MD simulations, and histopathology evidence - A. Hemanth Babu; D.S.N.B.K. Prasanth; Deepak A. Yaraguppi; Siva Prasad Panda; Sheikh F. Ahmad; Haneen A. Al-Mazroua; Akula Ruchitha Sai; P. Praveen Kumar (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Multi-location evaluation of field pea in Indian climates: eco-phenological dynamics, crop-environment relationships, and identification of mega-environments - Ashok K. Parihar; Kali Krishna Hazra; Amrit Lamichaney; Debjyoti Sen Gupta; Jitendra Kumar; R. K. Mishra; Anil K. Singh; Anuradha Bhartiya; Parvaze Ahmad Sofi; Ajaz A. Lone; Sankar P. Das; Rajesh Kumar Yadav; et al. (International Journal of Biometeorology, 2024)

Effects of air pollution on global health: evidence from the global burden of disease study in the BRICS countries - Deepak Kumar Behera; Pozhamkandath Karthiayani Viswanathan; Sanghamitra Mishra (International Archives of Occupational and Environmental Health, 2024)
Purpose Considering the dynamic influence of environmental, social, economic, and political factors in the emergence and growth of the BRICS countries (Brazil, Russia, India, China, and South Africa) over the years and pre-existing differences, the adverse effects of air pollution on the health and well-being of the people have remained major areas of academic inquiry and policy interventions. The present study examines the global trend of deaths and Disability Adjusted Life Years (DALYs) attributable to air pollution with particular reference to the BRICS countries for the period 1990 to 2019. Methods This study has used the global burden of disease estimates by using different rounds of the Global Burden of Disease (GBD) study report published by the Institute of Health Metrics Evaluation. This study has calculated the cause of death and DALYs due to environmental risk factors (i.e. Air pollution). Data analysis has been done by using the standard formula for the calculation of death (mortality) rate and DALYs rate. Similarly, we calculated the age and gender-wise death and DALYs rate by using the appropriate numerator and denominator. Results The study discovered a significant shift in disease patterns over this period, as communicable diseases like respiratory infections and tuberculosis were replaced by non-communicable diseases such as ischemic heart disease (17.2 million), chronic obstructive pulmonary disease (14.59 million), and stroke (17.02 million) as the primary causes of air pollution-related deaths in 2019 at the global level. Additionally, the study identified a worrying increase in deaths linked to neonatal disorders and respiratory infections caused by ambient particulate matter pollution in South Africa, India, and Brazil. The impact of air pollution on public health is evident across different age groups and genders, with people aged 50-69 years, those aged 70 and above, and children under 5 years being more vulnerable. Furthermore, the male population is disproportionately affected by communicable and noncommunicable diseases caused by air pollution. Conclusion The study highlights the need for policymakers to implement evidence-based interventions to tackle this global health problem. The interventions should aim to reduce the emerging crisis of non-communicable diseases related to air pollution, particularly among vulnerable age groups and the male population, ultimately improving public health outcomes.

Qualitative and quantitative genetic variations in bitter gourd (Momordica charantia L.) - K. N. Mallikarjuna; Bhoopal Singh Tomar; Manisha Mangal; Naveen Singh; Deepak Singh; Sachin Kumar; Avinash Tomer; Tusar Kanti Behera; Gograj Singh Jat (Genetic Resources and Crop Evolution, 2024)

Immunosensors in food, health, environment, and agriculture: a review - Harsh Kumar; Rajni Dhalaria; Shivani Guleria; Richard Cimler; Prerna Prerna; Daljeet Singh Dhanjal; Chirag Chopra; Nidhi Sethi; Ashok Kumar Pathera; Deepak Kala; Neetika Kimta; Talwinder Kaur; et al. (Environmental Chemistry Letters, 2024)

Phenotypic, Physiological and Biochemical Delineation of Wheat Genotypes Under Different Stress Conditions - Suman Devi; Vikram Singh; Shikha Yashveer; Anil Kumar Poonia; Paras; Rukoo Chawla; Deepak Kumar; Darya Khan Akbarzai (Biochemical Genetics, 2024)

Detection of facultative apomixis in little millet, Panicum sumatrense - Sujata Rathi; Renu Rani; Anand Kumar Srivastava; Deepak Kumar (Vegetos, 2024)

Impact assessment of precipitation and temperature trends on crop yield in water stress zone of Bundelkhand, India - Rahul Dwivedi; Vivek Kumar; Deepak Khare (Journal of Earth System Science, 2024)

Discovery, lead identification and exploration of potential oxadiazole derivatives in targeting STAT3 as anti-cancer agents - Vivek Panwar; Sounok SenGupta; Saroj Kumar; Praveen P. Singh; Arun Kumar; Shavkatjon Azizov; Manoj K. Gupta; Deepak Kumar (In Silico Pharmacology, 2024)

Solar water splitting for hydrogen production using Zn electrodes: a green and sustainable approach - Dhananjay Singh; Indresh Singh; Raj Kumar Arya; Vinay Mishra; Deepak Singh; Siraj Alam; Balendu Shekher Giri (Environmental Science and Pollution Research, 2024)

Dynamics and source characterization of chromophoric dissolved organic matter (CDOM) in a tropical monsoon driven lagoon - Sambit Singh; Susmita Raulo; Tamoghna Acharyya; Deepak R. Mishra; Abhishek Kumar; Anu Gopinath; Pradipta R. Muduli; Gurdeep Rastogi (Marine Chemistry, 2024)

Evidence of back-folding in the Beas Valley puts Himalayan tectonic models on trial - Arun Kumar Ojha; Deepak Srivastava; Marnie Forster; Gordon Lister (Journal of Structural Geology, 2024)

On-farm evidence on breaking yield barriers through optimizing wheat cropping system in Indo Gangetic Plain - Radheshyam; Shankar Lal Jat; M.L. Jat; C.M. Parihar; H.S. Jat; A.K. Singh; Deepak Bijarniya; Smruti Ranjan Padhan; Praveen V. Kadam; Manish Kumar (European Journal of Agronomy, 2024)

Synergistic effect of cellulo-xylanolytic and laccase enzyme consortia for improved deinking of waste papers - Guddu Kumar Gupta; Rajeev Kumar Kapoor; Deepak Chhabra; Nishi Kant Bhardwaj; Pratyoosh Shukla (Bioresource Technology, 2024)

Characterization and utilization of algal and wheat husk biochar as biofertilizers for sustainable soil amelioration - Sharma Mona; Neha Saini; Sujata; Sumit Kumar; Anuj Sharma; Anjali Yadav; Navita Yadav; Bansal Deepak (Bioresource Technology Reports, 2024)

Evaluation of the immune responses in buffaloes vaccinated with a live-attenuated lumpy skin disease vaccine (Lumpi-ProVacInd) - Shweta Dhanda; Deepak Kumar Sharma; Himanshu Kamboj; Garvit Kumar; Priyasi Mittal; Ram Kumar; Assim Verma; Karishma Rathore; Mitesh Gaur; Sanjay Barua; Bhupendra Nath Tripathi; Shalini Sharma; et al. (Tropical Animal Health and Production, 2024)

Alginate-mediated immobilization of jackfruit (Artocarpus heterophyllus) latex serine protease enzyme exhibits improved catalytic properties - Suman Natta; Swathi Chintala; Deepak Kumar; Nandita Sahana; Somnath Mandal (Journal of Plant Biochemistry and Biotechnology, 2024)

Analyzing the effects of critical active waveguide parameters on acoustic emission characteristics for soil slope deformation monitoring - Deepak Kumar; Ajit K. Mahapatro; Sushil Kumar Singh (Bulletin of Engineering Geology and the Environment, 2024)

Physicochemical Stimuli-Mediated Precipitation Approach for the Modulation of Rifampicin’s Dissolution and Oral Bioavailability - Vineet Kumar Rai; Deepak Pradhan; Jitu Halder; Tushar Kanti Rajwar; Ritu Mahanty; Ivy Saha; Priyanka Dash; Chandan Dash; Saroj Kumar Rout; Jameel Al-Tamimi; Hossan Ebaid; Salim Manoharadas; et al. (AAPS PharmSciTech, 2024)

Cropping System Intensification: Implications on Food Security and Environmental Sustainability in India - Devideen Yadav; Subhash Babu; Dinesh Kumar Yadav; Anita Kumawat; Deepak Singh; Ajay Kumar Yadav; Sanjay Singh Rathore; Raghavendra Singh; Neeshu Joshi; Rajendra Kumar Yadav; Anup Das (Anthropocene Science, 2024)

Evaluating the influence of calcined eggshells and ultrasonication in the Co-digestion of avoidable and unavoidable Food Waste and OLS regression analysis of the reactor system - Taniya Kumari Shaw; Deepak Kumar Rajendran; Smita Raghuvanshi; Sunil Prasad Lohani (Journal of Cleaner Production, 2024)

Molecularly imprinted Ag2S quantum dots with high photocatalytic activity for dye removal: Experimental and DFT insights - Azad Quyoom Malik; Tabinda Jabeen; Prasad Eknath Lokhande; Deepak Kumar; Shikha Awasthi; Sarvesh Kumar Pandey; Nabisab Mujawar Mubarak; Faisal Abnisa (Journal of Environmental Management, 2024)

Environmental drivers behind the exceptional increase in cyanobacterial blooms in Okavango Delta, Botswana - Jan Veerman; Deepak R. Mishra; Abhishek Kumar; Malvern Karidozo (Harmful Algae, 2024)

Comparative transcriptome profile of embryos at different developmental stages derived from somatic cell nuclear transfer (SCNT) and in-vitro fertilization (IVF) in riverine buffalo (Bubalus bubalis) - Deepak Kumar; Manish Tiwari; Pallavi Goel; Manoj Kumar Singh; Naresh Lala Selokar; Prabhat Palta (Veterinary Research Communications, 2024)

GWAS elucidated grain yield genetics in Indian spring wheat under diverse water conditions - Arpit Gaur; Yogesh Jindal; Vikram Singh; Ratan Tiwari; Philomin Juliana; Deepak Kaushik; K. J. Yashavantha Kumar; Om Parkash Ahlawat; Gyanendra Singh; Sonia Sheoran (Theoretical and Applied Genetics, 2024)

Assessment of heavy metal pollution level, ecological and human health risks in surface water of Narmada River, India - Deepak Gupta; Reetika Shukla; Pankaj Kumar Srivastava; Virendra Kumar Mishra (Sustainable Water Resources Management, 2024)

Comparison of Relative Activity versus Relative Expression Factors (RAF versus REF) in Predicting Glucuronidation Mediated Drug Clearance Using Recombinant UGTs - Sandhya Subash; Deepak Ahire; Mitesh Patel; Sahil Shaikh; Dilip Kumar Singh; Sujal Deshmukh; Bhagwat Prasad (Pharmaceutical Research, 2024)

Revisiting the ethnomedicinal, ethnopharmacological, phytoconstituents and phytoremediation of the plant Solanum viarum Dunal - Mehak Thakur; Rachna Verma; Dinesh Kumar; Priyanku Pradip Das; Rajni Dhalaria; Ajay Kumar; Kamil Kuca; Shavkatjon Azizov; Deepak Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Automation of takeoff data for aviation services using self-supervised LSTM approaches with time-series prediction - Anand Shankar; Pradhan Parth Sarthi; Deepak Kumar Singh; Mantosh Kumar; Pankaj Kumar (Modeling Earth Systems and Environment, 2024)

A Review on Evaluation of Microstructural Parameters to Estimate the Strength of Virtually Isotropic Rock Materials - Deepak Amban Mishra; Bikash Kumar Ram (Geotechnical and Geological Engineering, 2024)

Winter convective mixing regulates oceanic C : N : P ratios - Deepika Sahoo; Himanshu Saxena; Sipai Nazirahmed; Mohammad Atif Khan; Deepak Kumar Rai; Niharika Sharma; Sebin John; Sanjeev Kumar; A. K. Sudheer; Ravi Bhushan; Arvind Singh (Limnology and Oceanography, 2024)
Recent studies have challenged the validity of the Redfield ratio. It is proposed that physical and biogeochemical processes govern the geographical variations in carbon : nitrogen : phosphorus (C : N : P) ratios. However, this proposal remains to be examined through concurrent observations of C : N : P ratios with physical and biogeochemical processes in various marine reservoirs. Here, we sampled the Arabian Sea for its C, N, and P content in organic and inorganic pools during the winter monsoon. We analyzed the role of convective mixing, eddies, and N 2 fixation to explain the variation in observed elemental ratios. Convective mixing injected the cold water and enhanced the supply of N and P nutrients in the top layer (surface to 50–75 m) of the northern Arabian Sea. This led to a decrease in the N : P and C : P ratios in the particulate organic matter in the northern region, but C : N : P increased equatorward, averaging 245 : 32 : 1 in the top layer of the Arabian Sea. The variation in the elemental ratios in the top layer is best explained by the changes in water temperature. N 2 fixation contributed negligibly to the N : P ratio of the export flux. The substantial decrease in N : P ratios of nutrients in the subsurface waters is most likely caused by the denitrifying conditions in the Arabian Sea. As the processes of convective mixing and eddies are are prevalent oceanic processes, our observations underpin that the interplay of these processes leads to changes in the elemental ratios globally.

Unboxing PGPR-mediated management of abiotic stress and environmental cleanup: what lies inside? - Deepak Kumar; Mohd. Ali; Nandni Sharma; Roohi Sharma; Rajesh Kumari Manhas; Puja Ohri (Environmental Science and Pollution Research, 2024)

Proteomic analysis of lung responses to SARS-CoV-2 infection in aged non-human primates: clinical and research relevance - Andreu Garcia-Vilanova; Anna Allué-Guardia; Nadine M. Chacon; Anwari Akhter; Dhiraj Kumar Singh; Deepak Kaushal; Blanca I. Restrepo; Larry S. Schlesinger; Joanne Turner; Susan T. Weintraub; Jordi B. Torrelles (GeroScience, 2024)

Two new cycloartane type triterpenes from Dysoxyllum binectariferum - Chetan Paul Singh; Akshima Sharma; Kajal Sharma; Priya Darshani; Anil Katare; Deepak Kumar; Yogesh P. Bharitkar (Natural Product Research, 2024)

Melatonin mediated abiotic stress mitigation in plants: A comprehensive study from biochemical to omics cascades - Ipsita Samal; Tanmaya Kumar Bhoi; Deepak Kumar Mahanta; J. Komal; Prasanta Kumar Majhi; Sneha Murmu; Asit Kumar Pradhan; Himanshushekhar Chaurasia (South African Journal of Botany, 2024)

Enhanced supercapacitor performance through synergistic electrode design: Reduced graphene oxide-polythiophene (rGO-PTs) nanocomposite - Anita K. Tawade; Shivaji N. Tayade; Deepak P. Dubal; Sawanta S. Mali; Chang Kook Hong; Kiran Kumar K. Sharma (Chemical Engineering Journal, 2024)

Biosynthesis of biomolecules from saffron as an industrial crop and their regulation, with emphasis on the chemistry, extraction methods, identification techniques, and potential applications in human health and food: A critical comprehensive review - Vishal Gupta; Gayatri Jamwal; Gyanendra Kumar Rai; Sushil Kumar Gupta; Rakesh Mohan Shukla; Basant Kumar Dadrwal; Pawan Prabhakar; Soubhagya Tripathy; Sudhir K. Rajpoot; Amit Kumar Singh; Deepak Kumar Verma; Gemilang Lara Utama; et al. (Biocatalysis and Agricultural Biotechnology, 2024)

Novel remote sensing technologies for natural hazard management - Deepak Kumar; Achyut Shankar (Environmental Science and Pollution Research, 2024)

Image segmentation, classification, and recognition methods for wheat diseases: Two Decades’ systematic literature review - Deepak Kumar; Vinay Kukreja (Computers and Electronics in Agriculture, 2024)

Silica and polymer coated controlled release nitrogen-phosphorus fertilizer for improving nutrient and water use efficiency in semi-arid India - Avijit Ghosh; Amit K. Singh; R.V. Kumar; Prashant D. Singh; Sukanya Misra; Safik Ahamed; Deepak Ojha; Amaresh Chandra; Ranjan Bhattacharyya (Journal of Environmental Chemical Engineering, 2024)

Frontier in dark fermentative biohydrogen production from lignocellulosic biomass: Challenges and future prospects - Pushpa Rani; Deepak Kumar Yadav; Arti Yadav; Narsi Ram Bishnoi; Vivek Kumar; Chhotu Ram; Arivalagan Pugazhendhi; Smita S. Kumar (Fuel, 2024)

Ruthenium doping of NASICON electrolyte augments the performance of solid-state sodium-ion batteries - M. Dinachandra Singh; Deepak Kumar Gorai; Kumar Brajesh; Pragati Singh; Vishal Ranawade; Ajay Vijay Shinde; M. Jareer; Raju Gupta; Ashish Garg; Vishal Agarwal; Kanwar S. Nalwa (Chemical Engineering Journal, 2024)

Production of fatty acids from distilled aromatic waste biomass using oleaginous yeast - Suman Singh; Shivani Chaturvedi; Naziya Syed; Dheerendra Rastogi; Prashant Kumar; Praveen Kumar Sharma; Deepak Kumar; Debesmita Sahoo; Nitin Srivastava; Ashween Deepak Nannaware; Sunil Kumar Khare; Prasant Kumar Rout (Biomass and Bioenergy, 2024)

Seasonal rainfall pattern using coupled neural network-wavelet technique of southern Uttarakhand, India - Shekhar Singh; Deepak Kumar; Dinesh Kumar Vishwakarma; Rohitashw Kumar; Nand Lal Kushwaha (Theoretical and Applied Climatology, 2024)

Biochar supported Ag/Cu-ZrO2 nano-hetero assembly for enhanced adsorption of heavy metal ions and biomedical applications - Deepak Pathania; Ajay Kumar; Adesh K. Saini; Reena Saini; Divya Mittal; Arush Sharma (Nanotechnology for Environmental Engineering, 2024)

A Multivariate Geomorphometric Approach to Prioritize Drought Prone Sakri Basin for Land and Water Resource Management - Pawan Jeet; Anil Kumar Singh; Ashutosh Upadhyaya; Anup Das; Rakesh Kumar; Prem Kumar Sundaram; Arti Kumari; Kirti Saurabh; Deepak Singh; Prem Pal Kumar (Journal of the Indian Society of Remote Sensing, 2024)

Nonsterile Process for Biohydrogen Production: Recent Updates, Challenges, and Opportunities - Sanjay K. S. Patel; Rahul K. Gupta; Karthikeyan K. Karuppanan; Deepak Kumar Padhi; Sampathkumar Ranganathan; Parasuraman Paramanantham; Jung-Kul Lee (Indian Journal of Microbiology, 2024)

Management of rice blast disease caused by Pyricularia oryzae through application of biocontrol agents and fungicides alone and in possible combinations - Devanshi Pandit; A. K. Singh; V. K. Razdan; S. K. Singh; V. B. Singh; Deepak Kumar (Indian Phytopathology, 2024)

Rapid and visual detection of Shiga-toxigenic Escherichia coli (STEC) in carabeef meat harnessing loop-mediated isothermal amplification (LAMP) - Govindarajan Bhuvana Priya; Ravi Kant Agrawal; Arockiasamy Arun Prince Milton; Madhu Mishra; Sanjod Kumar Mendiratta; Bhoj Raj Singh; Deepak Kumar; Ravi Kumar Gandham; Zunjar Baburao Dubal; Swaraj Rajkhowa; Ashish Luke; Girish Patil (Brazilian Journal of Microbiology, 2024)

Production and testing of mahua oil–based biodiesel synthesized through heterogeneous catalyst using experimental and numerical method - Lawalesh Kumar Prajapati; Chandrabhushan Tiwari; Tikendra Nath Verma; Gaurav Dwivedi; Deepak Paliwal (Environmental Science and Pollution Research, 2024)

Exploring the Biofilm Inhibition Potential of a Novel Phytic Acid-Crosslinked Chitosan Nanoparticle: In Vitro and In Vivo Investigations - Reena Nayak; Vineet Kumar Rai; Deepak Pradhan; Jitu Halder; Tushar Kanti Rajwar; Priyanka Dash; Chandan Das; Ajit Mishra; Ritu Mahanty; Ivy Saha; Salim Manoharadas; Biswakanth Kar; et al. (AAPS PharmSciTech, 2024)

Computational study of the performance of a solar dryer for improvement in the shelf life of the food materials - Mukul Sengar; Dhananjay Singh; Pradeep Kumar Mishra; Deepak Singh; Balendu Shekher Giri (Environmental Science and Pollution Research, 2024)

The role of green finance and governance effectiveness in the impact of renewable energy investment on CO2 emissions in BRICS economies - Ashutosh Yadav; Bright Akwasi Gyamfi; Simplice A. Asongu; Deepak Kumar Behera (Journal of Environmental Management, 2024)

Innovative strategies to manage polluted aquatic ecosystem and agri-food waste for circular economy - Rashmi Trivedi; Tarun Kumar Upadhyay; Fahad Khan; Pratibha Pandey; Radhey Shyam Kaushal; Madan Sonkar; Deepak Kumar; Mohd Saeed; Mayeen Uddin Khandaker; Talha Bin Emran; Md. Abu Bakar Siddique (Environmental Nanotechnology, Monitoring & Management, 2024)

Book review - Monalisa Gochhi; Biswakanth Kar; Deepak Pradhan; Jitu Halder; Priyanka Dash; Chandan Das; Vineet Kumar Rai; Goutam Ghosh; Goutam Rath (Bioactive Carbohydrates and Dietary Fibre, 2024)

In silico approach for the identification of tRNA-derived small non-coding RNAs in SARS-CoV infection - Swati Ajmeriya; Deepak Ramkumar Bharti; Amit Kumar; Shweta Rana; Harpreet Singh; Subhradip Karmakar (Journal of Applied Genetics, 2024)

Exploring the influence of invasive weed biochar on the sorption and dissipation dynamics of imazethapyr in sandy loam soil - Mamta Kaswa; Anup Kumar; Mahendra Prasad; Deepak Upadhyay; Sonu Kumar Mahawer; Vinod Kumar Washnik; Pooja Tamboli (Environmental Monitoring and Assessment, 2024)

Novel Drug Delivery Approaches for the Localized Treatment of Cervical Cancer - Ivy Saha; Jitu Halder; Tushar Kanti Rajwar; Ritu Mahanty; Deepak Pradhan; Priyanka Dash; Chandan Das; Vineet Kumar Rai; Biswakanth Kar; Goutam Ghosh; Goutam Rath (AAPS PharmSciTech, 2024)

Multi-parametrical analysis of Haptal glacier, lower Chenab basin, Jammu and Kashmir, India: A remote sensing approach - Shashi Kant Rai; Sunil Dhar; Gagandeep Kour; Rakesh Sahu; Arun Kumar; Deepak Pathania; Pankaj Mehta; Dinesh Kumar (Journal of Earth System Science, 2024)

Exploration of upgrading of biomass and its paradigmatic synthesis: Future scope for biogas exertion - Mukesh Kumar Awasthi; Karthik Rajendran; V.S. Vigneswaran; Vinay Kumar; Andrei Mikhailovich Dregulo; Vijai Singh; Deepak Kumar; Raveendran Sindhu; Zengqiang Zhang (Sustainable Chemistry and Pharmacy, 2024)

Air-lift pump systems for vertical solid particle transport: A comprehensive review and deep sea mining potential - Deepak Kumar; K. Amudha; K. Gopakumar; G.A. Ramadass (Ocean Engineering, 2024)

Electronic waste disposal behavioral intention of millennials: A moderating role of electronic word of mouth (eWOM) and perceived usage of online collection portal - Manu Sharma; Deepak Kaushal; Sudhanshu Joshi; Anil Kumar; Sunil Luthra (Journal of Cleaner Production, 2024)

Fabrication of dual S-scheme based CuWO4/NiFe/WO3 heterojunction for visible-light-induced degradation and reduction applications - Rohit Sharma; Nasarul Islam; Aashish Priye; Deepak Kumar; Jay Singh; Manish Kumar; Prem P. Sharma; Vinay Chauhan; Pooja Shandilya (Journal of Environmental Chemical Engineering, 2024)

Development and Evaluation of Novel Amoxicillin and Phytic Acid-Loaded Gastro-Retentive Mucoadhesive Pectin Microparticles for the Management of Helicobacter pylori Infections - Ajit Mishra; Debalina Maity; Deepak Pradhan; Jitu Halder; Tushar Kanti Rajwar; Vineet Kumar Rai; Manoj Kumar Sarangi; Salim Manoharadas; Manish Ramchandani; Amit Goyal; Biswakanth Kar; Goutam Ghosh; et al. (Journal of Pharmaceutical Innovation, 2024)

Unlocking the Secrets of Rhizosphere Microbes: A New Dimension for Agriculture - Mony Thakur; Khushboo; Sujit Shah; Priyanka Kumari; Mohit Kumar; Raj Kamal Vibhuti; Avijit Pramanik; Vinod Yadav; Meenakshi Raina; Neelam Prabha Negi; Vibhav Gautam; Anjana Rustagi; et al. (Symbiosis, 2024)

Multipath phase based vegetation correction scheme for improved field-scale soil moisture retrieval over agricultural cropland using GNSS-IR technique - Sushant Shekhar; Rishi Prakash; Dharmendra Kumar Pandey; Anurag Vidyarthi; Prashant K. Srivastava; Deepak Putrevu; Nilesh M. Desai (Advances in Space Research, 2024)

Phytohormones mediated antifungal resistance against Fusarium oxysporum - Lucky Duhan; Raman Manoharlal; Deepak Kumar; Deepika Kumari; Mamta Saini; G. V. S. Saiprasad; Anil K. Chhillar; Ritu Pasrija (Acta Physiologiae Plantarum, 2024)

Preservation of plant‐wax biomarkers in deserts: implications for Quaternary environment and human evolutionary studies - Deepak Kumar Jha; Robert Patalano; Jana Ilgner; Hema Achyuthan; Abdullah M. Alsharekh; Simon Armitage; James Blinkhorn; Nicole Boivin; Paul S. Breeze; Ravindra Devra; Nicholas Drake; Huw S. Groucutt; et al. (Journal of Quaternary Science, 2024)
Analysis of plant‐wax biomarkers from sedimentary sequences can enable past environmental and hydrological reconstruction and provide insights into past hominin adaptations. However, biomarker preservation in desert contexts has been considered unlikely given the sparse nature of the vegetation within the landscape. Here we evaluate the preservation of n ‐alkanes and fatty acids collected from four depositional sequences associated with archaeological contexts in the Nefud Desert, Saudi Arabia, and the Thar Desert, India. Pleistocene and Holocene samples were selected to understand the effects of age on preservation. The results of molecular distribution patterns and indices, particularly the high carbon preference index and average chain length, show the preservation of plant‐wax biomarkers in both the Holocene and Pleistocene desert sequences, while δ 13 C values and organic content provide insights into the vegetation contributing to the plant‐wax organic pool. This study provides a baseline for understanding human–environment interactions and for reconstructing changes in arid land habitats of relevance to hominins during the Quaternary.

Dynamicity and extractability of hydro-alcoholic solvents for Tinospora cordifolia stem: an investigation for target-oriented traditional drug discovery based on biologically active phytocompounds - Kalyan Hazra; Deepak Kumar; Sudipto Debnath; Susmita Mondal; Manoj Batule; Sreya Dutta; Arjun Singh; Ravindra Singh; Anupam Kumar Mangal (Vegetos, 2024)

Investigating the potential of delignified rice husk as a carbon-rich resource for extracting glucose and its utilization in biocement production through fungal isolates - Inderpal Devgon; Rohan Samir Kumar Sachan; Anupam Kumar; Deepak Kumar; Ajit Sharma; Arun Karnwal (Environmental Science and Pollution Research, 2024)

Development of Betulin-Loaded Nanostructured Lipid Carriers for the Management of Imiquimod-Induced Psoriasis - Prativa Biswasroy; Deepak Pradhan; Dilip Kumar Pradhan; Goutam Ghosh; Goutam Rath (AAPS PharmSciTech, 2024)

Experimental and computational studies on the corrosion inhibition potential of a novel synthesized thiophene and pyridine-based 1,3,4-oxadiazole hybrid against mild steel corrosion in 1 N HCl - Deepak Sharma; Abhinay Thakur; Manish Kumar Sharma; Anand Bhardwaj; Ashish Sihmar; Hariom Dahiya; Ashok Kumar Sharma; Ashish Kumar; Avni Berisha; Hari Om (Environmental Science and Pollution Research, 2024)

A Simple Method for Synthesizing Nitrogen-Doped Carbon Quantum Dots for Fluorescent “Turn off” Mercury (II) Ion Sensing - Prafulla Kumar Behera; Deepak Sahu; Bigyan Ranjan Jali; Aruna Kumar Barick; Sarat Kumar Swain; Priyaranjan Mohapatra (Journal of Fluorescence, 2024)

Commercialization potential of PET (polyethylene terephthalate) recycled nanomaterials: A review on validation parameters - Vinay Kumar; Neha Sharma; Mridul Umesh; Roopali Sharma; Munish Sharma; Deepak Sharma; Munish Sharma; Sonica Sondhi; Jithin Thomas; Deepak Kumar; Lavish Kansal; Niraj Kumar Jha (Chemosphere, 2024)

Improvement of qualitative and quantitative traits in cotton under normal and stressed environments using genomics and biotechnological tools: A review - Aarti Gupta; Manoj Kumar; Baohong Zhang; Maharishi Tomar; Amandeep Kaur Walia; Prince Choyal; Ravi Prakash Saini; Jayashree Potkule; David J. Burritt; Vijay Sheri; Pooja Verma; Deepak Chandran; et al. (Plant Science, 2024)

Nanomolar electrochemical detection of feed additive ractopamine in meat samples using spinel zinc ferrite decorated 3-dimensional graphene nanosheets to combat food fraud in livestock industries - Deepak Balram; Kuang-Yow Lian; Neethu Sebastian; Salman S. Alharthi; Hamed M. Al-Saidi; Deepak Kumar (Food Chemistry, 2024)

Biocatalyst for the synthesis of natural flavouring compounds as food additives: Bridging the gap for a more sustainable industrial future - Suman Singh; Praveen Kumar Sharma; Shivani Chaturvedi; Prashant Kumar; Ashween Deepak Nannaware; Alok Kalra; Prasant Kumar Rout (Food Chemistry, 2024)

Antibiotic resistance and virulence genes profile of Non typhodial Salmonella species isolated from poultry enteritis in India - Arpita Sain; Deepak Kumar Sharma; Rajesh Singathia; Abhishek Gaurav; Chaman Patidar; PrabuRam Suthar; Karishma Rathore; Rohit Juneja (Tropical Animal Health and Production, 2024)

Discovering the regulators of heat stress tolerance in Ziziphus nummularia (Burm.f) wight and walk.-arn - Kishor Prabhakar Panzade; Kishor U. Tribhuvan; Deepak V. Pawar; Rahul Singh Jasrotia; Kishor Gaikwad; Monika Dalal; Ranjeet Ranjan Kumar; Madan Pal Singh; Om Prakash Awasthi; Jasdeep Chatrath Padaria (Physiology and Molecular Biology of Plants, 2024)

Green synthesis of iron nanoparticles using Mangifera indica leaves extract: phytochemical analysis and characterizations, for environmental remediation of pollution - Giriraj Tailor; Muhammad Tukur Mukhtar; Ahmad Nasir Labaran; Alhassan Muhd Garba; Ya’u Datti; Saurabh Singh; Deepak Kumar; Jyoti Chaudhary (Nanotechnology for Environmental Engineering, 2024)

Boosting of Free Radical Scavenging Capacity and Physiological Markers of Tomato Plants by Vermicompost Application During Nematode Stress - Raman Tikoria; Deepak Kumar; Mohd Ali; Puja Ohri (Journal of Soil Science and Plant Nutrition, 2024)

Genetic and functional mechanisms of yield-related genes in rice - Poulomi Sen; Avishek Chatterjee; Deepak Kumar; Somnath Bhattacharyya; Sayani Bandyopadhyay; Apurba Sarkar (Acta Physiologiae Plantarum, 2024)

Spray-Dried Mucoadhesive Re-dispersible Gargle of Chlorhexidine for Improved Response Against Throat Infection: Formulation Development, In Vitro and In Vivo Evaluation - Vineet Kumar Rai; Amresh Kumar; Deepak Pradhan; Jitu Halder; Tushar Kanti Rajwar; Manoj Kumar Sarangi; Priyanka Dash; Chandan Das; Salim Manoharadas; Biswakanth Kar; Goutam Ghosh; Goutam Rath (AAPS PharmSciTech, 2024)

In silico exploration of hypothetical proteins in Neisseria gonorrhoeae for identification of therapeutic targets - Gunjan Lakhanpal; Harshita Tiwari; Monu Kumar Shukla; Deepak Kumar (In Silico Pharmacology, 2024)

Influence of flow area zone and vertical lift motion of polymetallic nodules in hydraulic collecting - K. Amudha; S.K. Bhattacharya; Rajiv Sharma; K. Gopkumar; Deepak Kumar; G.A. Ramadass (Ocean Engineering, 2024)

Investigating antimicrobial resistance determinants and micropollutants in urban sewage treatment plants of India: Occurrence, removal and ecotoxicological risk - Rishabh Shukla; Deepak Kumar Prasad; Shaikh Ziauddin Ahammad (Journal of Environmental Chemical Engineering, 2024)

In vitro and In silico evaluation of the antioxidant, anti-microbial and antihyperglycemic properties of giloy (Tinospora cordifolia L.) stem extract - Kimmy; Deepak Kumar Verma; Pawan Prabhakar; Soubhagya Tripathy; Basant Kumar Dadrwal; Pradyuman Kumar; Prem Prakash Srivastav; Mamoni Banerjee (Biocatalysis and Agricultural Biotechnology, 2024)

Occurrence of Multidrug-Resistant (MDR) Extended-Spectrum Beta-lactamase (ESBL)-Producing Escherichia coli in Wastewater and Natural Water Sources from the Eastern Part of Uttar Pradesh, India - Kaushik Satyaprakash; Pavan Kumar Pesingi; Annada Das; M. R. Vineeth; Satya Veer Singh Malik; Sukhadeo B. Barbuddhe; Deepak Bhiwa Rawool (Water, Air, & Soil Pollution, 2024)

Optimization and characterization of hybrid bio-briquettes produced from the mixture of sawdust, sugarcane bagasse, and paddy straw - Arshad Ali; Deepak Chhabra; Meena Kumari; Manisha; Pinkey; Sumit Tiwari; Ravinder Kumar Sahdev (Environmental Science and Pollution Research, 2024)

Air stone-induced microbubble agitation: a strategy for solar still performance enhancement - Deepak Kumar Murugan; Hitesh Panchal; Zafar Said; S. Shankaranarayanan (Clean Technologies and Environmental Policy, 2024)

Active waveguide deformation dynamics using acoustic emission technology for landslide early warning system - Deepak Kumar; Ajit K. Mahapatro; Sushil Kumar Singh (Bulletin of Engineering Geology and the Environment, 2024)

Reactivation of varicella zoster virus following trigeminal schwannoma resection - Singh Deepak Kumar; Sinha Kshitij; Singh Rakesh Kumar; Yadav Kuldeep; Kaif Mohammad; Chand Vipin Kumar; Singh Nirbhay (Journal of NeuroVirology, 2024)

Chromium-induced phytotoxicity and its impact on plant metabolism - Hemanta Kumar Patra; Deepak Kumar Patra; Srinivas Acharya (Acta Physiologiae Plantarum, 2024)

Insight into the Biomass-Based Briquette Generation from Agro-Residues: Challenges, Perspectives, and Innovations - Arshad Ali; Meena Kumari; Manisha; Sumit Tiwari; Mahesh Kumar; Deepak Chhabra; Ravinder Kumar Sahdev (BioEnergy Research, 2024)

Evaluation of anticancer, immunomodulatory and anti-inflammatory potential of antioxidant rich Anzia ornatoides, a lichen species from eastern Himalayan region - Pungbili Islary; Rajesh Kumar Meher; Suparna Biswas; Derhasat Basumatary; Indra Bhusan Basumatary; Debasmita Dubey; Deepak Basumatary; Rebecca Daimari (South African Journal of Botany, 2024)

Late Quaternary human-environment relationship in the Ganga Plain, India - Deepak Kumar Jha; Hemant Kumar Vaishnav; Nigamasish Roy (Quaternary International, 2024)

Does leaf wax isotopic characterisation of gymnosperms and angiosperms capture environmental gradients in Himalayas? - Deepak Kumar Jha; Pranav Hirave; Sambit Ghosh; Bibhasvata Dasgupta; Prasanta Sanyal (Organic Geochemistry, 2024)

Prioritized experience replay based deep distributional reinforcement learning for battery operation in microgrids - Deepak Kumar Panda; Oliver Turner; Saptarshi Das; Mohammad Abusara (Journal of Cleaner Production, 2024)

Sustainable pathways for solar desalination using nanofluids: A critical review - Dhananjay Singh; Sunita Singh; Deepak Singh; Jyoti Kushwaha; Vinay Mishra; Suresh Kumar Patel; Sanjay Tewari; Balendu Shekher Giri (Environmental Research, 2024)

Fabrication of next-generation multifunctional LBG-s-AgNPs@ g-C3N4 NS hybrid nanostructures for environmental applications - Sadanand Pandey; Sujeong Kim; Young Soo Kim; Deepak Kumar; Misook Kang (Environmental Research, 2024)

Insights into the characterization and therapeutic potential of Tasar silkworm pupal oil - Devika Srivastava; Deepak Kumar Tripathi; Vandana Singh; Krishna Mohan Poluri; Venkatesh Kumar R (Biocatalysis and Agricultural Biotechnology, 2024)

Unraveling the involvement of WRKY TFs in regulating plant disease defense signaling - Baisista Saha; Jagatjeet Nayak; Richa Srivastava; Swarnmala Samal; Deepak Kumar; Jeky Chanwala; Nrisingha Dey; Mrunmay Kumar Giri (Planta, 2024)

Facile Synthesis of S-doped Carbon Quantum Dots and Their Application in the Detection of Sudan I in Saffron - Tahir ul Gani Mir; Azad Qayoom Malik; Saurabh Shukla; Jaskaran Singh; Deepak Kumar (Journal of Fluorescence, 2024)

Israel−Palestine Conflict: Risk of Sleep Disorders and Post-Traumatic Stress Disorders - Seithikurippu R. Pandi‑Perumal; Kamalesh K. Gulia; Hruda Nanda Mallick; Deepak Shrivastava; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Konda Mani Saravanan; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Derebe Madoro; Meera Narasimhan; et al. (Sleep and Vigilance, 2023)

Upper-crustal structure, compositions and tectonic settings obtained from Perur–Chikmagalur 3-C seismic profile of Archean Dharwar Province, southern India - Deepak Kumar; Laxmidhar Behera (Acta Geophysica, 2023)

Hybrid technique for crop image compression using discrete wavelet transform and sparse singular vector reconstruction - Deepak Mishra; Anil Kumar; Vijaypal Singh Rathor; G.K. Singh (Computers and Electronics in Agriculture, 2023)

Surface mass balance calculation with ground observation in the sub-basin of Larsemann Hills, East Antarctica - Surendra Jat; Mohammad Sadiq; Pradeep Kumar; Abhishek Verma; Deepak Y Gajbhiye (Polar Science, 2023)

Estimation of lunar surface roughness using Chandrayaan-2 full-polarimetric DFSAR data - Inderkumar Kochar; Tathagata Chakraborty; Sriram Saran Bhiravarasu; Anup Das; Deepak Putrevu; Rajib Kumar Panigrahi (Icarus, 2023)

Tea (Camellia sinensis (L.) Kuntze) as an emerging source of protein and bioactive peptides: A narrative review - Manoj Kumar; Pavidharshini Selvasekaran; Ramalingam Chidambaram; Baohong Zhang; Muzaffar Hasan; Om Prakash Gupta; Nadeem Rais; Kanika Sharma; Anshu Sharma; José M. Lorenzo; E. Parameswari; Vishal P. Deshmukh; et al. (Food Chemistry, 2023)

Ag decorated Zn-Al layered double hydroxide for adsorptive removal of heavy metals and antimicrobial activity: Numerical investigations, statistical analysis and kinetic studies - P.K. Asha; K. Deepak; M.K. Prashanth; L. Parashuram; V.S. Anusuya Devi; S. Archana; H. Shanavaz; S. Shashidhar; K.N. Prashanth; K. Yogesh Kumar; M.S. Raghu (Environmental Nanotechnology, Monitoring & Management, 2023)

Post-thaw murrah buffalo (Bubalus bubalis) sperm traits using ice recrystallization inhibitors - Prahlad Singh; Deepak Sharma; Ajeet Kumar; Ashwani Kumar Singh; Mrigank Honparkhe (Cryobiology, 2023)

Growing Organic Exotic Apples in Trans-Himalayan Ladakh in Climate Change Scenarios - Tsetan Dolker; Tsering Dolma; Deepak Kumar; Naveen C. Sharma; O. P. Chaurasia; Tsering Stobdan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Modulations of functional traits of Spinacia oleracea plants exposed to cadmium stress by using H2S as an antidote: a regulatory mechanism - Pradeep Kumar Yadav; Arun Kumar; Prashasti Pandey; Deepak Kumar; Anita Singh (Physiology and Molecular Biology of Plants, 2023)

Efficient photodegradation of fast sulphon black and crystal violet dyes from water systems using locust bean gum (LBG)-encapsulated zirconium-based nanoparticles and antibacterial activity - Ajay Sharma; Manita Thakur; Ajay Kumar; Manjula Gautam; Swati Kumari; Deepak Pathania; Arush Sharma (Nanotechnology for Environmental Engineering, 2023)

Insights into the Role of Biochar as Potential Agent in the Management of Disease Caused by Phytopathogens: a Review - Raman Tikoria; Deepak Kumar; Roohi Sharma; Parkirti Parkirti; Shivam Jasrotia; Anu Bala Chowdhary; Puja Ohri (Journal of Soil Science and Plant Nutrition, 2023)

Development and Pharmaceutical Evaluation of Azelaic Acid and Vitamin E Oil-Based Nanoemulgel of Tacrolimus for Topical Application in Plaque Psoriasis - Vineet Kumar Rai; Ankita Roy; Alok Sharma; Goutam Rath; Biswakanth Kar; Goutam Ghosh; Deepak Pradhan; Jitu Halder (Journal of Pharmaceutical Innovation, 2023)

Machine learning models for predicting vegetation conditions in Mahanadi River basin - Deepak Kumar Raj; T. Gopikrishnan (Environmental Monitoring and Assessment, 2023)

Comparative inhibitory screening of phytoconstituents from Capparis decidua against various ailments targets: a novel In-silico semblance ADME/Tox profiling studies - Rajendra S. Dave; Deepak Kumar Sharma; Kamlesh R. Shah (Advances in Traditional Medicine, 2023)

Impacts of changing climate and topography on snow cover variability of Parvati River Basin, western Himalayas, India - Deepak Kumar; Parteek SIngh Thind; Tejpal Sharma (Environmental Science and Pollution Research, 2023)

Production of lactones for flavoring and pharmacological purposes from unsaturated lipids: an industrial perspective - Naziya Syed; Suman Singh; Shivani Chaturvedi; Ashween Deepak Nannaware; Sunil Kumar Khare; Prasant Kumar Rout (Critical Reviews in Food Science and Nutrition, 2023)

Deficiency of spns1 exacerbates per- and polyfluoroalkyl substances mediated hepatic toxicity and steatosis in zebrafish (Danio rerio) - Sashi Gadi; Suryakant Niture; Hieu Hoang; Qi Qi; Charles Hatcher; Xiaoyan Huang; Jamil Haider; Derek C. Norford; TinChung Leung; Keith E. Levine; Deepak Kumar (Toxicology, 2023)

A review unveiling traditional uses and pharmacological potential of Hedychium spicatum Buch.-Ham. ex Sm. rhizomes for asthma - Aditi Sharma; Vikas Sharma; Deepak Kumar; Rohit Goyal (South African Journal of Botany, 2023)

In-silico anti-vitiligo activity of glycyrrhizin as potential IL-17 inhibitor and in-vitro antioxidant potential of isolated glycyrrhizin from G. glabra - Meena Kausar; Pallavi Pandey; Dheeraj Bisht; Sounok Sengupta; Deepak Kumar; Rajeshwar Kamal Kant Arya (South African Journal of Botany, 2023)

Biocontrol potential of Bacillus spp. for resilient and sustainable agricultural systems - Bhairav Prasad; Deepak Sharma; Pankaj Kumar; Ramesh Chandra Dubey (Physiological and Molecular Plant Pathology, 2023)

Sustainability issues of solar desalination hybrid systems integrated with heat exchangers for the production of drinking water: A review - Dhananjay Singh; Deepak Singh; Vinay Mishra; Jyoti Kushwaha; Rahul Dev; Suresh Kumar Patel; Ravi Shankar; Balendu Shekher Giri (Desalination, 2023)

Technology development and challenges for the transformation of municipal solid waste into sustainable energy production - Tirath Raj; Sandhya Sompura; K. Chandrasekhar; Sushil Kumar Singh; Srinath Pandey; Lalit Kumar Singh; Manish Singh Rajput; Deepak Kumar; Shashi Kant Bhatia; Anil Kumar Patel; Reeta Rani Singhania (Biomass and Bioenergy, 2023)

Environmental Antibiotic Resistance: Recent Trends, Scope, and Relevance - Neha Sharda; Deepak Kumar; Raman Thakur; Anil K. Sharma; Shailja Sankhyan; Anil Kumar (Water, Air, & Soil Pollution, 2023)

Development of entropy-river water quality index for predicting water quality classification through machine learning approach - Deepak Gupta; Virendra Kumar Mishra (Stochastic Environmental Research and Risk Assessment, 2023)

An emerging role of heterotrimeric G-proteins in nodulation and nitrogen sensing - Suvriti Sharma; Jahanvi Ganotra; Jyotipriya Samantaray; Ranjan Kumar Sahoo; Deepak Bhardwaj; Narendra Tuteja (Planta, 2023)

Seed endophytic bacterium Bacillus velezensis and its lipopeptides acts as elicitors of defense responses against Fusarium verticillioides in maize seedlings - Gaurav Pal; Samiksha Saxena; Kanchan Kumar; Anand Verma; Deepak Kumar; Pooja Shukla; Ashutosh Pandey; Satish K. Verma (Plant and Soil, 2023)

Examining the dynamic synthesis between environmental quality, economic globalization, and economic complexity in OECD countries - Hemachandra Padhan; Deepak Kumar Behera; Santosh Kumar Sahu; Umakant Dash (Environment, Development and Sustainability, 2023)

Rapid and Specific Detection of B. melitensis Targeting BMEI1661 Gene Using Loop-mediated Isothermal Amplification (LAMP) Combined With Lateral Flow immunoassay (LFIA) - Marcia Ashmi; Bablu Kumar; Sanjana; Abhishek; Deepak Kumar; Praveen Singh (Current Microbiology, 2023)

Ziziphus mauritiana-derived nitrogen-doped biogenic carbon dots: Eco-friendly catalysts for dye degradation and antibacterial applications - Subramani Rajapandi; Senthilkumar Nangan; Thirumalaivasan Natesan; Anuj Kumar; Govindaraj Dharman; M. Pandeeswaran; Deepak Verma; Mohd Ubaidullah; Bidhan Pandit; Navdeep Dhaliwal; Satbir S. Sehgal; Rajavel Rangappan; et al. (Chemosphere, 2023)

Hedychium spicatum: A comprehensive insight into its ethnobotany, phytochemistry, pharmacological and therapeutic attributes - Monika Singh; Ranjan Kumar; Samridhi Sharma; Lokender Kumar; Sachin Kumar; Gaurav Gupta; Kamal Dua; Deepak Kumar (South African Journal of Botany, 2023)

Variance-capturing forward-forward autoencoder (VFFAE): A forward learning neural network for fault detection and isolation of process data - Deepak Kumar; Umang Goswami; Hariprasad Kodamana; Manojkumar Ramteke; Prakash Kumar Tamboli (Process Safety and Environmental Protection, 2023)

Sustainable functionalized chitosan based nano-composites for wound dressings applications: A review - Deepak Verma; Manunya Okhawilai; Kheng Lim Goh; Vijay Kumar Thakur; Nangan Senthilkumar; Mohit Sharma; Hiroshi Uyama (Environmental Research, 2023)

Advancement in precision diagnosis and therapeutic for triple-negative breast cancer: Harnessing diagnostic potential of CRISPR-cas & engineered CAR T-cells mediated therapeutics - Vinayak Nayak; Sushmita Patra; Kshitij RB Singh; Bristy Ganguly; Das Nishant Kumar; Deepak Panda; Ganesh Kumar Maurya; Jay Singh; Sanatan Majhi; Rohit Sharma; Shyam S. Pandey; Ravindra Pratap Singh; et al. (Environmental Research, 2023)

Effective corrosion inhibition of mild steel using novel 1,3,4-oxadiazole-pyridine hybrids: Synthesis, electrochemical, morphological, and computational insights - Deepak Sharma; Abhinay Thakur; Manish Kumar Sharma; Renu Sharma; Suresh Kumar; Ashish Sihmar; Hariom Dahiya; Gaurav Jhaa; Ashish Kumar; Ashok Kumar Sharma; Hari Om (Environmental Research, 2023)

Deep learning-enhanced design for functionally graded auxetic lattices - Jinghui Li; Deepak Kumar Pokkalla; Zhen-Pei Wang; Yingjun Wang (Engineering Structures, 2023)

Plant -microbe assisted emerging contaminants (ECs) removal and carbon cycling - Anand Giri; Deepak Pant; Vimal Chandra Srivastava; Manoj Kumar; Ashok Kumar; Meera Goswami (Bioresource Technology, 2023)

Nanoencapsulation of biofunctional components as a burgeoning nanotechnology-based approach for functional food development: A review - Soubhagya Tripathy; Deepak Kumar Verma; Alok Kumar Gupta; Prem Prakash Srivastav; Ami R. Patel; Mónica L. Chávez González; Gemilang Lara Utama; Cristobal Noe Aguilar (Biocatalysis and Agricultural Biotechnology, 2023)

Correction: Zingerone inhibits biofilm formation and enhances antibiotic efficacy against Salmonella biofilm - Kusum Kharga; Irra Dhar; Shashank Kashyap; Sounok Sengupta; Deepak Kumar; Lokender Kumar (World Journal of Microbiology and Biotechnology, 2023)

Zingerone inhibits biofilm formation and enhances antibiotic efficacy against Salmonella biofilm - Kusum Kharga; Irra Dhar; Shashank Kashyap; Sounok Sengupta; Deepak Kumar; Lokender Kumar (World Journal of Microbiology and Biotechnology, 2023)

Phytochemistry and biological activity of Erigeron annuus (L.) Pers - Rupali Rana; Swati Pundir; Uma Ranjan Lal; Raveen Chauhan; Santosh Kumar Upadhyay; Deepak Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

A delve into the pharmacological targets and biological mechanisms of Paederia foetida Linn.: a rather invaluable traditional medicinal plant - Mrinal Kashyap Sarma; Dipankar Saha; Bhrigu Kumar Das; Trishna Das; Shavkatjon Azizov; Deepak Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Glucose-conjugated glutenin nanoparticles for selective targeting and delivery of camptothecin into breast cancer cells - Raja Rajeswari Rajeshkumar; Parasuraman Pavadai; Theivendren Panneerselvam; Venkataraman Deepak; Sureshbabu Ram Kumar Pandian; Shanmugampillai Jeyarajaguru Kabilan; Sivakumar Vellaichamy; Anbu Jeyaraman; A. Santhana Krishna Kumar; Krishnan Sundar; Selvaraj Kunjiappan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Does the size of a protected area matter? An assessment of leopard population and habitat usage in a protected area of Shiwalik foothills, Himalaya - Janam Jai Sehgal; Debashish Panda; Deepak Kumar; Rajiv Kalsi; Maximilian L. Allen; Randeep Singh (Mammal Research, 2023)

Exogenous Melatonin Counteracts Salinity and Cadmium Stress via Photosynthetic Machinery and Antioxidant Modulation in Solanum lycopersicum L - Kritika Bhardwaj; Meenakshi Raina; Giovanni Marco Sanfratello; Prashasti Pandey; Ankita Singh; Ravi Rajwanshi; Neelam Prabha Negi; Anjana Rustagi; Khushboo; Deepak Kumar (Journal of Plant Growth Regulation, 2023)

Interactions of urbanisation, climate variability, and infectious disease dynamics: insights from the Coimbatore district of Tamil Nadu - Sudha Suresh; Gowhar Meraj; Pankaj Kumar; Deepak Singh; Inam Danish Khan; Ankita Gupta; Tarun Kumar Yadav; Asma Kouser; Ram Avtar (Environmental Monitoring and Assessment, 2023)

Crop establishment methods and weed management practices influence the productivity and profitability of Kharif rice (Oryza sativa L.) in a hot-humid summer climatic conditions - Sarthak Pattanayak; Satyananda Jena; Priyanka Das; Pravat Kumar Roul; Sagar Maitra; Tanmoy Shankar; Masina Sairam; Deepak Kumar Swain; Biswajit Pramanick; Ahmed Gaber; Akbar Hossain (Paddy and Water Environment, 2023)

Assessment of in-house algorithms on re-entry time prediction of uncontrolled space objects - Pooja Dutt; M. Mutyalarao; P. Bhanumathy; T.R. Saritha Kumari; Deepak Negi; A.K. Anilkumar; Abhay Kumar; V. Ashok (Advances in Space Research, 2023)

Seedpod extracts of Wrightia tinctoria shows significant anti-inflammatory effects in HepG2 and RAW-264.7cell lines - Eshani Karmakar; Prosenjit Das; Priyanka Yatham; Deepak Kumar; Satinath Mukhopadhyay; Sib Sankar Roy (Natural Product Research, 2023)

Harnessing unexplored medicinal values of the red listed South African weed Erigeron bonariensis: From ethnobotany to biomedicine - Vishal B. Mahanur; Rahul R. Rajge; Rashmi Saxena Pal; M.V.N.L. Chaitanya; Sukriti Vishwas; Saurabh Gupta; Gaurav Gupta; Deepak Kumar; Oluwafemi Omoniyi Oguntibeju; Zia ur Rehman; Faris F. Aba Alkhayl; Vinay Thakur; et al. (South African Journal of Botany, 2023)

Thermal and mechanical investigation of chemically treated hybrid biomass epoxy bio-composite: An approach of pyrolysis kinetics - Manish Choudhary; Dhananjay Singh; Sandesh K. Jain; Deepak Singh; G.L. Devnani; Sunita Singh; Anil Kumar Patel; Reeta Rani Singhania; Balendu Shekher Giri; Manish Kumar (Bioresource Technology Reports, 2023)

Demonstration of n-dodecane suitability for milking lipids from Chlorella vulgaris for the production of biodiesel - Deepak Kumar Yadav; Meenu Yadav; Pushpa Rani; Arti Yadav; Nisha Bhardwaj; N.R. Bishnoi; Anita Singh (Bioresource Technology Reports, 2023)

Advances and prospects of platelet-rich plasma therapy in veterinary ophthalmology - Khan Sharun; Deepak Chandran; K. M. Manjusha; Pratheesh D. Mankuzhy; Rohit Kumar; Abhijit M. Pawde; Kuldeep Dhama; Hussein M. El-Husseiny; Amarpal (Veterinary Research Communications, 2023)

Evaluation of multifrequency SAR data for estimating tropical above-ground biomass by employing radiative transfer modeling - Faseela V. Sainuddin; Sanid Chirakkal; Smitha V. Asok; Anup Kumar Das; Deepak Putrevu (Environmental Monitoring and Assessment, 2023)

Multi-scale feature fusion-based lightweight dual stream transformer for detection of paddy leaf disease - Ajitesh Kumar; Dhirendra Prasad Yadav; Deepak Kumar; Manu Pant; Gaurav Pant (Environmental Monitoring and Assessment, 2023)

An assessment of sustainable supply chain initiatives in Indian automobile industry using PPS method - Rupesh Kumar; Deepak Bangwal (Environment, Development and Sustainability, 2023)

Recent developments on photovoltaic thermal drying systems: a clean energy production - Manisha; Sumit Tiwari; Deepak Chhabra; Meena Kumari; Prabhakar Tiwari; Ravinder Kumar Sahdev (Clean Technologies and Environmental Policy, 2023)

Unveiling the microbial diversity and functional dynamics of Shiv Kund, Sohna hot spring, India through a shotgun metagenomics approach - Neha Saini; Mohd Aamir; Vinay Kumar Singh; Bansal Deepak; Sharma Mona (Archives of Microbiology, 2023)

Imazethapyr-Resistant Jungle Rice (Echinochloa colona) in Soybean Growing Belt of Central India: A Case Study - Subhash Chander; Dibakar Ghosh; Vikas C. Tyagi; C. R. Chethan; Deepak Pawar; Yogita Gharde; Bhumesh Kumar; P. K. Singh (Agricultural Research, 2023)

Household food waste and theory of planned behavior: A systematic review and meta-analysis - Saurabh Kumar Srivastava; Aviral Mishra; Saumya Singh; Deepak Jaiswal (Environmental Science and Pollution Research, 2023)

siRNA-Based Novel Therapeutic Strategies to Improve Effectiveness of Antivirals: An Insight - Krittika Chatterjee; Sagheerah Lakdawala; Sheikh Shahnawaz Quadir; Dinesh Puri; Dinesh Kumar Mishra; Garima Joshi; Sanjay Sharma; Deepak Choudhary (AAPS PharmSciTech, 2023)

In-silico identification of small molecule benzofuran-1,2,3-triazole hybrids as potential inhibitors targeting EGFR in lung cancer via ligand-based pharmacophore modeling and molecular docking studies - Sunil Kumar; Iqra Ali; Faheem Abbas; Nimra Khan; Manoj K. Gupta; Manoj Garg; Saroj Kumar; Deepak Kumar (In Silico Pharmacology, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

Seagrass ecosystem adjacent to mangroves store higher amount of organic carbon of Andaman and Nicobar Islands, Andaman Sea - Amrit Kumar Mishra; Prasannajit Acharya; Deepak Apte; Syed Hilal Farooq (Marine Pollution Bulletin, 2023)

Identifying optimum residue levels for stable crop and water productivity and carbon sequestration under a conservation agriculture based rice-wheat system - Ram Swaroop Bana; Shanti Devi Bamboriya; Vipin Kumar; Samarth Godara; Donald S. Gaydon; Alison M. Laing; Rajkumar Dhakar; Y.S. Shivay; Vijay Singh Meena; Deepak Singh (Soil and Tillage Research, 2023)

Production of bio-oil from lychee-based biomass through pyrolysis and maximization of bio-oil yield with statistical and machine learning techniques - Yashvir Singh; Deepak Singh; Nishant Kumar Singh; Abhishek Sharma; Erween Abd Rahim; Arunkumar Ranganathan; Pandiarajan Palanichamy; Arkom Palamanit; Sanjeev Kumar (Journal of Cleaner Production, 2023)

Peach (Prunus persica (L.) Batsch) seeds and kernels as potential plant-based functional food ingredients: A review of bioactive compounds and health-promoting activities - Neeraj Kumari; Radha; Manoj Kumar; Sunil Puri; Baohong Zhang; Nadeem Rais; Ashok Pundir; Deepak Chandran; Priya Raman; Sangram Dhumal; Abhijit Dey; Marisennayya Senapathy; et al. (Food Bioscience, 2023)

Optimization of MAE for Carica papaya phytochemicals, and its in silico, in vitro, and ex vivo evaluation: For functional food and drug applications - Pawan Prabhakar; Sayan Mukherjee; Ankit Kumar; Suraj Kumar; Deepak Kumar Verma; Santanu Dhara; Mrinal Kumar Maiti; Mamoni Banerjee (Food Bioscience, 2023)

Enhanced pearl millet yield stability, water use efficiency and soil microbial activity using superabsorbent polymers and crop residue recycling across diverse ecologies - R.S. Bana; Minakshi Grover; Deepak Singh; Shanti D. Bamboriya; Samarth Godara; Manoj Kumar; Anil Kumar; Seema Sharma; P.S. Shekhawat; Dinesh Lomte; H.M. Bhuva; Sadhana R. Babar; et al. (European Journal of Agronomy, 2023)

U-Pb Neoproterozoic age and petrogenesis of a calc-alkaline shoshonitic lamprophyre from Simdega area, Chhotanagpur Gneissic Complex (Eastern India): Implication for the evolution of the Central Indian Tectonic Zone and Rodinia tectonics - Deepak Kumar; N.V. Chalapathi Rao; Aparajita Tripathi; B. Belyatsky; Priyesh Prabhat; Waliur Rahaman; M. Satyanarayanan (Chemical Geology, 2023)

Rottlerin renders a selective and highly potent CYP2C8 inhibition to impede EET formation for implication in cancer therapy - Diksha Manhas; Shipra Bhatt; Garima Rai; Vinay Kumar; Sahil Bharti; Sumit Dhiman; Shreyans K. Jain; Deepak K. Sharma; Probir Kumar Ojha; Sumit G. Gandhi; Anindya Goswami; Utpal Nandi (Chemico-Biological Interactions, 2023)

Poly(3-hydroxybutyrate) production from industrial hemp waste pretreated with a chemical-free hydrothermal process - Anindita Paul; Linjing Jia; Erica L.-W. Majumder; Chang Geun Yoo; Karthik Rajendran; Esteban Villarreal; Deepak Kumar (Bioresource Technology, 2023)

Entropy-based assessment of climate dynamics with varying elevations for hilly areas of Uttarakhand, India - Shekhar Singh; Deepak Kumar; Anil Kumar; Alban Kuriqi (Sustainable Water Resources Management, 2023)

Development of Thermotolerant Lactobacilli Cultures with Improved Probiotic Properties Using Adaptive Laboratory Evolution Method - Jyothna Bommasamudram; Pradeep Kumar; Sonal Kapur; Deepak Sharma; Somashekar Devappa (Probiotics and Antimicrobial Proteins, 2023)

Correction: Salicylic Acid and Methyl Jasmonate Synergistically Ameliorate Salinity Induced Damage by Maintaining Redox Balance and Stomatal Movement in Potato - Shashi Shekhar; Ayushi Mahajan; Prashasti Pandey; Meenakshi Raina; Anjana Rustagi; Ram Prasad; Deepak Kumar (Journal of Plant Growth Regulation, 2023)

Salicylic Acid and Methyl Jasmonate Synergistically Ameliorate Salinity Induced Damage by Maintaining Redox Balance and Stomatal Movement in Potato - Shashi Shekhar; Ayushi Mahajan; Prashasti Pandey; Meenakshi Raina; Anjana Rustagi; Ram Prasad; Deepak Kumar (Journal of Plant Growth Regulation, 2023)

Ensemble surface soil moisture estimates at farm-scale combining satellite-based optical-thermal-microwave remote sensing observations - Bappa Das; Pooja Rathore; Debasish Roy; Debashis Chakraborty; Bimal Kumar Bhattacharya; Dipankar Mandal; Raghuveer Jatav; Deepak Sethi; Joydeep Mukherjee; Vinay Kumar Sehgal; Amit Kumar Singh; Parveen Kumar (Agricultural and Forest Meteorology, 2023)

Future prediction of water balance using the SWAT and CA-Markov model using INMCM5 climate projections: a case study of the Silwani watershed (Jharkhand), India - Mukesh Kumar; Lakhan Lal Mahato; Shakti Suryavanshi; Sudhir Kumar Singh; Arnab Kundu; Dipanwita Dutta; Deepak Lal (Environmental Science and Pollution Research, 2023)

Fermentative valorisation of xylose-rich hemicellulosic hydrolysates from agricultural waste residues for lactic acid production under non-sterile conditions - Rylan Cox; Vivek Narisetty; Eulogio Castro; Deepti Agrawal; Samuel Jacob; Gopalakrishnan Kumar; Deepak Kumar; Vinod Kumar (Waste Management, 2023)

Economic perspectives and policy insights on carbon capture, storage, and utilization for sustainable development - Sarath C. Gowd; Prabakaran Ganeshan; V.S. Vigneswaran; Md Shahadat Hossain; Deepak Kumar; Karthik Rajendran; Huu Hao Ngo; Arivalagan Pugazhendhi (Science of The Total Environment, 2023)

Freezability and Fertility Rates of Stallion Semen Supplemented With Trehalose in Lactose Extender - Dinesh Jhamb; Thirumala Rao Talluri; Sunanda Sharma; Rohit Juneja; Surendar Singh Nirwan; Deepak Yadav; Kalpesh Kumar Pargi; Aashish Tanwar; Pramod Kumar; Ramesh Kumar; Sharat Chandra Mehta; Mukesh Parashar; et al. (Journal of Equine Veterinary Science, 2023)

Overexpression of flowering locus D (FLD) in Indian mustard (Brassica juncea) enhances tolerance to Alternaria brassicae and Sclerotinia sclerotiorum - Shashi Shekhar; Ruby Panwar; Subhash Chandra Prasad; Deepak Kumar; Anjana Rustagi (Plant Cell Reports, 2023)

Does access to clean cooking fuels reduce environmental degradation? Evidence from BRICS nations - Ajayan Thamarakshan Sreeja; Anjali Dhengle; Deepak Kumar; Ashis Kumar Pradhan (Environmental Science and Pollution Research, 2023)

Anticancer activity of essential oils: Cell cycle perspective - Vanshika Sharma; Deepak Kumar; Kamal Dev; Anuradha Sourirajan (South African Journal of Botany, 2023)

Modeling of standardized groundwater index of Bihar using machine learning techniques - Shomya Kumari; Deepak Kumar; Manish Kumar; Chaitanya B. Pande (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Plant biomass driven synthesis of gAu/RGO nanocomposite towards photocatalytic degradation of phenolic compounds in wastewater - Aparna Prabha Devi; Deepak Kumar Padhi; Ashish Madhual; Pravat Manjari Mishra; Ajay Kumar Behera (Journal of Environmental Chemical Engineering, 2023)

How does techno-economic analysis and lifecycle assessment help in commercializing the biohydrogen supply chain? - Prabakaran Ganeshan; V.S. Vigneswaran; Sarath C. Gowd; Dhamodharan Kondusamy; C. Sanjay kumar; Nageshwari Krishnamoorthy; Deepak Kumar; Ankita Juneja; Balasubramanian Paramasivan; Nithin N Raju; Karthik Rajendran; Arivalagan Pugazhendhi (Fuel, 2023)

Understanding HIV-associated neurocognitive and neurodegenerative disorders (neuroAIDS): enroute to achieve the 95-95-95 target and sustainable development goal for HIV/AIDS response - Shailendra K. Saxena; Deepak Sharma; Swatantra Kumar; Bipin Puri (VirusDisease, 2023)

Rejuvenating impact of COVID-19 lockdown on major environmental parameters: an Indian perspective - Deepak Kumar Jha; Niti Yashvardhini; Samiksha; Amit Kumar (Spatial Information Research, 2023)

Vasoconstriction during non-hypotensive hypovolemia is not associated with activation of baroreflex: A causality-based approach - Mansi Jain; Vinay Chitturi; Dinu S Chandran; Ashok Kumar Jaryal; K. K. Deepak (Pflügers Archiv - European Journal of Physiology, 2023)

Therapeutic Potential of Quercetin and its Derivatives in Epilepsy: Evidence from Preclinical Studies - Chandra Prakash; Jyoti Tyagi; Shyam Sunder Rabidas; Vijay Kumar; Deepak Sharma (NeuroMolecular Medicine, 2023)

Preparation and Characterization of Gatifloxacin-Loaded Polyacrylonitrile Nanofiber for the Management of Dry Eye Infection - Dipak Kumar Sahu; Deepak Pradhan; Jitu Halder; Prativa Biswasroy; Biswakanth Kar; Goutam Ghosh; Goutam Rath (Journal of Pharmaceutical Innovation, 2023)

Application of deep learning approaches to predict monthly stream flows - H. Yildirim Dalkilic; Deepak Kumar; Pijush Samui; Barnali Dixon; S. Nur Yesilyurt; O. Mert Katipoğlu (Environmental Monitoring and Assessment, 2023)

Effect of soil amendments on the sorption behavior of atrazine in sandy loam soil - Saif Ullah Khan; Anup Kumar; Mahendra Prasad; Deepak Upadhyay; Brijesh K. Mehta; P Shashikumara; Pooja Tamboli (Environmental Monitoring and Assessment, 2023)

Assessing the Impact of the 2004 Indian Ocean Tsunami on South Andaman’s Coastal Shoreline: A Geospatial Analysis of Erosion and Accretion Patterns - Saurabh Singh; Suraj Kumar Singh; Deepak Kumar Prajapat; Vikas Pandey; Shruti Kanga; Pankaj Kumar; Gowhar Meraj (Journal of Marine Science and Engineering, 2023)
The 2004 Indian Ocean earthquake and tsunami significantly impacted the coastal shoreline of the Andaman and Nicobar Islands, causing widespread destruction of infrastructure and ecological damage. This study aims to analyze the short- and long-term shoreline changes in South Andaman, focusing on 2004–2005 (pre- and post-tsunami) and 1990–2023 (to assess periodic changes). Using remote sensing techniques and geospatial tools such as the Digital Shoreline Analysis System (DSAS), shoreline change rates were calculated in four zones, revealing the extent of the tsunami’s impact. During the pre- and post-tsunami periods, the maximum coastal erosion rate was −410.55 m/year, while the maximum accretion was 359.07 m/year in zone A, the island’s east side. For the 1990–2023 period, the most significant coastal shoreline erosion rate was also recorded in zone A, which was recorded at −2.3 m/year. After analyzing the result, it can be seen that the tsunami severely affected the island’s east side. To validate the coastal shoreline measurements, the root mean square error (RMSE) of Landsat-7 and Google Earth was 18.53 m, enabling comparisons of the accuracy of different models on the same dataset. The results demonstrate the extensive impact of the 2004 Indian Ocean Tsunami on South Andaman’s coastal shoreline and the value of analyzing shoreline changes to understand the short- and long-term consequences of such events on coastal ecosystems. This information can inform conservation efforts, management strategies, and disaster response plans to mitigate future damage and allocate resources more efficiently. By better understanding the impact of tsunamis on coastal shorelines, emergency responders, government agencies, and conservationists can develop more effective strategies to protect these fragile ecosystems and the communities that rely on them.

Genotyping of Bemisia tabaci (Hemiptera: Aleyrodidae) affirmed a new record of Asia II 7, China 3 and dominance of Asia I cryptic species in Bihar, India - Gummudala Yashaswini; Somala Karthik; Beerelli Deepak Reddy; Mohammad Abbas Ahmad; Udit Kumar; Alagesan Keerthana; Gurram Mallikarjun; Seenivasan Abinaya; Morthala Shankara Sai Reddy (International Journal of Tropical Insect Science, 2023)

Statistical optimization for the production of bioactive exopolysaccharide by Ganoderma gibbosum under submerged fermentation conditions and in-vitro evaluation of its antioxidant activity - Ekta Chaudhary; Deepak Kumar Rahi (Biologia, 2023)

A review on the green synthesis of nanoparticles, their biological applications, and photocatalytic efficiency against environmental toxins - Azad Qayoom Malik; Tahir ul Gani Mir; Deepak Kumar; Irtiqa Ashraf Mir; Adfar Rashid; Mehnaz Ayoub; Saurabh Shukla (Environmental Science and Pollution Research, 2023)

Quantitative assessment of land surface temperature and vegetation indices on a kilometer grid scale - Noyingbeni Kikon; Deepak Kumar; Syed Ashfaq Ahmed (Environmental Science and Pollution Research, 2023)

Isolation and whole genome sequencing of Pseudomonas aeruginosa strain RK1 and its biocontrol potential against phytopathogens of rice - Ram Jatan; Richa Kamboj; Manish Kumar; Nitin Kumar; Priyanka Jain; Charu Lata; Joshitha Vijayan; Vandana Rai; Nagendra Kumar Singh; Deepak Singh Bisht (Biologia, 2023)

GWAS scans of cereal cyst nematode (Heterodera avenae) resistance in Indian wheat germplasm - Vikas Kumar Singh; Deepti Chaturvedi; Saksham Pundir; Deepak Kumar; Rajiv Sharma; Sundeep Kumar; Shiveta Sharma; Shailendra Sharma (Molecular Genetics and Genomics, 2023)

4D electrical resistivity to monitor unstable slopes in mountainous tropical regions: an example from Munnar, India - Arnaud Watlet; Hemalatha Thirugnanam; Balmukund Singh; Nitin Kumar M.; Deepak Brahmanandan; Cornelia Inauen; Russell Swift; Phil Meldrum; Sebastian Uhlemann; Paul Wilkinson; Jonathan Chambers; Maneesha Vinodini Ramesh (Landslides, 2023)
The number of large landslides in India has risen in the recent years, due to an increased occurrence of extreme monsoon rainfall events. There is an urgent need to improve our understanding of moisture-induced landslide dynamics, which vary both spatially and temporally. Geophysical methods provide integrated tools to monitor subsurface hydrological processes in unstable slopes at high spatial resolution. They are complementary to more conventional approaches using networks of point sensors, which can provide high temporal resolution information but are severely limited in terms of spatial resolution. Here, we present and discuss data from an electrical resistivity tomography monitoring system—called PRIME—deployed at the Amrita Landslide Early Warning System (Amrita-LEWS) site located in Munnar in the Western Ghats (Kerala, India). The system monitors changes in electrical resistivity in the subsurface of a landslide-prone slope that directly threatens a local community. The monitoring system provides a 4D resistivity model informing on the moisture dynamics in the subsurface of the slope. Results from a 10-month period spanning from pre-monsoon to the end of the monsoon season 2019 are presented and discussed with regard to the spatial variation of soil moisture. The temporal changes in resistivity within the slope are further investigated through the use of time-series clustering and compared to weather and subsurface pore water pressure data. This study sheds new light on the hydrological processes occurring in the shallow subsurface during the monsoon and potentially leading to slope failure. This geophysical approach aims at better understanding and forecasting slope failure to reduce the risk for the local community, thereby providing a powerful tool to be included in local landslide early warning systems.

The Effect of Cadmium Tolerant Plant Growth Promoting Rhizobacteria on Plant Growth Promotion and Phytoremediation: A Review - Ashok Kumar; Neha Kumari; Anjali Singh; Deepak Kumar; Dhirendra Kumar Yadav; Ashi Varshney; Navneet Sharma (Current Microbiology, 2023)

Structural Changes in Liposomal Vesicles in Association with Sodium Taurodeoxycholate - Deepak Kumar; Abhishek Suna; Debes Ray; Vinod K. Aswal; Pratap Bahadur; Sanjay Tiwari (AAPS PharmSciTech, 2023)

Solvent-free selective oxidation of cyclohexane to KA oil in air over CoWO4@W18O49 catalyst - Sonu Bhandari; Suresh Chandra Andola; Anil Chandra Kothari; Deepak Khurana; Shivani Singh; Mukesh Kumar Poddar; Tuhin Suvra Khan; Takehiko Sasaki; V.V.D.N. Prasad; Rajaram Bal (Journal of Environmental Chemical Engineering, 2023)

Microbial meat: A sustainable vegan protein source produced from agri-waste to feed the world - Samara Cardoso Alves; Erick Díaz-Ruiz; Bruna Lisboa; Minaxi Sharma; Solange I. Mussatto; Vijay Kumar Thakur; Deepak M. Kalaskar; Vijai Kumar Gupta; Anuj K. Chandel (Food Research International, 2023)

High dimensional model representation for flood fragility analysis of highway bridge - A. Anisha; Deepak Kumar Sahu; Pradip Sarkar; Sujith Mangalathu; Robin Davis (Engineering Structures, 2023)

Genetic mapping of some key plant architecture traits in Brassica juncea using a doubled haploid population derived from a cross between two distinct lines: vegetable type Tumida and oleiferous Varuna - Shikha Mathur; Priyansha Singh; Satish Kumar Yadava; Vibha Gupta; Akshay Kumar Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2023)

Change in Temperature Extremes over India Under 1.5 °C and 2 °C Global Warming Targets - Hardeep Kumar Maurya; Nitin Joshi; Deepak Swami; Shakti Suryavanshi (Theoretical and Applied Climatology, 2023)

Foliar zinc fertilization improves yield, biofortification and nutrient-use efficiency of upland rice - Akshay Kumar Yogi; Ram Swaroop Bana; Shanti D. Bamboriya; Ram L. Choudhary; Alison M. Laing; Deepak Singh; Samarth Godara; Subhash Babu; Amresh Chaudhary (Nutrient Cycling in Agroecosystems, 2023)

Revisiting the therapeutic potential of gingerols against different pharmacological activities - Samridhi Sharma; Monu Kumar Shukla; Krishan Chander Sharma; Tirath; Lokender Kumar; Jasha Momo H. Anal; Santosh Kumar Upadhyay; Sanjib Bhattacharyya; Deepak Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Liquiritigenin, isoliquiritigenin rich extract of glycyrrhiza glabra roots attenuates inflammation in macrophages and collagen-induced arthritis in rats - Vineet Babu; Deepak Singh Kapkoti; Monika Binwal; Rajendra S. Bhakuni; Karuna Shanker; Manju Singh; Sudeep Tandon; Madhav N. Mugale; Narendra Kumar; Dnyaneshwar U. Bawankule (Inflammopharmacology, 2023)

Fluoride risk assessment from agricultural soils in India: a study based on vertical, spatial and geochemical distribution - Sunil Kumar Jha; Yogesh Kumar Sharma; Amaresh Kumar Nayak; Deepak; Devanand (Environmental Monitoring and Assessment, 2023)

Hansen’s disease presenting as polyneuropathy: an unusual presentation - Dipti Baskar; Deepak Menon; Shilpa Rao; Pramod Kumar Pal (Acta Neurologica Belgica, 2023)

Monitoring of catechin content by high performance liquid chromatography during the development of seed and pods of Saraca asoca (Roxb.) De Willd - Jyoti Dahiya; Deepak Kumar; Rajesh Bolleddu; Sreya Dutta; Simmi Mall; Kalyan Hazra; Anupam K. Mangal (Vegetos, 2023)

Malabaricone C, a constituent of spice Myristica malabarica, exhibits anti-inflammatory effects via modulation of cellular redox - Raghavendra S Patwardhan; Kshama Kundu; Vaitashi Purohit; Binita Kislay Kumar; Beena Singh; Maikho Thoh; Khushboo Undavia; Hari N Bhilwade; Sandip K Nayak; Deepak Sharma; Santosh K Sandur (Journal of Biosciences, 2023)

Rice straw derived cellulose nanofibers modified with L-histidine for ultra-trace fluorometric assay of Cr(VI) and Hg(II) in aqueous medium - Vijay Kumar; Gaurav Rattan; Preeti Tewatia; Manpreet Kaur; Deepak Pathania; Sonal Singhal; Anupama Kaushik (Journal of Cleaner Production, 2023)

Application of ultrasonication as pre-treatment for freeze drying: An innovative approach for the retention of nutraceutical quality in foods - Roji Waghmare; Manoj Kumar; Rahul Yadav; Priyank Mhatre; Sachin Sonawane; Swati Sharma; Yogesh Gat; Deepak Chandran; Radha; Muzaffar Hasan; Abhijit Dey; Tanmay Sarkar; et al. (Food Chemistry, 2023)

Arsenite and arsenate ions adsorption onto a biogenic nano-iron entrapped dual network Fe@alginate-κ-carrageenan hydrogel beads - Anushree Srivastava; Shivesh Kumar Azad; Kavita Singh; Bablu Prasad; Madhu Kumari; Nandan; Amresh Kumar Sahoo; Hemen Dave; Deepak M. Maurya; Deepak Singh; Kumar Suranjit Prasad (Nanotechnology for Environmental Engineering, 2023)

Stem cell therapy: a novel approach against emerging and re-emerging viral infections with special reference to SARS-CoV-2 - Vishal Khandelwal; Tarubala Sharma; Saurabh Gupta; Shoorvir Singh; Manish Kumar Sharma; Deepak Parashar; Vivek K. Kashyap (Molecular Biology Reports, 2023)

New Luminescent Pyridine-based Disc type Molecules: Synthesis, Photophysical, Electrochemical, and DFT studies - Deepak Devadiga; T. N. Ahipa; S. Vanishree Bhat; Sandeep Kumar (Journal of Fluorescence, 2023)

Mechanistic insights into granule-bound starch synthase I (GBSSI.L539P) allele in high amylose starch biosynthesis in wheat (Triticum aestivum L.) - Vinita Sharma; Kousar Jahan; Prashant Kumar; Anuradhika Puri; Vishnu K. Sharma; Ankita Mishra; P. V. Bharatam; Deepak Sharma; Vikas Rishi; Joy Roy (Functional & Integrative Genomics, 2023)

Morphology, phylogeny, and pathogenicity of Simplicillium obclavatum (Hypocreales: Cordycipitaceae) against tomato leafminer, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Gurmeet Kour Bali; Deepak Kumar Maurya; Sanjay Kumar Singh; Radhakrishnan Sitaram Pandit (International Journal of Tropical Insect Science, 2023)

Development of Indian motorcycle driving cycles, evaluation for fuel economy and emissions - Masilamani Sithananthan; Ravindra Kumar; Deepak Saxena (Environment, Development and Sustainability, 2023)

Genetic diversity and risk factor analysis of drug-resistant Escherichia coli recovered from broiler chicken farms - Dadimi Bhargavi; Radhakrishna Sahu; Maria Anto Dani Nishanth; Swapnil Prakash Doijad; Pollumahanti Niveditha; Obli Rajendran Vinodh Kumar; C. Sunanda; P.S. Girish; B.M. Naveena; Jess Vergis; Satya Veer Singh Malik; Nitin Vasantrao Kurkure; et al. (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Enhancement of oxygen vacancy sites of La2-xMxCe2O7-δ (M = Ca, Ba, Sr) catalyst for the low temperature oxidative coupling of Methane: A combined DFT and experimental study - Rohan Singh Pal; Swati Rana; Sachin Kumar Sharma; Rubina Khatun; Deepak Khurana; Tuhin Suvra Khan; Mukesh Kumar Poddar; Rahul Sharma; Rajaram Bal (Chemical Engineering Journal, 2023)

Microalgae biomass deconstruction using green solvents: Challenges and future opportunities - Tirath Raj; Raj Morya; K Chandrasekhar; Deepak Kumar; Shveta Soam; Ravindra Kumar; Anil Kumar Patel; Sang-Hyoun Kim (Bioresource Technology, 2023)

Synthetic sub-genomic transcript promoter from Horseradish Latent Virus (HRLV) - Tsheten Sherpa; Deepak Kumar Jha; Khushbu Kumari; Jeky Chanwala; Nrisingha Dey (Planta, 2023)

In vitro and in vivo therapeutic antileishmanial potential of ellagic acid against Leishmania donovani in murine model - Poonam Keshav; Deepak Kumar Goyal; Sukhbir Kaur (Medical Microbiology and Immunology, 2023)

Integrated management of Fusarium wilt disease of banana in Kerala, India - N. P. Lishma; K. Anita Cherian; Vimi Louis; R. Sureshkumar; P. Naveen Kumar; Deepak Chandran; M. Pran; Rohit Sharma (Vegetos, 2023)

Drying characteristics of thin layer of potato (Solanum tuberosum): experimental and computational studies - Deepak Singh; Mukul Sengar; Suresh Kumar Patel; Dilip Kumar; Dharm Pal; Balendu Shekhar Giri; Dhananjay Singh (Environmental Science and Pollution Research, 2023)

Co-occurrence patterns and environmental factors associated with rapid onset of Microcystis aeruginosa bloom in a tropical coastal lagoon - Lipika Tarafdar; Madhusmita Mohapatra; Pradipta R. Muduli; Abhishek Kumar; Deepak R. Mishra; Gurdeep Rastogi (Journal of Environmental Management, 2023)

RETRACTED: Recent advances in lignocellulosic and algal biomass pretreatment and its biorefinery approaches for biochemicals and bioenergy conversion - Yue Zhang; Zheli Ding; Md Shahadat Hossain; Rupesh Maurya; Yulu Yang; Vijai Singh; Deepak Kumar; El-Sayed Salama; Xinwei Sun; Raveendran Sindhu; Parameswaran Binod; Zengqiang Zhang; et al. (Bioresource Technology, 2023)

Marker assisted stacking of Ty3, Mi1.2 and Ph3 resistance alleles for leaf curl, root knot and late blight diseases in tomato - Deepak Maurya; Arnab Mukherjee; Bhagyashree; Surabhi Sangam; Randhir Kumar; Shirin Akhtar; Tirthartha Chattopadhyay (Physiology and Molecular Biology of Plants, 2023)

Validation of resistance to cereal cyst nematode (Heterodera avenae) and yield performance study in doubled haploid lines of wheat (Triticum aestivum L.) - Saksham Pundir; Vikas Kumar Singh; Satish Kumar; Deepti Chaturvedi; Deepak Kumar; Rambir Singh Kanwar; Ashok Kumar; Andreas Börner; Shiveta Sharma; Shailendra Sharma (Genetic Resources and Crop Evolution, 2023)

Spatio-temporal variation of trace elements distributed over surface water of Upper Ganga River Basin in Western Himalayan Region - Deepika Dimri; Ambika Kumar; Deepak Kumar Mishra; Archana Sharma (Journal of Mountain Science, 2023)

Comprehensive spatio-temporal benchmarking of surface water quality of Hindon River, a tributary of river Yamuna, India: Adopting multivariate statistical approach - Anand Kumar Gupta; Ambrish Kumar; Uma Kant Maurya; Deepak Singh; Sadikul Islam; Avinash Chandra Rathore; Parmanand Kumar; Ravish Singh; M. Madhu (Environmental Science and Pollution Research, 2022)

Removal Process of a Metal-Dye Mixture Using Beauveria bassiana - Deepak Gola; Pankaj Kumar Tyagi; Meenu Singh; Anushree Malik; Nitin Chauhan; Yamini Agarwal (Water Conservation Science and Engineering, 2022)

Rhodamine B induced alteration in antioxidant enzymes and photosynthetic performance of Eichhornia crassipes - Jyotshana Sharma; Hanwant Singh; Shubhangani Sharma; Deepak Kumar; Upma Bhatt; Vineet Soni (Plant Physiology Reports, 2022)

Anti-viral triterpenes: a review - Priya Darshani; Shreya Sen Sarma; Amit K. Srivastava; Rinku Baishya; Deepak Kumar (Phytochemistry Reviews, 2022)

Good view frames from ultrasonography (USG) video containing ONS diameter using state-of-the-art deep learning architectures - Maninder Singh; Basant Kumar; Deepak Agrawal (Medical & Biological Engineering & Computing, 2022)

Liquefaction resistance of polypropylene strips reinforced sand-fly ash blend under strain-controlled cyclic triaxial test - Deepak Kumar; Siddhartha Sengupta (Innovative Infrastructure Solutions, 2022)

Novel Nanostructured Lipid Carriers Co-Loaded with Mesalamine and Curcumin: Formulation, Optimization and In Vitro Evaluation - Ankit Awasthi; Bimlesh Kumar; Monica Gulati; Sukriti Vishwas; Leander Corrie; Jaskiran Kaur; Rubiya Khursheed; Rozhan Arif Muhammed; Duran Kala; Omji Porwal; Malakapogu Ravindra Babu; M. V. N. L. Chaitanya; et al. (Pharmaceutical Research, 2022)

Enhancement of ketoprofen dissolution rate by the liquisolid technique: optimization and in vitro and in vivo investigations - Sunita Devi; Sunil Kumar; Vikas Verma; Deepak Kaushik; Ravinder Verma; Meenakshi Bhatia (Drug Delivery and Translational Research, 2022)

A comprehensive and quantitative assessment of Raunthi Gad flash flood, Rishi Ganga catchment, central Himalaya, Uttarakhand, India - Harish Chandra Nainwal; R. Shankar; Aditya Mishra; Sumit Mishra; Ankit Pandey; Sunil Singh Shah; Gambhir Singh Chauhan; Deepak Kumar (Natural Hazards, 2022)

Role of curcumin in ameliorating hypertension and associated conditions: a mechanistic insight - Priyanka Joshi; Sushil Joshi; Deepak Kumar Semwal; Kanika Verma; Jaya Dwivedi; Swapnil Sharma (Molecular and Cellular Biochemistry, 2022)

Thermo-economic comparison of single basin and stacked solar still configurations - Deepak Kumar Murugan; Sekar Subramani; Arunkumar Thirugnanasambantham; Karthick Munuswamy (Environmental Science and Pollution Research, 2022)

Groundwater vulnerability assessment using DRASTIC model in Niwari District of Bundelkhand Region, Madhya Pradesh, India - Deepak Patle; Sourabh Nema; Manoj Kumar Awasthi; Shailesh Kumar Sharma; Yogesh Kishore Tiwari (Arabian Journal of Geosciences, 2022)

Exploring the Potential of Metal Nanoparticles as a Possible Therapeutic Adjunct for Covid-19 Infection - Biswakanth Kar; Deepak Pradhan; Poonamrani Mishra; Sanat Kumar Bhuyan; Goutam Ghosh; Goutam Rath (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Integrating patient symptoms, clinical readings, and radiologist feedback with computer-aided diagnosis system for detection of infectious pulmonary disease: a feasibility study - Tej Bahadur Chandra; Bikesh Kumar Singh; Deepak Jain (Medical & Biological Engineering & Computing, 2022)

Glyphosate-resistant Brassica juncea (oilseed mustard) transgenics for possible control of root parasite Orobanche aegyptiaca and conservation agriculture - Parul Agarwal; Arundhati Mukhopadhyay; Vibha Gupta; Akshay Kumar Pradhan; Deepak Pental (Journal of Plant Biochemistry and Biotechnology, 2022)

Status of alternaria leaf blight and leaf spot diseases of makhana in North Bihar and their management strategies under integrated approach - Santosh Kumar; Md. Nadeem Akhtar; Deepak Kumar Patel; Tamoghna Saha; S. B. Sah (Indian Phytopathology, 2022)

Isolation, modification, and characterization of rice starch with emphasis on functional properties and industrial application: a review - Deepak Kumar Verma; Prem Prakash Srivastav (Critical Reviews in Food Science and Nutrition, 2022)

Thermal neutron as a potential mutagen for induced plant mutation breeding: radiosensitivity response on wheat and rice - Shivdas Tukaram Kadam; Gautam Vishwakarma; Yogesh Kashyap; Mayank Shukla; Tushar Roy; Parmeshwar Kumar Sahu; Deepak Sharma; Abhijit Shaligram Shitre; Vikash Kumar; Bikram Kishore Das (Genetic Resources and Crop Evolution, 2022)

Promising protein biomarkers in the early diagnosis of Alzheimer’s disease - Lalit Sharma; Aditi Sharma; Deepak Kumar; Manish Kumar Asthana; H. Lalhlenmawia; Ashwani Kumar; Sanjib Bhattacharyya; Deepak Kumar (Metabolic Brain Disease, 2022)

Characterization of composite coal seam III–IV of Ramagundam coalfield, Godavari Basin (India): an attempt to evaluate CBM prospects - Harinandan Kumar; Shweta Rai; Ankita Rai; Atif Faheem; Amiya Shankar Naik; Pramod Kumar Rajak; Dilip Kumar Srivastava; Deepak Singh Maurya; Don Chatterjee; Prakash K. Singh (Arabian Journal of Geosciences, 2022)

Decarbonization: examining the role of environmental innovation versus renewable energy use - Bhagaban Sahoo; Deepak Kumar Behera; Dil Rahut (Environmental Science and Pollution Research, 2022)
Climate change resulting from a rapid increase in greenhouse gas (GHG) emissions is adversely affecting humanity. If the GHG emission continues to rise at the current pace, humanity will face severe consequences and reverse all the progress made. This paper, therefore, uses relevant data from 14 developing countries in Asia from 1990 to 2018 to examine the potential impact of environmental innovation on CO 2 emissions by controlling globalization, urbanization, and economic growth. The number of environmental-related technology patents is used as a measure of environmental innovation. We employed a panel long-run regression model — FMOLS, PCSE, and FGLS to estimate the elasticity of CO 2 emissions. For causal association among variables, we used Dumitrescu-Hurlin Granger causality tests. Our results show that renewable energy consumption and globalization have a significant impact in reducing CO 2 emissions, while environmental technology innovations play a meager role in reducing emissions and only when economic growth support those type of investment. Furthermore, we found urbanization, oil consumption, and economic growth is detrimental to the environment, which is also evident in past studies. Therefore, countries should invest in renewable energy and environmental innovation aligned with the growth to reduce GHG emissions.

Detection of Human Serum Albumin on Gel from Sample Obtained from Different Cardiopulmonary Bypass (CPB) Filtrates in a Patient on Cardiopulmonary Bypass Surgery - Surender; Sumanpreet Kaur; Deepak Kumar; Sheemona Chowdhary; Rupesh Kumar; Rajasri Bhattacharyya; Dibyajyoti Banerjee (Indian Journal of Clinical Biochemistry, 2022)

Luliconazole Nail Lacquer for the Treatment of Onychomycosis: Formulation, Characterization and In Vitro and Ex Vivo Evaluation - Deepa Dehari; Abhishesh Kumar Mehata; Vishnu Priya; Dharmnath Parbat; Deepak Kumar; Anand Kumar Srivastava; Sanjay Singh; Ashish Kumar Agrawal (AAPS PharmSciTech, 2022)

Purification and identification of anticancer organosulfides from Ferula assa-foetida gum: integrative analysis employing GC/GC-MS/RP-HPLC/NMR - Priyanka Yatham; Devendra Shukla; Amit K. Srivastava; V.S. Pragadheesh; Deepak Kumar (Natural Product Research, 2022)

Sun-Dried Sugarcane Press Mud Could be a Prospective Feedstuff for Swine Production - Subhasish Sahu; B. H. M. Patel; Archana Sarangi; Dinesh Kumar; M. S. Mahesh; Deepak Upadhyay; Triveni Dutt (Sugar Tech, 2022)

A new window to the fossil herpetofauna of India: amphibians and snakes from the Miocene localities of Kutch (Gujarat) - Ningthoujam Premjit Singh; Rajeev Patnaik; Andrej Čerňanský; K Milankumar Sharma; Nongmaithem Amardas Singh; Deepak Choudhary; Ramesh Kumar Sehgal (Palaeobiodiversity and Palaeoenvironments, 2022)

Integrated Nutrient Management in Coconut (Cocos nucifera L.): an Assessment of Soil Chemical and Biological Parameters Under Subtropical Humid Climate - Deepak Kumar; Rajiv Rakshit; Ruby Rani; Pallavi Bharti; Anupam Das; Manoj Kundu (Journal of Soil Science and Plant Nutrition, 2022)

Coastal vulnerability assessment using Geospatial technologies and a Multi-Criteria Decision Making approach – a case study of Kozhikode District coast, Kerala State, India - K. Ch. V. Naga Kumar; P. M. Deepak; K. K. Basheer Ahammed; Kakani Nageswara Rao; Girish Gopinath; V. P. Dinesan (Journal of Coastal Conservation, 2022)

Association mapping, trait variation, interaction and population structure analysis in cucumber (Cucumis sativus L.) - Rahul Kumar; Anilabh Das Munshi; Tusar Kanti Behera; Gograj Singh Jat; Harshawardhan Choudhary; Akshay Talukdar; Prasanta Dash; Deepak Singh (Genetic Resources and Crop Evolution, 2022)

Residents’ willingness-to-pay for watershed conservation program facilitating ecosystem services in Begnas watershed, Nepal - Shivaraj Thapa; Subina Shrestha; Ram Kumar Adhikari; Suman Bhattarai; Deepa Paudel; Deepak Gautam; Anil Koirala (Environment, Development and Sustainability, 2022)

Spaceborne synthetic aperture radar (SAR) earth observations for surface deformation analysis and mapping - Noyingbeni Kikon; Deepak Kumar; S. A. Ahmed (Arabian Journal of Geosciences, 2022)

Recent insights into oceanic dimethylsulfoniopropionate biosynthesis and catabolism - Deepak Kumar Shaw; Jegan Sekar; Prabavathy Vaiyapuri Ramalingam (Environmental Microbiology, 2022)
Summary Dimethylsulfoniopropionate (DMSP), a globally important organosulfur compound is produced in prodigious amounts (2.0 Pg sulfur) annually in the marine environment by phytoplankton, macroalgae, heterotrophic bacteria, some corals and certain higher plants. It is an important marine osmolyte and a major precursor molecule for the production of climate‐active volatile gas dimethyl sulfide (DMS). DMSP synthesis take place via three pathways: a transamination ‘pathway‐’ in some marine bacteria and algae, a Met‐methylation ‘pathway‐’ in angiosperms and bacteria and a decarboxylation ‘pathway‐’ in the dinoflagellate, Crypthecodinium . The enzymes DSYB and TpMMT are involved in the DMSP biosynthesis in eukaryotes while marine heterotrophic bacteria engage key enzymes such as DsyB and MmtN. Several marine bacterial communities import DMSP and degrade it via cleavage or demethylation pathways or oxidation pathway, thereby generating DMS, methanethiol, and dimethylsulfoxonium propionate, respectively. DMSP is cleaved through diverse DMSP lyase enzymes in bacteria and via Alma1 enzyme in phytoplankton. The demethylation pathway involves four different enzymes, namely DmdA, DmdB, DmdC and DmdD/AcuH. However, enzymes involved in the oxidation pathway have not been yet identified. We reviewed the recent advances on the synthesis and catabolism of DMSP and enzymes that are involved in these processes.

Applications of Data-driven Models for Daily Discharge Estimation Based on Different Input Combinations - Manish Kumar; Ahmed Elbeltagi; Chaitanya B. Pande; Ali Najah Ahmed; Ming Fai Chow; Quoc Bao Pham; Anuradha Kumari; Deepak Kumar (Water Resources Management, 2022)

A Charge Variant of Bevacizumab Offers Enhanced FcRn-Dependent Pharmacokinetic Half-Life and Efficacy - Sumit K. Singh; Deepak Kumar; Saurabh Nagpal; Sunil K. Dubey; Anurag S. Rathore (Pharmaceutical Research, 2022)

A brief address of the causal factors, mechanisms, and the effects of a major landslide in Kangra valley, North-Western Himalaya, India - Ambrish Kumar Mahajan; Swati Sharma; Sunanda Patial; Harsh Sharma; Desh Deepak Pandey; Sushma Negi (Arabian Journal of Geosciences, 2022)

Streamflow regionalisation of an ungauged catchment with machine learning approaches - Lakhwinder Singh; Prabhash Kumar Mishra; Santosh Murlidhar Pingale; Deepak Khare; Hitesh Prasad Thakur (Hydrological Sciences Journal, 2022)

Isolation and estimation of flavonoid compound(s) of Baccharoides anthelmintica (L.) Moench - Deepak Kumar; Amanpreet Kaur; Reecha Madaan; Suresh Kumar (Natural Product Research, 2022)

Evaluating the impact of flood inundation with the cloud computing platform over vegetation cover of Ganga Basin during COVID-19 - Sukanya Ghosh; Deepak Kumar; Rina Kumari (Spatial Information Research, 2022)

Positive impact of COVID-19 induced lockdown on the environment of India’s national capital, Delhi - Niti Yashvardhini; Amit Kumar; Manjush Gaurav; Kumar Sayrav; Deepak Kumar Jha (Spatial Information Research, 2022)

Spatio-temporal overlap of leopard and prey species in the foothills of Shiwalik, Himalaya - Janam Jai Sehgal; Deepak Kumar; Rajiv S. Kalsi; Maximilian L. Allen; Randeep Singh (European Journal of Wildlife Research, 2022)

Anti-migraine activity of freeze-dried latex obtained from Calotropis gigantea Linn - Saurabh Bhatia; Ahmed Al-Harrasi; Arun Kumar; Tapan Behl; Aayush Sehgal; Sukhbir Singh; Neelam Sharma; Md. Khalid Anwer; Deepak Kaushik; Vineet Mittal; Sridevi Chigurupati; Pritam Babu Sharma; et al. (Environmental Science and Pollution Research, 2022)

A comprehensive multidisciplinary investigation on CO2 capture from diesel engine - Pulkit Kumar; Deepak K. Pandey; Ajit Kumar Parwani; Dheeraj K. Singh (Environmental Science and Pollution Research, 2022)

Gold nanoparticle–decorated earth-abundant clay nanotubes as catalyst for the degradation of phenothiazine dyes and reduction of 4-(4-nitrophenyl)morpholine - Krishnamoorthy Shanmugaraj; Cristian H. Campos; Ramalinga Viswanathan Mangalaraja; Karuppasamy Nandhini; Radhamanohar Aepuru; Cecilia C. Torres; Dinesh Pratap Singh; Deepak Kumar; Malaichamy Ilanchelian; Ajit Sharma; Dai-Viet N. Vo (Environmental Science and Pollution Research, 2022)

Antidiabetic effect of aqueous-ethanol extract from the aerial parts of Artemisia roxburghiana - Ankit Kumar; Sonali Aswal; Ashutosh Chauhan; Ruchi Badoni Semwal; Randhir Singh; Harish Chandra Andola; Sunil Kumar Joshi; Deepak Kumar Semwal (Natural Product Research, 2022)

Synthesis and effect of TiO2 nanoparticles on phytotoxicity and genotoxicity in Pisum sativum L. - Kalyan Singh Kushwah; Sapan Patel; Deepak Kumar Verma (Vegetos, 2022)

Ice dynamics of Vestre Brøggerbreen glaciers, Ny-Ålesund, Svalbard, Arctic - Mohammad Sadiq; Sharat Dutta; Pradeep Kumar; Surendra Jat; Deepak Y Gajbhiye; Amit Dharwadkar (Journal of Earth System Science, 2022)

Harnessing phytomicrobiome signals for phytopathogenic stress management - Akanksha Sharma; Meenakshi Raina; Deepak Kumar; Archana Singh; Samira Chugh; Shalu Jain; Manoj Kumar; Anjana Rustagi (Journal of Biosciences, 2022)

Correction to: Novel coronavirus pathogen in humans and animals: an overview on its social impact, economic impact, and potential treatments - Rokeya Akter; Md.Habibur Rahman; Tanima Bhattacharya; Deepak Kaushik; Vineet Mittal; Jatin Parashar; Kuldeep Kumar; Md.Tanvir Kabir; Priti Tagde (Environmental Science and Pollution Research, 2022)

Proximate analysis, preliminary phytochemical screening and characterization of compounds by GC–MS from “Cycas revoluta” - Deepak Kumar Sharma; R. S. Dave; K. R. Shah (Vegetos, 2022)

Unmanned Aerial Vehicle-Based Multispectral Remote Sensing for Commercially Important Aromatic Crops in India for Its Efficient Monitoring and Management - Sonam Bahuguna; Shubham Anchal; Deepak Guleria; Mamta Devi; Meenakshi; Devshree Kumar; Rakesh Kumar; P. V. S. Murthy; Amit Kumar (Journal of the Indian Society of Remote Sensing, 2022)

Molecular detection of tick-borne pathogens harbored by ticks collected from local breed (Non-descript) of cattle in the chhattishgarh state of India - Suresh Gulabrao Jadhao; Sushanta Pal; Sonali Deepak Borkar; Gajanan M. Chigure; Subrhodal Nath; Prabhir Kumar Sanyal; Sachin Sudhakar Waghmare; Sachin Kumar (International Journal of Tropical Insect Science, 2022)

Severe leaf-vein infestation upregulates antioxidant and photosynthetic activities in the lamina of Ficus religiosa - Upma Bhatt; Hanwant Singh; Deepak Kumar; Reto J. Strasser; Vineet Soni (Acta Physiologiae Plantarum, 2022)

Experimental investigation of different-shaped microwave-heated potatoes: thermal and quality characteristics analysis for food preservation - Deepak Singh; Sunita Singh; Suresh Kumar Patel; Shishir Sinha; Raj Kumar Arya; Dhananjay Singh (Environmental Science and Pollution Research, 2022)

Correction to: Delineation of Neuroprotective Effects and Possible Benefits of AntioxidantsTherapy for the Treatment of Alzheimer’s Diseases by Targeting Mitochondrial-Derived Reactive Oxygen Species: Bench to Bedside - Vaibhav Walia; Deepak Kaushik; Vineet Mittal; Kuldeep Kumar; Ravinder Verma; Jatin Parashar; Rokeya Akter; Md. Habibur Rahman; Saurabh Bhatia; Ahmed Al-Harrasi; Chenmala Karthika; Tanima Bhattacharya; et al. (Molecular Neurobiology, 2022)

Delineation of Neuroprotective Effects and Possible Benefits of AntioxidantsTherapy for the Treatment of Alzheimer’s Diseases by Targeting Mitochondrial-Derived Reactive Oxygen Species: Bench to Bedside - Vaibhav Walia; Deepak Kaushik; Vineet Mittal; Kuldeep Kumar; Ravinder Verma; Jatin Parashar; Rokeya Akter; Md. Habibur Rahman; Saurabh Bhatia; Ahmed Al-Harrasi; Chenmala Karthika; Tanima Bhattacharya; et al. (Molecular Neurobiology, 2022)

Fast Blue B Produces a Light Background on the Gel Surface - Deepak Kumar; Sakshi Behal; Rajasri Bhattacharyya; Dibyajyoti Banerjee (Indian Journal of Clinical Biochemistry, 2022)

Field-Safety Notice and Recall of Sleep Care Devices by Philips Respironics - Deepak Shrivastava; Velayudhan Mohan Kumar; Ravi Gupta; Hruda Nanda Mallick (Sleep and Vigilance, 2021)

Quantitative Ecological Study of Rhizophoraceae Mangroves of Bhitarkanika Wildlife Sanctuary Regions of Odisha Coast, India - Srinivas Acharya; Deepak Kumar Patra; Gyanranjan Mahalik; Pradipta Kumar Mohapatra (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Nanoemulgel for Efficient Topical Delivery of Finasteride Against Androgenic Alopecia - Deepak Kumar Upadhyay; Amit Sharma; Navjot Kaur; Ghanshyam Das Gupta; Raj Kumar Narang; Vineet Kumar Rai (Journal of Pharmaceutical Innovation, 2021)

Radiopharmaceuticals: An insight into the latest advances in medical uses and regulatory perspectives - Deepak Kaushik; Pooja Jangra; Ravinder Verma; Deepika Purohit; Parijat Pandey; Sandeep Sharma; Rakesh Kumar Sharma (Journal of Biosciences, 2021)

Evaluation of acaricidal resistance status of Rhipicephalus microplus ticks from the hilly state (Uttarakhand) of India and evaluation of efficacy of a natural formulation for the management of resistant ticks - Ashutosh Fular; Anil Kumar Sharma; Deepak Upadhaya; Abhijit Nandi; Gaurav Nagar; Nisha Bisht; Mukesh Shakya; Sachin Kumar; Satyanshu Kumar; Rajesh Kumar; Srikant Ghosh (Experimental and Applied Acarology, 2021)

Novel coronavirus pathogen in humans and animals: an overview on its social impact, economic impact, and potential treatments - Rokeya Akter; Md. Habibur Rahman; Tanima Bhattacharya; Deepak Kaushik; Vineet Mittal; Jatin Parashar; Kuldeep Kumar; Md. Tanvir Kabir; Priti Tagde (Environmental Science and Pollution Research, 2021)

Effects of piperazine and EDTA in garden snail towards electrolytic variation and antimicrobial activities - Anil Kumar; Varun Dhiman; Pawan Kumar; Deepak Pant (Environmental Science and Pollution Research, 2021)

Developing an effectiveness index for biomedical waste management in Indian states using a composite indicators approach - Anurag Deepak; Dinesh Kumar; Varun Sharma (Environmental Science and Pollution Research, 2021)

Investigating capability of open archive multispectral and SAR datasets for Wheat crop monitoring and acreage estimation studies - Manjari Upreti; Deepak Kumar (Earth Science Informatics, 2021)

Antiparasitic potential of Indian honey bee glue against strains of Leishmania donovani sensitive and resistant to synthetic antileishmanial - Deepak Kumar Goyal; Poonam Keshav; Sukhbir Kaur (Biologia, 2021)

Ameliorative effect of Dillenia indica fruits against doxorubicin-induced cardiomyocyte toxicity - Kalyani Tene; Kalyan Kumar; Deepak Bharadwaj Pemmaraju; Jagadeesh Kumar; P. A. Shantanu; Ranadeep Gogoi; V. G. M. Naidu (Advances in Traditional Medicine, 2021)

Synthesis and Characterization of Chitosan-Alginate-Based Cross-linked Copolymer for the Effective Removal of Methylene Blue from Its Aqueous Solution - Sumit Kumar; Shailesh Kumar; Ashok Kumar; Swati Rastogi; Deepak Kumar (Water, Air, & Soil Pollution, 2021)

Correction to: WheatQTLdb: a QTL database for wheat - Kalpana Singh; Ritu Batra; Shiveta Sharma; Gautam Saripalli; Tinku Gautam; Rakhi Singh; Sunita Pal; Parveen Malik; Manoj Kumar; Irfat Jan; Sahadev Singh; Deepak Kumar; et al. (Molecular Genetics and Genomics, 2021)

Utilization of layered double hydroxides (LDHs) and their derivatives as photocatalysts for degradation of organic pollutants - Prakash Bobde; Ravi Kumar Patel; Deepak Panchal; Abhishek Sharma; Amit Kumar Sharma; Rita S. Dhodapkar; Sukdeb Pal (Environmental Science and Pollution Research, 2021)

Statistical investigation of long-term meteorological data to understand the variability in climate: a case study of Jharkhand, India - Lakhan Lal Mahato; Mukesh Kumar; Shakti Suryavanshi; Sudhir Kumar Singh; Deepak Lal (Environment, Development and Sustainability, 2021)

Identification and characterization of mutations in the SARS-CoV-2 RNA-dependent RNA polymerase as a promising antiviral therapeutic target - Niti Yashvardhini; Deepak Kumar Jha; Saurav Bhattacharya (Archives of Microbiology, 2021)

Water spread mapping of multiple lakes using remote sensing and satellite data - Vaibhav Deoli; Deepak Kumar; Manish Kumar; Alban Kuriqi; Ahmed Elbeltagi (Arabian Journal of Geosciences, 2021)

Application of enzymes for an eco-friendly approach to textile processing - Deepak Kumar; Raveena Bhardwaj; Sunena Jassal; Tanya Goyal; Aastha Khullar; Naveen Gupta (Environmental Science and Pollution Research, 2021)

Synthesis, molecular modelling studies of indolyl chalcone derivatives and their antimalarial activity evaluation - Jyoti; Rashmi Gaur; Yogesh Kumar; Harveer Singh Cheema; Deepak Singh Kapkoti; Mahendra P. Darokar; Feroz Khan; Rajendra Singh Bhakuni (Natural Product Research, 2021)

Therapeutic management of Mycobacterium avium subspecies paratuberculosis infection with complete resolution of symptoms and disease in a patient with advanced inflammatory bowel syndrome - Saurabh Gupta; Kundan Kumar Chaubey; Prabhat Agarwal; J. Todd Kuenstner; Deepak Parashar; Shoor Vir Singh (Molecular Biology Reports, 2021)

Saffron (Crocus sativus L.): gold of the spices—a comprehensive review - Deepak Kothari; Rajesh Thakur; Rakesh Kumar (Horticulture, Environment, and Biotechnology, 2021)

Skim sequencing: an advanced NGS technology for crop improvement - Pardeep Kumar; Mukesh Choudhary; B. S. Jat; Bhupender Kumar; Vishal Singh; Virender Kumar; Deepak Singla; Sujay Rakshit (Journal of Genetics, 2021)

Prediction of remdesivir resistance in COVID-19 illness: Need for development of clinical laboratory test - Deepak Kumar; Sukhpreet Singh; Deepak Yadav; Sumanpreet Kaur; Monu Kumari; Samiksha Jain; Rajasri Bhattacharyya; Dibyajyoti Banerjee (Indian Journal of Clinical Biochemistry, 2021)

WheatQTLdb: a QTL database for wheat - Kalpana Singh; Ritu Batra; Shiveta Sharma; Gautam Saripalli; Tinku Gautam; Rakhi Singh; Sunita Pal; Parveen Malik; Manoj Kumar; Irfat Jan; Sahadev Singh; Deepak Kumar; et al. (Molecular Genetics and Genomics, 2021)

Study of seasonal variation of PM2.5 concentration associated with meteorological parameters at residential sites in Delhi, India - Bhupendra Pratap Singh; Deepak Singh; Krishan Kumar; Vinod Kumar Jain (Journal of Atmospheric Chemistry, 2021)

Pan evaporative changes in transboundary Godavari River basin, India - Deepak Jhajharia; Shivam Gupta; Rasoul Mirabbasi; Rohitashw Kumar; G. T. Patle (Theoretical and Applied Climatology, 2021)

Correction to: Sodium nitroprusside enhances biomass and gymnemic acids production in cell suspension of Gymnema sylvestre (Retz.) R.Br. ex. Sm. - Ganesan Mahendran; Deepak Kumar; Sanjeet Kumar Verma; Ashish Chandran; ·Zafar Iqbal Warsi; Zakir Husain; Shama Afroz; Prasant Kumar Rout; Laiq Ur Rahman (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Analysis and visualization of meteorological extremes in humid subtropical regions - Brij Kishor Pandey; Deepak Khare; Harinarayan Tiwari; Prabhash Kumar Mishra (Natural Hazards, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Sodium nitroprusside enhances biomass and gymnemic acids production in cell suspension of Gymnema sylvestre (Retz.) R.Br. ex. Sm. - Ganesan Mahendran; Deepak Kumar; Sanjeet Kumar Verma; Ashish Chandran; Zafar Iqbal Warsi; Zakir Husain; Shama Afroz; Prasant Kumar Rout; Laiq Ur Rahman (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Determination of trace metal(loid)s in mangrove swamp sediments in relation to its adjacent host rocks of South Andaman, India - Shiva Shankar Venkatesan; Neelam Purti; Kaviarasan Thanamegam; Baskaran Ram; Dharanirajan Kesavan; Pm Mohan; Karthik Raji; Narshimulu Ganta; Arumugam Kathirvel; Satyakeerthy Thonduparambil Ravindaran; Deepak Kumar Agrawal; Swamynathan Balasundraganapathy; et al. (Arabian Journal of Geosciences, 2021)

Possible Biomarkers and Contributing Factors of Psychosis: a Review - Monu Yadav; Naresh Kumar; Anil Kumar; Deepak Kumar Jindal; Mini Dahiya (Current Pharmacology Reports, 2021)

Middle East Respiratory Syndrome (MERS) Virus—Pathophysiological Axis and the Current Treatment Strategies - Abdullah M Alnuqaydan; Abdulmajeed G Almutary; Arulmalar Sukamaran; Brian Tay Wei Yang; Xiao Ting Lee; Wei Xuan Lim; Yee Min Ng; Rania Ibrahim; Thiviya Darmarajan; Satheeshkumar Nanjappan; Jestin Chellian; Mayuren Candasamy; et al. (AAPS PharmSciTech, 2021)

Impact of heat and drought stress on phenological development and yield in bread wheat - K. J. Yashavanthakumar; Vijendra S. Baviskar; Sudhir Navathe; Ravindra M. Patil; Juned H. Bagwan; Deepak N. Bankar; Vitthal D. Gite; K. Gopalareddy; Chandra Nath Mishra; H. M. Mamrutha; Sanjay Kumar Singh; Shreenivas A. Desai; et al. (Plant Physiology Reports, 2021)

Evaluating filter properties for urban feature identification from dual-pol SAR images - Deepak Kumar; Aman Kumar (Modeling Earth Systems and Environment, 2021)

Genome Analysis of Bacillus aryabhattai to Identify Biosynthetic Gene Clusters and In Silico Methods to Elucidate its Antimicrobial Nature - Deepak A. Yaraguppi; Sanjay H. Deshpande; Zabin K. Bagewadi; Sudeep Kumar; Uday M. Muddapur (International Journal of Peptide Research and Therapeutics, 2021)

Electricigens and microbial fuel cells for bioremediation and bioenergy production: a review - Jyoti Verma; Deepak Kumar; Nimmi Singh; Sanjeev S. Katti; Yatish T. Shah (Environmental Chemistry Letters, 2021)

StCaM2, a calcium binding protein, alleviates negative effects of salinity and drought stress in tobacco - Meenakshi Raina; Ashish Kumar; Nikita Yadav; Sumita Kumari; Mohd Aslam Yusuf; Ananda Mustafiz; Deepak Kumar (Plant Molecular Biology, 2021)

Coomassie Brilliant Blue Can Visualize a Protein Band Without Destaining: A Quick Visualization Protocol on the Agarose Gel - Monu Kumari; Bhavishya Bhardwaj; Deepak Kumar; Rajasri Bhattacharyya; Dibyajyoti Banerjee (Indian Journal of Clinical Biochemistry, 2021)

Novel model of restricted mobility induced osteopenia in zebrafish - Deepak Kumar Khajuria; David Karasik (Journal of Fish Biology, 2021)
Immobilization, such as prolonged bed rest, is a risk factor for bone loss in humans. Motivated by the emerging utility of zebrafish ( Danio rerio ) as an animal of choice for the study of musculoskeletal disease, here we report a model of restricted mobility induced osteopenia in adult zebrafish. Aquatic tanks with small cubical compartments to restrict the movement and locomotion of single fish were designed and fabricated for this study. Adult zebrafish were divided into two groups: a normal control (CONT) and a restricted mobility group (RMG) (18 fish/group). Six fish from each group were euthanized on days 14, 21 and 35 of the movement restriction. By using microcomputed tomography (micro‐CT), we assessed bone volume/tissue volume (BV/TV) and bone density in the whole skeleton of the fish. Furthermore, we assessed skeletal shape in the vertebrae (radius, length, volume, neural and haemal arch aperture areas, neural and haemal arch angle, and thickness of the intervertebral space), single vertebra bone volume and bone density. Movement restriction significantly decreased vertebral skeletal parameters such as radius, length, volume, arch aperture areas and angles as well as the thickness of the intervertebral space in RMG. Furthermore, restricted mobility significantly ( P

An appraisal of uranium deposits of India and their style of deposition with reference to the Paleoproterozoic great oxidation event - Deepak Kumar Agarwal; Bulusu Sreenivas (International Geology Review, 2021)

Interplay effect modeling in stereotactic body radiotherapy treatment of liver cancer using volumetric modulated arc therapy - Deepak Thaper; Arun S. Oinam; Rose Kamal; Gaganpreet Singh; Bhumika Handa; Vivek Kumar; Hanuman P. Yadav (Physical and Engineering Sciences in Medicine, 2021)

Identification and functional prediction of long non-coding RNAs of rice (Oryza sativa L.) at reproductive stage under salinity stress - Priyanka Jain; Samreen Hussian; Jyoti Nishad; Himanshu Dubey; Deepak Singh Bisht; Tilak Raj Sharma; Tapan Kumar Mondal (Molecular Biology Reports, 2021)

Reliability analysis of settlement of pile group - Manish Kumar; Pijush Samui; Deepak Kumar; Wengang Zhang (Innovative Infrastructure Solutions, 2021)

Ethnomedicinal applications of forest plants for the treatment of common ailments by Gond and Madia tribes of Maharashtra, India - Virendra Kumar Mishra; Prabhu Nath Shukla; Gurudatta Singh; Deepak Gupta; Guruvaiya Bhanaviya Durge (Environmental Sustainability, 2021)

Response of a rice-field cyanobacterium Anabaena sp. HKAR-7 upon exposure to ultraviolet-B radiation and ammonium chloride - Deepak Kumar Singh; Jainendra Pathak; Abha Pandey; Vidya Singh; Haseen Ahmed; Deepak Kumar; Rajneesh; Rajeshwar Prasad Sinha (Environmental Sustainability, 2021)

Genomic analysis of a novel species Halomonas shambharensis isolated from hypersaline lake in Northwest India - Kapilesh Jadhav; Bijayendra Kushwaha; Indrani Jadhav; Prem Shankar; Anjali Geethadevi; Gaurav Kumar; Sonam Mittal; Guru Prasad Sharma; Madhuri Parashar; Deepak Parashar (Molecular Biology Reports, 2021)

A Novel Methodology to Classify Soil Liquefaction Using Deep Learning - Deepak Kumar; Pijush Samui; Dookie Kim; Anshuman Singh (Geotechnical and Geological Engineering, 2021)

Intelligent vulnerability prediction of soil erosion hazard in semi-arid and humid region - Deepak Agnihotri; Tarun Kumar; Dalchand Jhariya (Environment, Development and Sustainability, 2021)

Geospatial approach to evaluate the morphometry of Sabarmati River Basin, India - Pooja Kumari; Rina Kumari; Deepak Kumar (Arabian Journal of Geosciences, 2021)

Hydrogenation properties and kinetic study of MgH2 - x wt% AC nanocomposites prepared by ball milling - Kanhaiya Chawla; Deepak Kumar Yadav; Abhinav Bajpai; Sushant Kumar; Chhagan Lal (Environmental Science and Pollution Research, 2021)

Catalytic effect on hydrogen de/absorption properties of MgH2 − x wt% MM (x = 0, 10, 20, 30) nanomaterials - Deepak Kumar Yadav; Kanhaiya Chawla; I. P. Jain; Chhagan Lal (Environmental Science and Pollution Research, 2021)

Green biosynthesis of silver nanoparticles and impact on growth, chlorophyll, yield and phytotoxicity of Phaseolus vulgaris L - Deepak Kumar Verma; Sapan Patel; Kalyan Singh Kushwah (Vegetos, 2020)

Guidelines of the Indian Society for Sleep Research (ISSR) for Practice of Sleep Medicine during COVID-19 - Ravi Gupta; V. Mohan Kumar; Manjari Tripathi; Karuna Datta; Manjunatha Narayana; Kripesh Ranjan Sarmah; Manvir Bhatia; Preeti Devnani; Sourav Das; Deepak Shrivastava; Rama Devi Gourineni; Tripat Deep Singh; et al. (Sleep and Vigilance, 2020)

A Novel Intelligent ELM-BBO Technique for Predicting Distance of Mine Blasting-Induced Flyrock - Bhatawdekar Ramesh Murlidhar; Deepak Kumar; Danial Jahed Armaghani; Edy Tonnizam Mohamad; Bishwajit Roy; Binh Thai Pham (Natural Resources Research, 2020)

VacPred: Sequence-based prediction of plant vacuole proteins using machine-learning techniques - Arvind Kumar Yadav; Deepak Singla (Journal of Biosciences, 2020)

Prevalence of ixodid ticks infesting in cattle of Chhattisgarh state, an east-central part of India - Suresh Gulabrao Jadhao; Prabir Kumar Sanyal; Sonali Deepak Borkar; Gajanan Madhavrao Chigure; Nitin Dadarao Jadhav; Pramod Madhavrao Shirsikar; Sachin Kumar (International Journal of Tropical Insect Science, 2020)

Evaluation of different substrate supplements on growth and yield of oyster mushroom (Pleurotus florida) - Santosh Kumar; Gireesh Chand; Deepak Kumar Patel (Indian Phytopathology, 2020)

Predicting groundwater depth fluctuations using deep learning, extreme learning machine and Gaussian process: a comparative study - Deepak Kumar; Thendiyath Roshni; Anshuman Singh; Madan Kumar Jha; Pijush Samui (Earth Science Informatics, 2020)

Pea Gβ subunit of G proteins has a role in nitric oxide-induced stomatal closure in response to heat and drought stress - Deepak Bhardwaj; Ranjan Kumar Sahoo; Afsar Raza Naqvi; Suman Lakhanpaul; Narendra Tuteja (Protoplasma, 2020)

A Hybrid Indexing Approach for Sustainable Smart Cities Development - Mandvi Misra; Deepak Kumar (Journal of the Indian Society of Remote Sensing, 2020)

New Distributional Record of Petal-Eyed Swimmer Crab, Vojmirophthalmus minabensis (Sakai 1961) (Portunidae: Podophthalminae) from Indian Waters - Mariasingarayan Yosuva; Chinnathambi Viswanathan; Vijay Kumar Deepak Samuel; Kanagaraj Chamundeeswari; Ramachandran Purvaja; Ramachandran Ramesh (Thalassas: An International Journal of Marine Sciences, 2020)

Understanding Oxidation Propensity in GCSF and Assessment of its Safety and Efficacy - Sumit Kumar Singh; Deepak Kumar; Anurag S. Rathore (Pharmaceutical Research, 2020)

Elucidating micro RNAs role in different plant–pathogen interactions - Charu Kulshrestha; Hardik Pathak; Deepak Kumar; Saurabh Dave; Jebi Sudan (Molecular Biology Reports, 2020)

Traffic noise prediction model of an Indian road: an increased scenario of vehicles and honking - Chaitanya Thakre; Vijaya Laxmi; Ritesh Vijay; Deepak J. Killedar; Rakesh Kumar (Environmental Science and Pollution Research, 2020)

Emerging era of “somes”: polymersomes as versatile drug delivery carrier for cancer diagnostics and therapy - Abhishek Kumar Sharma; Parteek Prasher; Alaa A. Aljabali; Vijay Mishra; Himanshu Gandhi; Sunil Kumar; Srinivas Mutalik; Dinesh Kumar Chellappan; Murtaza M. Tambuwala; Kamal Dua; Deepak N. Kapoor (Drug Delivery and Translational Research, 2020)

Molecular Investigation of the Status of Ticks on Infected Cattle for Coxiella burnetii in India - Pankaj Dhaka; Satya Veer Singh Malik; Jay Prakash Yadav; Srikant Ghosh; Manesh Kumar; Sukhadeo B. Barbuddhe; Deepak B. Rawool (Acta Parasitologica, 2020)

Chemical composition, antioxidant and antiproliferative activities of essential oil from rhizome and leaves of Curcuma mutabilis Škorničk., M. Sabu & Prasanthk., endemic to Western Ghats of India - T. Soumya; P. R. Jayasree; M. Deepak; P. R. Manish Kumar (Natural Product Research, 2020)

Health benefits of chromones: common ingredients of our daily diet - Ruchi Badoni Semwal; Deepak Kumar Semwal; Sandra Combrinck; Alvaro Viljoen (Phytochemistry Reviews, 2020)

Eroding islands of Gulf of Mannar, Southeast India: a consequence of long-term impact of coral mining and climate change - N. Gladwin Gnana Asir; P. Dinesh Kumar; A. Arasamuthu; G. Mathews; K. Diraviya Raj; T. K. Ashok Kumar; Deepak S. Bilgi; J. K. Patterson Edward (Natural Hazards, 2020)

Ameliorative effect of curcumin on altered expression of CACNA1A and GABRD in the pathogenesis of FeCl3-induced epilepsy - Prince Kumar; Deepak Sharma (Molecular Biology Reports, 2020)

Recent technological advancements in stem cell research for targeted therapeutics - Nilesh Rai; Anurag Kumar Singh; Santosh Kumar Singh; Bhaskar Gaurishankar; Swapnil C. Kamble; Pradeep Mishra; Deepak Kotiya; Suvakanta Barik; Neelam Atri; Vibhav Gautam (Drug Delivery and Translational Research, 2020)

Intrascale windowing-based cuckoo search–optimized sub-band thresholding for satellite image denoising - Ashish Kumar Bhandari; Deepak Kumar; Anil Kumar (Arabian Journal of Geosciences, 2020)

Sustainability at a cost: An inceptive analysis of “extended” fishing ban on the livelihoods of fishers of Tamil Nadu - John Amali Infantina; Parasuram Priya; Vijay Kumar Deepak Samuel; Kottarathil Rajendiran Abhilash; Ramchandran Purvaja; Ramachandran Ramesh (Fisheries Management and Ecology, 2020)
An emphasis on sustainable marine fish production has paved the way for the enactment of Marine Fisheries Regulation Acts and subsequent regulations in India. A closed season ban on fishing has been one of the very few successful regulatory measures since its introduction in 2001 in Tamil Nadu. Since 2017, the fishing ban period has been extended from 45 to 60 days for the east coast of India, for ecosystem‐based marine fisheries management. This study analyses the socioeconomic impacts of change in the fishing ban (closed season) across the four coastal zones of Tamil Nadu. For the past 10 years, CPUE has been stable or increased marginally. Among the four coasts, the relative change in employment and labour income loss was highest for Palk Bay (36.84%). Transaction costs of implementation of the ban caused an additional expense of Rs 496.5 million to the Government in 2017 and the overall total labour income loss has leaped from Rs 1,638.2 to 2,100.2 million due to the extension of the ban. The fishing ban has aided in the recovery of habitat and regeneration of stock through recruitment. Training and capacity building on alternative livelihood options are highly recommended to enable the workers to cope with the ban period.

Physiological and Biochemical Response of a Hot-Spring Cyanobacterium Nostoc Sp. Strain HKAR-2 to Aluminum Toxicity - Vinod K. Kannaujiya; Deepak Kumar; Jainendra Pathak; Rajneesh; Rajeshwar P. Sinha (Water, Air, & Soil Pollution, 2020)

Formulation, Optimization, and Evaluation of Allopurinol-Loaded Bovine Serum Albumin Nanoparticles for Targeting Kidney in Management of Hyperuricemic Nephrolithiasis - Gurpreet Kandav; D. C. Bhatt; Deepak Kumar Jindal; Shailendra Kumar Singh (AAPS PharmSciTech, 2020)

Nitrate-leaching and groundwater vulnerability mapping in North Bihar, India - Pankaj Kumar Gupta; Binita Kumari; Saurabh Kumar Gupta; Deepak Kumar (Sustainable Water Resources Management, 2020)

Efficacy of Indolicidin, Cecropin A (1-7)-Melittin (CAMA) and Their Combination Against Biofilm-Forming Multidrug-Resistant Enteroaggregative Escherichia coli - Jess Vergis; S. V. S. Malik; Richa Pathak; Manesh Kumar; R. Sunitha; S. B. Barbuddhe; Deepak B. Rawool (Probiotics and Antimicrobial Proteins, 2020)

Sobol sensitivity analysis for risk assessment of uranium in groundwater - Deepak Kumar; Anshuman Singh; Pappu Kumar; Rishi Kumar Jha; Sunil Kumar Sahoo; Vivekanand Jha (Environmental Geochemistry and Health, 2020)

Identification and mapping of quantitative trait loci (QTL) and epistatic QTL for salinity tolerance at seedling stage in traditional aromatic short grain rice landrace Kolajoha (Oryza sativa L.) of Assam, India - Abhishek Mazumder; Megha Rohilla; Deepak Singh Bisht; S. L. Krishnamurthy; Mandira Barman; Ramendra Nath Sarma; Tilak Raj Sharma; Tapan Kumar Mondal (Euphytica, 2020)

Emergence of fipronil resistant Rhipicephalus microplus populations in Indian states - Mukesh Shakya; Sachin Kumar; Ashutosh Fular; Deepak Upadhaya; Anil Kumar Sharma; Nisha Bisht; Abhijit Nandi; Srikant Ghosh (Experimental and Applied Acarology, 2020)

Acaricide resistance in Rhipicephalus microplus collected from selected districts of Madhya Pradesh, Uttar Pradesh and Punjab states of India - Sharath V. Sagar; Kuldeep Saini; Anil Kumar Sharma; Sachin Kumar; Rinesh Kumar; Ashutosh Fular; Mukesh Shakya; Deepak Upadhaya; Gaurav Nagar; Shanmuganath C.; Subhamoy Samanta; Suman Kumar; et al. (Tropical Animal Health and Production, 2020)

Applicability of HEC-RAS 2D and GFMS for flood extent mapping: a case study of Sangam area, Prayagraj, India - Neeraj Kumar; Mukesh Kumar; Arpan Sherring; Shakti Suryavanshi; Ajaz Ahmad; Deepak Lal (Modeling Earth Systems and Environment, 2020)

Photoprotective role of UV-screening pigment scytonemin against UV-B-induced damages in the heterocyst-forming cyanobacterium Nostoc sp. strain HKAR-2 - Abha Pandey; Jainendra Pathak; Deepak K. Singh; Haseen Ahmed; Vidya Singh; Deepak Kumar; Rajeshwar P. Sinha (Brazilian Journal of Botany, 2020)

Systematic precipitation redistribution following a strong hurricane landfall - Paul W. Miller; Thomas L. Mote; Abhishek Kumar; Deepak R. Mishra (Theoretical and Applied Climatology, 2020)

A spatiotemporal analysis of Indian warming target using CORDEX-SA experiment data - Deepak Kumar Prajapat; Jyoti Lodha; Mahender Choudhary (Theoretical and Applied Climatology, 2020)

Pseudomonas aeruginosa quorum-sensing molecule N-(3-oxo-dodecanoyl)-l-homoserine lactone triggers mitochondrial dysfunction and apoptosis in neutrophils through calcium signaling - Pradeep Kumar Singh; Vivek Kumar Yadav; Manmohit Kalia; Deepmala Sharma; Deepak Pandey; Vishnu Agarwal (Medical Microbiology and Immunology, 2019)

Therapeutic management of mange infestation in cat (Felis catus): a case report - Ashutosh Fular; Geeta; Mukesh Shakya; Mamta Singh; Deepak Upadhaya; Sachin Kumar (International Journal of Tropical Insect Science, 2019)

Solvent-Tolerant Acyltransferase from Bacillus sp. APB-6: Purification and Characterization - Deepak Pandey; Sanjay K. S. Patel; Rajendra Singh; Pradeep Kumar; Vikram Thakur; Duni Chand (Indian Journal of Microbiology, 2019)

Targeting kidneys by superparamagnetic allopurinol loaded chitosan coated nanoparticles for the treatment of hyperuricemic nephrolithiasis - Gurpreet Kandav; D. C. Bhatt; Deepak Kumar Jindal (DARU Journal of Pharmaceutical Sciences, 2019)

Groundnut AhcAPX conferred abiotic stress tolerance in transgenic banana through modulation of the ascorbate–glutathione pathway - Shashi Shekhar; Anjana Rustagi; Deepak Kumar; Mohd. Aslam Yusuf; Neera Bhalla Sarin; Kapil Lawrence (Physiology and Molecular Biology of Plants, 2019)

Role of plant-derived alkaloids against diabetes and diabetes-related complications: a mechanism-based approach - Ankit Kumar; Sonali Aswal; Ruchi Badoni Semwal; Ashutosh Chauhan; Sunil Kumar Joshi; Deepak Kumar Semwal (Phytochemistry Reviews, 2019)

RNA-seq reveals outcome-specific gene expression of MMP7 and PCK1 in biliary atresia - Priya Ramachandran; Deepak Balamurali; J. John Peter; M. Milner Kumar; Mohamed Safwan; Mukul Vij; Mohamed Rela; Sundarasamy Mahalingam (Molecular Biology Reports, 2019)

Long short-term memory (LSTM) recurrent neural network for low-flow hydrological time series forecasting - Bibhuti Bhusan Sahoo; Ramakar Jha; Anshuman Singh; Deepak Kumar (Acta Geophysica, 2019)

Assessment of Low Intensity Solar Radiation Susceptibility in 20 Wheat Varieties under Field Conditions Grown in Indo-Gangetic Plains of India - Usha Mina; S.D. Singh; B. Singh; S. Tiwari; Deepak Singh; Pranav Kumar (Journal of Crop Science and Biotechnology, 2019)

BjuWRR1, a CC-NB-LRR gene identified in Brassica juncea, confers resistance to white rust caused by Albugo candida - Heena Arora; K. Lakshmi Padmaja; Kumar Paritosh; Nitika Mukhi; A. K. Tewari; Arundhati Mukhopadhyay; Vibha Gupta; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2019)

Risk assessment of low arsenic exposure using biomarkers of oxidative and genotoxic stress in a piscine model - Deepak K. Jha; Kumar Sayrav; Gaurav P. Mishra; Bipin B. Mishra; Anupma Kumari; Amod Kumar; Parimal K. Khan (Ecotoxicology, 2019)

Seagrass restoration in Gulf of Mannar, Tamil Nadu, Southeast India: a viable management tool - J. K. Patterson Edward; K. Diraviya Raj; G. Mathews; P. Dinesh Kumar; A. Arasamuthu; Nisha D’ Souza; Deepak S. Bilgi (Environmental Monitoring and Assessment, 2019)

A Variance Decomposition Approach for Risk Assessment of Groundwater Quality - Deepak Kumar; Anshuman Singh; Rishi Kumar Jha; Sunil Kumar Sahoo; Vivekanand Jha (Exposure and Health, 2019)

Genetic variant rs10937405 of TP63 and susceptibility to lung cancer risk in north Indian population - GH. Rasool Bhat; Amrita Bhat; Sonali Verma; Itty Sethi; Ruchi Shah; Varun Sharma; S. Minerva; Divya Bakshi; Bhanu Sharma; Sandeep Koul; Deepak Abrol; Audesh Bhat; et al. (Journal of Genetics, 2019)

Source characterization and human health risk assessment of nitrate in groundwater of middle Gangetic Plain, India - Deepak Kumar; Anshuman Singh; Rishi Kumar Jha; Bibhuti Bhushan Sahoo; Sunil Kumar Sahoo; Vivekanand Jha (Arabian Journal of Geosciences, 2019)

Meeting the challenge of developing food crops with improved nutritional quality and food safety: leveraging proteomics and related omics techniques - Shalu Jain; Anjana Rustagi; Deepak Kumar; Mohd Aslam Yusuf; Shashi Shekhar; Neera Bhalla Sarin (Biotechnology Letters, 2019)

Forecasting monthly precipitation using sequential modelling - Deepak Kumar; Anshuman Singh; Pijush Samui; Rishi Kumar Jha (Hydrological Sciences Journal, 2019)

Recent advances and opportunities in the treatment of hydrocarbons and oils: Metal-organic frameworks-based approaches - Vanish Kumar; Kowsalya Vellingiri; Deepak Kukkar; Sandeep Kumar; Ki-Hyun Kim (Critical Reviews in Environmental Science and Technology, 2019)

Altered lipid metabolism in post-traumatic epileptic rat model: one proposed pathway - Niraj Kumar Srivastava; Somnath Mukherjee; Rajkumar Sharma; Jharana Das; Rohan Sharma; Vikas Kumar; Neeraj Sinha; Deepak Sharma (Molecular Biology Reports, 2019)

Targeting oxidative stress, acetylcholinesterase, proinflammatory cytokine, dopamine and GABA by eucalyptus oil (Eucalyptus globulus) to alleviate ketamine-induced psychosis in rats - Monu Yadav; Deepak Kumar Jindal; Milind Parle; Anil Kumar; Sameer Dhingra (Inflammopharmacology, 2019)

A perspective on the diagnostics, prognostics, and therapeutics of microRNAs of triple-negative breast cancer - Rama Rao Malla; Seema Kumari; Murali Mohan Gavara; Anil Kumar Badana; Shailender Gugalavath; Deepak Kakara Gift Kumar; Prasuja Rokkam (Biophysical Reviews, 2019)

β-Naphthyl Acetate in Acetone Produces a Dark Background for Staining of Esterase Activity on Gel - Deepak Kumar; Sakshi Behal; Rajasri Bhattacharyya; Dibyajyoti Banerjee (Indian Journal of Clinical Biochemistry, 2019)

High speed regeneration via somatic embryogenesis in elite Indian banana cv. Somrani monthan (ABB) - Anjana Rustagi; Shashi Shekhar; Deepak Kumar; Kapil Lawrence; Vishnu Bhat; Neera Bhalla Sarin (Vegetos, 2019)

Contribution of systemic vascular reactivity to variability in pulse volume amplitude response during reactive hyperemia - Geetanjali Bade; Dinu S. Chandran; Ashok Kumar Jaryal; Anjana Talwar; Kishore Kumar Deepak (European Journal of Applied Physiology, 2019)

Insights on the pharmacological, phytochemical and ethnobotanical aspects of Artemisia roxburghiana: a rather less explored but therapeutically important species of lower Himalayas - Ankit Kumar; Sonali Aswal; Ruchi Badoni Semwal; Ashutosh Chauhan; Deepak Kumar Semwal (Phytochemistry Reviews, 2019)

Plasma Hydrogen Peroxide: A Myth or Reality? - Deepak Kumar; Vandana Singh; Sakshi Behal; Kunal Maniar; Sheemona Chawdhary; Rajasri Bhattacharyya; Dibyajyoti Banerjee (Indian Journal of Clinical Biochemistry, 2019)

Demand for Affordable “Sleep Study” - V. Mohan Kumar; H. N. Mallick; Deepak Shrivastava (Sleep and Vigilance, 2018)

Molecular dynamics simulation as a tool for assessment of drug binding property of human serum albumin - Meenu Narwal; Deepak Kumar; Tapan Kumar Mukherjee; Rajasri Bhattacharyya; Dibyajyoti Banerjee (Molecular Biology Reports, 2018)

Real Time Eye Blink Extraction Circuit Design from EEG Signal for ALS Patients - Rakesh Ranjan; Rajeev Arya; Poonam Kshirsagar; Vinay Jain; Deepak K. Jain; Arun Kumar Sangaiah (Journal of Medical and Biological Engineering, 2018)

Development of fungicides spray schedule to manage the late blight of potato in north eastern Himalayan region of India - Malkhan Singh Gurjar; Raju Kumar; Deepak Singh; T. K. Bag (Indian Phytopathology, 2018)

Identification and characterization of the promoter of a gene expressing mainly in the tapetum tissue of cotton (Gossypium hirsutum L.) - Kumar Paritosh; Amarjeet Kumar Singh; Amita Kush Mehrotra; Deepak Pental; Pradeep Kumar Burma (Plant Biotechnology Reports, 2018)

Abnormal lipid metabolism in a rat model of arthritis: one possible pathway - Niraj Kumar Srivastava; Shikha Sharma; Neeraj Sinha; Sudhir Kumar Mandal; Deepak Sharma (Molecular and Cellular Biochemistry, 2018)

Marine Bacterial Compounds Evaluated by In Silico Studies as Antipsychotic Drugs Against Schizophrenia - Dhinesh Kumar Thiyagarajamoorthy; Charli Deepak Arulanandam; Hans-Uwe Dahms; Santhosh Gokul Murugaiah; Muthukumar Krishnan; Arthur James Rathinam (Marine Biotechnology, 2018)

Exogenous application of calcium chloride in wheat genotypes alleviates negative effect of drought stress by modulating antioxidant machinery and enhanced osmolyte accumulation - Khushboo; Kritika Bhardwaj; Preeti Singh; Meenakshi Raina; Vinay Sharma; Deepak Kumar (In Vitro Cellular & Developmental Biology - Plant, 2018)

A study of indoor radon, thoron and their exhalation rates in the environment of Fazilka district, Punjab, India - Saurabh Narang; Deepak Kumar; Dinesh Kumar Sharma; Ajay Kumar (Acta Geophysica, 2018)

Cytological and immunocytological detection and differentiation of Marek’s disease and lymphoid leucosis in poultry - M. Asok Kumar; M. Palanivelu; R. Barathidasan; Deepak Kumar; S. D. Singh; Shyma K. Lateef; Rajendra Singh; K. Dhama (VirusDisease, 2018)

Multivariate statistical analysis approach for prediction of blast-induced ground vibration - Vivek K. Himanshu; M. P. Roy; A. K. Mishra; Ranjit Kumar Paswan; Deepak Panda; P. K. Singh (Arabian Journal of Geosciences, 2018)

Effect of grain packing tightness on strain estimation from the Fry method - Arun Kumar Ojha; Deepak C Srivastava (Journal of Earth System Science, 2018)

Paradigm for disease deconvolution in rare neurodegenerative disorders in Indian population: insights from studies in cerebellar ataxias - Renu Kumari; Deepak Kumar; Samir K. Brahmachari; Achal K. Srivastava; Mohammed Faruq; Mitali Mukerji (Journal of Genetics, 2018)

Isolation, structural elucidation and antiplasmodial activity of fucosterol compound from brown seaweed , Sargassum linearifolium against malarial parasite Plasmodium falciparum - Pachiappan Perumal; Rajamani Sowmiya; Sundaram Prasanna kumar; Sundaram Ravikumar; Paramasivam Deepak; Govindasamy Balasubramani (Natural Product Research, 2018)

Pathological and molecular investigation of velogenic viscerotropic Newcastle disease outbreak in a vaccinated chicken flocks - Asok Kumar Mariappan; Palanivelu Munusamy; Deepak Kumar; Shyma K. Latheef; Shambu Dayal Singh; Rajendra Singh; Kuldeep Dhama (VirusDisease, 2018)

Spatial distribution of uranium and basic water quality parameter in the capital of Bihar and consequent ingestion dose - Deepak Kumar; Anshuman Singh; Rishi Kumar Jha (Environmental Science and Pollution Research, 2018)

Composition and functional property of photosynthetic pigments under circadian rhythm in the cyanobacterium Spirulina platensis - Deepak Kumar; Vinod K. Kannaujiya; Richa; Jainendra Pathak; Shanthy Sundaram; Rajeshwar P. Sinha (Protoplasma, 2018)

Protective effect of gallic acid in experimental model of ketamine-induced psychosis: possible behaviour, biochemical, neurochemical and cellular alterations - Monu Yadav; Deepak Kumar Jindal; Mamta Sachdeva Dhingra; Anil Kumar; Milind Parle; Sameer Dhingra (Inflammopharmacology, 2018)

Pathological and molecular studies of the renal trematode Paratanaisia bragai in Indian peafowls (Pavo cristatus) - M. Asok Kumar; Deepak Kumar; Munuswamy Palanivelu; Latchumikanthan Annamalai; Karikalan Mathesh; Rajendra Singh; Anil Kumar Sharma; Kuldeep Dhama (Acta Parasitologica, 2018)
Endoparasitic diseases are commonly encountered in free-ranging birds. Although not all endoparasites cause disease, persistent infection with large numbers of parasites almost always affects normal physiological functions, leading to deleterious effects on the host. This paper describes the anatomopathological alterations caused by the renal trematode Paratanaisia bragai in Indian peafowl (n = 3) and examines the phylogeny of these and related parasites. Peafowl from forests in and around the Bareilly region, Uttar Pradesh, India, were necropsied, and microscopic and molecular investigations were performed. The peafowl were confirmed to be infected with P . bragai . Significant gross pathological lesions suggested nephrosis, and microscopic findings indicated a mild-to-moderate degree of nephrosis caused by the parasites in the tissue. The parasites were identified as P . bragai by histomorphological analysis of adult and eggs in the ureters, and the identification was confirmed by PCR and phylogenetic analysis. Nucleotide sequencing of the PCR products from the renal trematodes recovered from Indian peafowl revealed a close association with P . bragai from Columbiformes in the United Kingdom and Spain. The pathology and molecular epidemiology of parasitic diseases affecting peafowl is not well understood in India. This is the first report from India and the second report worldwide to document P . bragai infection in peafowl.

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Applicability of HEC-RAS & GFMS tool for 1D water surface elevation/flood modeling of the river: a Case Study of River Yamuna at Allahabad (Sangam), India - Neeraj Kumar; Deepak Lal; Arpan Sherring; R. K. Issac (Modeling Earth Systems and Environment, 2017)

Development and Evaluation of Simple Dot–Blot Assays for Rapid Detection of Staphylococcal Enterotoxin-A in Food - Mamta Singh; Ravi Kant Agrawal; Bhoj Raj Singh; Sanjod Kumar Mendiratta; Rajesh Kumar Agarwal; Mithilesh Kumar Singh; Deepak Kumar (Indian Journal of Microbiology, 2017)

Determination of Critical Quality Attributes for a Biotherapeutic in the QbD Paradigm: GCSF as a Case Study - Sumit K. Singh; Deepak Kumar; Anurag S. Rathore (The AAPS Journal, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Identifying Transcription Factor Genes Associated with Yield Traits in Chickpea - Philanim Wungmarong Shimray; Deepak Bajaj; Rishi Srivastava; Anurag Daware; Hari D. Upadhyaya; Rajendra Kumar; Chellapilla Bharadwaj; Akhilesh K. Tyagi; Swarup K. Parida (Plant Molecular Biology Reporter, 2017)

Dynamic interaction of trace gases (VOCs, ozone, and NOx) in the rural atmosphere of sub-tropical India - Amit Kumar; Deepak Singh; Kumar Anandam; Krishan Kumar; Vinod Kumar Jain (Air Quality, Atmosphere & Health, 2017)

Comparative diagnostic evaluation of OMP31 gene based TaqMan® real-time PCR assay with visual LAMP assay and indirect ELISA for caprine brucellosis - Suman Saini; V. K. Gupta; K. Gururaj; D. D. Singh; R. V. S. Pawaiya; N. K. Gangwar; A. K. Mishra; Deepak Dwivedi; Dimple Andani; Ashok Kumar; T. K. Goswami (Tropical Animal Health and Production, 2017)

Biocompatible Phospholipid-Based Mixed Micelles for Tamoxifen Delivery: Promising Evidences from In - Vitro Anticancer Activity and Dermatokinetic Studies - Pramod Kumar; Rajendra Kumar; Bhupinder Singh; Ruchi Malik; Gajanand Sharma; Deepak Chitkara; O. P. Katare; Kaisar Raza (AAPS PharmSciTech, 2017)

Comprehensive assessment of the genes involved in withanolide biosynthesis from Withania somnifera: chemotype-specific and elicitor-responsive expression - Aditya Vikram Agarwal; Parul Gupta; Deeksha Singh; Yogeshwar Vikram Dhar; Deepak Chandra; Prabodh Kumar Trivedi (Functional & Integrative Genomics, 2017)

The History of Indian Society for Sleep Research (ISSR) from its Inception to the Launching of the Journal “Sleep and Vigilance” - V. Mohan Kumar; H. N. Mallick; Deepak Shrivastava (Sleep and Vigilance, 2017)

Differential Impact of Anniversary-Severe Cyclones on the Water Quality of a Tropical Coastal Lagoon - Abhishek Kumar; Deepak R. Mishra; Sk. Md. Equeenuddin; Hyun Jung Cho; Gurdeep Rastogi (Estuaries and Coasts, 2017)

Perturbations and 3R in carbon management - Deepak Pant; Virbala Sharma; Pooja Singh; Manoj Kumar; Anand Giri; M P Singh (Environmental Science and Pollution Research, 2017)

Detection and delineation of glacial lakes and identification of potentially dangerous lakes of Dhauliganga basin in the Himalaya by remote sensing techniques - Lalan Kumar Jha; Deepak Khare (Natural Hazards, 2017)

Identification of genic SSRs and construction of a SSR-based linkage map in Brassica juncea - Namrata Dhaka; Arundhati Mukhopadhyay; Kumar Paritosh; Vibha Gupta; Deepak Pental; Akshay K. Pradhan (Euphytica, 2017)

Ursolic Acid Loaded PLGA Nanoparticles: in vitro and in vivo Evaluation to Explore Tumor Targeting Ability on B16F10 Melanoma Cell Lines - Rinku Baishya; Dipak K. Nayak; Deepak Kumar; Samarendu Sinha; Amit Gupta; Shantanu Ganguly; Mita Chatterjee Debnath (Pharmaceutical Research, 2016)

Transcriptome-wide identification and characterization of CAD isoforms specific for podophyllotoxin biosynthesis from Podophyllum hexandrum - Dipto Bhattacharyya; Saptarshi Hazra; Anindyajit Banerjee; Riddhi Datta; Deepak Kumar; Saikat Chakrabarti; Sharmila Chattopadhyay (Plant Molecular Biology, 2016)

Linear gradient analysis of kinetic temperature through geostatistical approach - Deepak Kumar; Sulochana Shekhar (Modeling Earth Systems and Environment, 2016)

Adaptive hierarchical cell sub-division (AHCS) method for enhanced surface radiance temperature variability analysis - Deepak Kumar (Modeling Earth Systems and Environment, 2016)

Preparation and Preclinical Evaluation of Inhalable Particles Containing Rapamycin and Anti-Tuberculosis Agents for Induction of Autophagy - Anuradha Gupta; Deepak Sharma; Jairam Meena; Sanketkumar Pandya; Madhur Sachan; Sadan Kumar; Kavita Singh; Kalyan Mitra; Sharad Sharma; Amulya K. Panda; Pushpa Gupta; Umesh Datta Gupta; et al. (Pharmaceutical Research, 2016)

The impact of assimilating MeghaTropiques SAPHIR radiances in the simulation of tropical cyclones over the Bay of Bengal using the WRF model - M. Dhanya; Deepak Gopalakrishnan; A. Chandrasekar; Sanjeev Kumar Singh; V.S. Prasad (International Journal of Remote Sensing, 2016)

Spatial and temporal variability of VOCs and its source estimation during rush/non-rush hours in ambient air of Delhi, India - Deepak Singh; Amit Kumar; Bhupendra Pratap Singh; Kumar Anandam; Manoj Singh; Usha Mina; Krishan Kumar; Vinod Kumar Jain (Air Quality, Atmosphere & Health, 2016)

A Temporal Study on the Effects of TiO2 Nanoparticles in a Fresh Water Microcosm - Deepak Kumar; A. Rajeshwari; Rajdeep Roy; Sunandan Pakrashi; V. Iswarya; Ida Evangeline Paul; Ankita Mathur; N. Chandrasekaran; Amitava Mukherjee (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Multiple abiotic stress tolerance in Vigna mungo is altered by overexpression of ALDRXV4 gene via reactive carbonyl detoxification - Preeti Singh; Deepak Kumar; Neera Bhalla Sarin (Plant Molecular Biology, 2016)

SNP mining in transcripts and concomitant estimation of genetic variation in Macrobrachium rosenbergii stocks - Deepak Agarwal; Nilav Aich; A Pavan-Kumar; Sujit Kumar; Supriya Sabnis; C. G. Joshi; Prakash Koringa; Dipal Pandya; Namrata Patel; Tanvi Karnik; Ridhima Bhingarde; P Gireesh-Babu; et al. (Conservation Genetics Resources, 2016)

In vitro evaluation of anticancer properties of exopolysaccharides from Lactobacillus acidophilus in colon cancer cell lines - Venkataraman Deepak; Sharavan Ramachandran; Reham Mohammed Balahmar; Sureshbabu Ram Kumar Pandian; Shiva D. Sivasubramaniam; Hariharan Nellaiah; Krishnan Sundar (In Vitro Cellular & Developmental Biology - Animal, 2016)

A comparative study with biologically and chemically synthesized nZVI: applications in Cr (VI) removal and ecotoxicity assessment using indigenous microorganisms from chromium-contaminated site - K. V. G. Ravikumar; Deepak Kumar; A. Rajeshwari; G. M. Madhu; P. Mrudula; Natarajan Chandrasekaran; Amitava Mukherjee (Environmental Science and Pollution Research, 2016)

Semi-analytical Solutions of Multiprocessing Non-equilibrium Transport Equations with Linear and Exponential Distance-Dependent Dispersivity - Pramod Kumar Sharma; C. S. P. Ojha; Deepak Swami; Nitin Joshi; Sanjay Kumar Shukla (Water Resources Management, 2015)

A genome-scale integrated approach aids in genetic dissection of complex flowering time trait in chickpea - Hari D. Upadhyaya; Deepak Bajaj; Shouvik Das; Maneesha S. Saxena; Saurabh Badoni; Vinod Kumar; Shailesh Tripathi; C. L. L. Gowda; Shivali Sharma; Akhilesh K. Tyagi; Swarup K. Parida (Plant Molecular Biology, 2015)

A study on biosynthesis of “citral” in lemongrass (C. flexuosus) cv. Suvarna - Ashish Kumar Gupta; Deepak Ganjewala (Acta Physiologiae Plantarum, 2015)

Nose-To-Brain Delivery of PLGA-Diazepam Nanoparticles - Deepak Sharma; Rakesh Kumar Sharma; Navneet Sharma; Reema Gabrani; Sanjeev K. Sharma; Javed Ali; Shweta Dang (AAPS PharmSciTech, 2015)

Recombinant LipL32 Based Enzyme Linked Immunosorbent Assay for Seroprevalence Studies of Leptospirosis in Livestock Farmers - Sujit K. Behera; Sabrinath Thankpan; Sasmita Khatua; Deepak Pal; Suresh C. Das; Gitanjali Sarangi; Pallab Chaudhary; Ashok Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Sustainability assessment and ranking of run of the river (RoR) hydropower projects using analytical hierarchy process (AHP): A study from Western Himalayan region of India - Deepak Kumar; Surjit Singh Katoch (Journal of Mountain Science, 2015)

Determination of Sex Origin of Meat and Meat Products on the DNA Basis: A Review - Palanisamy Gokulakrishnan; Rajiv Ranjan Kumar; Brahm Deo Sharma; Sanjod Kumar Mendiratta; Omprakash Malav; Deepak Sharma (Critical Reviews in Food Science and Nutrition, 2015)

Identification of Species Origin of Meat and Meat Products on the DNA Basis: A Review - Arun Kumar; Rajiv Ranjan Kumar; Brahm Deo Sharma; Palanisamy Gokulakrishnan; Sanjod Kumar Mendiratta; Deepak Sharma (Critical Reviews in Food Science and Nutrition, 2015)

The mRNA expression of immune-related genes in crossbred and Tharparkar cattle in response to in vitro infection with Theileria annulata - Prashant Dewangan; Manjit Panigrahi; Amod Kumar; B. C. Saravanan; Shrikant Ghosh; V. N. Muhashin Asaf; Subhashree Parida; G. K. Gaur; Deepak Sharma; Bharat Bhushan (Molecular Biology Reports, 2015)

Spatial and temporal variability of surface ozone and nitrogen oxides in urban and rural ambient air of Delhi-NCR, India - Amit Kumar; Deepak Singh; Bhupendra Pratap Singh; Manoj Singh; Kumar Anandam; Krishan Kumar; V. K. Jain (Air Quality, Atmosphere & Health, 2015)

Cytotoxicity of aluminum oxide nanoparticles on Allium cepa root tip—effects of oxidative stress generation and biouptake - A. Rajeshwari; S. Kavitha; Sruthi Ann Alex; Deepak Kumar; Anita Mukherjee; Natarajan Chandrasekaran; Amitava Mukherjee (Environmental Science and Pollution Research, 2015)

Genetics- and genomics-based interventions for nutritional enhancement of grain legume crops: status and outlook - Abhishek Bohra; Kanwar L. Sahrawat; Shiv Kumar; Rohit Joshi; Ashok K. Parihar; Ummed Singh; Deepak Singh; Narendra P. Singh (Journal of Applied Genetics, 2015)

Selection and genetic transformation of a fast-growing cell line in cotton (Gossypium hirsutum) for transgene expression studies - Amarjeet Kumar Singh; Deepak Pental (Journal of Plant Biochemistry and Biotechnology, 2015)

PEG–PHB-glutaminase nanoparticle inhibits cancer cell proliferation in vitro through glutamine deprivation - Sureshbabu Ram Kumar Pandian; Venkataraman Deepak; Hariharan Nellaiah; Krishnan Sundar (In Vitro Cellular & Developmental Biology - Animal, 2015)

Efficacy and safety of Stephania glabra : an alkaloid-rich traditional medicinal plant - Deepak Kumar Semwal; Ruchi Badoni Semwal (Natural Product Research, 2015)

Integrated transcriptomic and proteomic analysis of Arabidopsis thaliana exposed to glutathione unravels its role in plant defense - Ragini Sinha; Deepak Kumar; Riddhi Datta; Saptarshi Hazra; Dipto Bhattacharyya; Aparupa Bose Mazumdar; Ria Mukhopadhyay; Asma Sultana; Sharmila Chattopadhyay (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

An acenocoumarol dosing algorithm exploiting clinical and genetic factors in South Indian (Dravidian) population - Dhakchinamoorthi Krishna Kumar; Deepak Gopal Shewade; Marie-Anne Loriot; Philippe Beaune; B. V. Sai Chandran; Jayaraman Balachander; Chandrasekaran Adithan (European Journal of Clinical Pharmacology, 2015)

Genetic Predisposition to Diabetic Nephropathy: Evidence for a Role of ACE (I/D) Gene Polymorphism in Type 2 Diabetic Population from Kutch Region - Deepak N. Parchwani; Kamlesh M. Palandurkar; D. Hema Chandan Kumar; Darshan J. Patel (Indian Journal of Clinical Biochemistry, 2015)

Real-time PCR carried out on DNA extracted from serum or blood sample is not a good method for surveillance of bovine brucellosis - Arvind Tiwari; Vijai Pal; Prachiti Afley; Deepak Kumar Sharma; Chandra Shekhar Bhatnagar; Bhupendra Bhardwaj; Ganga Prasad Rai; Subodh Kumar (Tropical Animal Health and Production, 2014)

Core-shell nanoparticulate formulation of gemcitabine: lyophilization, stability studies, and in vivo evaluation - Deepak Chitkara; Anupama Mittal; Ram I. Mahato; Neeraj Kumar (Drug Delivery and Translational Research, 2014)

The role of TLR9 polymorphism in susceptibility to pulmonary tuberculosis - Deepak Bharti; Ashish Kumar; Ranjeet Singh Mahla; Sushil Kumar; Harshad Ingle; Hari Shankar; Beenu Joshi; Ashwin Ashok Raut; Himanshu Kumar (Immunogenetics, 2014)

Optimization and purification of anticancer enzyme L-glutaminase from Alcaligenes faecalis KLU102 - Sureshbabu Ram Kumar Pandian; Venkataraman Deepak; Shiva D. Sivasubramaniam; Hariharan Nellaiah; Krishnan Sundar (Biologia, 2014)

Tetralocular ovary and high silique width in yellow sarson lines of Brassica rapa (subspecies trilocularis) are due to a mutation in Bra034340 gene, a homologue of CLAVATA3 in Arabidopsis - Satish Kumar Yadava; Kumar Paritosh; Priya Panjabi-Massand; Vibha Gupta; Atika Chandra; Y. S. Sodhi; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2014)

Type II PtdIns 4-kinase β associates with CD4–p56lck complex and is involved in CD4 receptor signaling - Ranjeet Kumar Sinha; Naveen Bojjireddy; Deepak Kanojia; Gosukonda Subrahmanyam (Molecular and Cellular Biochemistry, 2014)

When is a South Indian Really Anemic? - Deepak Kumar Pasupula; P. S. Reddy (Indian Journal of Clinical Biochemistry, 2014)

Analysis of Climate and Melt-runoff in Dunagiri Glacier of Garhwal Himalaya (India) - Deepak Srivastava; Amit Kumar; Akshaya Verma; Siddharth Swaroop (Water Resources Management, 2014)

Electrostatic effects control the stability and iron release kinetics of ovotransferrin - Sandeep Kumar; Deepak Sharma; Rajesh Kumar; Rajesh Kumar (JBIC Journal of Biological Inorganic Chemistry, 2014)

Vespa tropica venom suppresses lipopolysaccharide-mediated secretion of pro-inflammatory cyto-chemokines by abrogating nuclear factor-κ B activation in microglia - Deepak Kumar Kaushik; Menaka Chanu Thounaojam; Arinjay Mitra; Anirban Basu (Inflammation Research, 2014)

Polymorphism of cytokine and innate immunity genes associated with bovine brucellosis in cattle - Om Prakash; Amit Kumar; Arvind Sonwane; Rajesh Rathore; Ran Vir Singh; Anuj Chauhan; Pushpendra Kumar; R. Renjith; Ramji Yadav; Ashish Bhaladhare; Mohd Baqir; Deepak Sharma (Molecular Biology Reports, 2014)

Correlation of human S100A12 (EN-RAGE) and high-sensitivity C-reactive protein as gingival crevicular fluid and serum markers of inflammation in chronic periodontitis and type 2 diabetes - A. R. Pradeep; Santosh S. Martande; Sonender Pal Singh; Deepak Kumar Suke; Arjun P. Raju; Savitha B. Naik (Inflammation Research, 2014)

In vitro evaluation of polyethylene glycol based microparticles containing azithromycin - Shunmugaperumal Tamilvanan; Vinay Kumar; Deepak Sharma; Ashutosh Thakur (Drug Delivery and Translational Research, 2014)

Precipitable water vapor estimation in India from GPS-derived zenith delays using radiosonde data - Dinesh Singh; Jayanta Kumar Ghosh; Deepak Kashyap (Meteorology and Atmospheric Physics, 2014)

Assessment of indoor air concentrations of VOCs and their associated health risks in the library of Jawaharlal Nehru University, New Delhi - Amit Kumar; Bhupendra Pratap Singh; Monika Punia; Deepak Singh; Krishan Kumar; V. K. Jain (Environmental Science and Pollution Research, 2014)

Effect of CYP2C9, VKORC1, CYP4F2 and GGCX genetic variants on warfarin maintenance dose and explicating a new pharmacogenetic algorithm in South Indian population - Dhakchinamoorthi Krishna Kumar; Deepak Gopal Shewade; Marie-Anne Loriot; Philippe Beaune; Jayaraman Balachander; B. V. Sai Chandran; Chandrasekaran Adithan (European Journal of Clinical Pharmacology, 2014)

Cross-species transferability of microsatellite markers from Fusarium oxysporum for the assessment of genetic diversity in Fusarium udum - Sudheer Kumar; Shalini Rai; Deepak Kumar Maurya; Prem Lal Kashyap; Alok K. Srivastava; M. Anandaraj (Phytoparasitica, 2013)

Genotyping and subtyping of mumps virus isolates from the Indian subcontinent - Baijayantimala Mishra; Sujit Kumar Pujhari; Vandana Dhiman; P. MahaLakshmi; Abhinav Bharadwaj; Sandeep Pokhrel; Deepak Sharma; Mirnalini Sharma; Deepak Bhatia; Radha Kanta Ratho (Archives of Virology, 2013)

Modulation of antioxidant machinery in α-tocopherol-enriched transgenic Brassica juncea plants tolerant to abiotic stress conditions - Deepak Kumar; Mohd Aslam Yusuf; Preeti Singh; Meryam Sardar; Neera Bhalla Sarin (Protoplasma, 2013)

Structural and Transcriptional Characterization of rbcS Genes of Cotton (Gossypium hirsutum) - Kumar Paritosh; Deepak Pental; Pradeep Kumar Burma (Plant Molecular Biology Reporter, 2013)

BSA-PLGA-Based Core-Shell Nanoparticles as Carrier System for Water-Soluble Drugs - Deepak Chitkara; Neeraj Kumar (Pharmaceutical Research, 2013)

Sequence and expression analyses of KIX domain proteins suggest their importance in seed development and determination of seed size in rice, and genome stability in Arabidopsis - Jitendra Kumar Thakur; Pinky Agarwal; Swarup Parida; Deepak Bajaj; Richa Pasrija (Molecular Genetics and Genomics, 2013)

Effects of wild-type and α-tocopherol-enriched transgenic Brassica juncea on the components of xenobiotic metabolism, antioxidant status, and oxidative stress in the liver of mice - Manju Singh; Deepak Kumar; Mohd Aslam Yusuf; Meryam Sardar; Neera Bhalla Sarin (Transgenic Research, 2013)

Synthesis and biological evaluation of some new quinazolin-4(3H)-ones derivatives as anticonvulsants - Deepak Gupta; Rajiv Kumar; Ram Kumar Roy; Adish Sharma; Israr Ali; Md. Shamsuzzaman (Medicinal Chemistry Research, 2013)

Soil moisture levels affect mycorrhization during early stages of development of agroforestry plants - Ashok Shukla; Anil Kumar; Anuradha Jha; Onkar Salunkhe; Deepak Vyas (Biology and Fertility of Soils, 2013)

The first multituberculate mammal from India - Varun Parmar; Guntupalli V. R. Prasad; Deepak Kumar (The Science of Nature, 2013)

A new triterpenoid saponin from Glinus oppositifolius with α-glucosidase inhibitory activity - Deepak Kumar; Vrunda Shah; Rina Ghosh; Bikas C. Pal (Natural Product Research, 2013)

Study of atmospheric stagnation, recirculation and ventilation potential at Narora Atomic Power Station NPP site - Deepak Kumar; Avinash Kumar; Vimal Kumar; Jaivender Kumar; P. M Ravi (Environmental Monitoring and Assessment, 2013)

The effects of meteorological parameters in ambient noise modelling studies in Delhi - Deepak Singh; Amit Prakash; A. K. Srivastava; Krishan Kumar; V. K. Jain (Environmental Monitoring and Assessment, 2013)

QTL mapping of yield-associated traits in Brassica juncea: meta-analysis and epistatic interactions using two different crosses between east European and Indian gene pool lines - Satish Kumar Yadava; N. Arumugam; Arundhati Mukhopadhyay; Yashpal Singh Sodhi; Vibha Gupta; Deepak Pental; Akshay K. Pradhan (Theoretical and Applied Genetics, 2012)

Cumulative effects of tree-based intercropping on arbuscular mycorrhizal fungi - Ashok Shukla; Anil Kumar; Anuradha Jha; Shiv Kumar Dhyani; Deepak Vyas (Biology and Fertility of Soils, 2012)

Life cycle assessment of energy and GHG emissions during ethanol production from grass straws using various pretreatment processes - Deepak Kumar; Ganti S. Murthy (The International Journal of Life Cycle Assessment, 2012)

Inter and intra-ethnic differences in the distribution of the molecular variants of TPMT, UGT1A1 and MDR1 genes in the South Indian population - Gurusamy Umamaheswaran; Dhakchinamoorthi Krishna Kumar; Dhandapani Kayathiri; Subramanian Rajan; Deepak Gopal Shewade; Steven Aibor Dkhar; Sajjanavar Manjunath; Prayaga Ushakiran; Gangadharan Reneega; Kukreti Ritushree; Chandrasekaran Adithan (Molecular Biology Reports, 2012)

Ectopic overexpression of a salt stress-induced pathogenesis-related class 10 protein (PR10) gene from peanut (Arachis hypogaea L.) affords broad spectrum abiotic stress tolerance in transgenic tobacco - Shalu Jain; Deepak Kumar; Mukesh Jain; Prerna Chaudhary; Renu Deswal; Neera Bhalla Sarin (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Development of quercetin nanoformulation and in vivo evaluation using streptozotocin induced diabetic rat model - Deepak Chitkara; Sanjay K. Nikalaje; Anupama Mittal; Mahesh Chand; Neeraj Kumar (Drug Delivery and Translational Research, 2012)

Genome-wide transcriptomic analysis of cotton under drought stress reveal significant down-regulation of genes and pathways involved in fibre elongation and up-regulation of defense responsive genes - Kethireddy Venkata Padmalatha; Gurusamy Dhandapani; Mogilicherla Kanakachari; Saravanan Kumar; Abhishek Dass; Deepak Prabhakar Patil; Vijayalakshmi Rajamani; Krishan Kumar; Ranjana Pathak; Bhupendra Rawat; Sadhu Leelavathi; Palakolanu Sudhakar Reddy; et al. (Plant Molecular Biology, 2012)

Synthesis and antimicrobial activities of some new 5-((3-(aryl)-1-phenyl-1H-pyrazol-4-yl)methylene)-3-phenylthiazolidine-2,4-diones - Om Prakash; Deepak Kumar Aneja; Sanjiv Arora; Chetan Sharma; K. R. Aneja (Medicinal Chemistry Research, 2012)

The first draft of the pigeonpea genome sequence - Nagendra K. Singh; Deepak K. Gupta; Pawan K. Jayaswal; Ajay K. Mahato; Sutapa Dutta; Sangeeta Singh; Shefali Bhutani; Vivek Dogra; Bikram P. Singh; Giriraj Kumawat; Jitendra K. Pal; Awadhesh Pandit; et al. (Journal of Plant Biochemistry and Biotechnology, 2012)

Neuroprotective Effect of Cyclooxygenase Inhibitors in ICV-STZ Induced Sporadic Alzheimer’s Disease in Rats - Dinesh Kumar Dhull; Ankur Jindal; Rakesh K. Dhull; Saurabh Aggarwal; Deepak Bhateja; Satyanarayana S. V. Padi (Journal of Molecular Neuroscience, 2012)

Combined Effect of N-Acetyl Cysteine, Zinc, and Selenium Against Chronic Dimethylmercury-Induced Oxidative Stress: A Biochemical and Histopathological Approach - Deepmala Joshi; Deepak Mittal; Sadhana Shrivastav; Sangeeta Shukla; Ajai Kumar Srivastav (Archives of Environmental Contamination and Toxicology, 2011)

Photoluminescence Studies of Pr3+ Doped Lead Germanate Glass - Deepak Kumar Mohanty; Vineet Kumar Rai (Journal of Fluorescence, 2011)

Detrimental effect of expression of Bt endotoxin Cry1Ac on in vitro regeneration, in vivo growth and development of tobacco and cotton transgenics - Preeti Rawat; Amarjeet Kumar Singh; Krishna Ray; Bhupendra Chaudhary; Sanjeev Kumar; Taru Gautam; Shaveta Kanoria; Gurpreet Kaur; Paritosh Kumar; Deepak Pental; Pradeep Kumar Burma (Journal of Biosciences, 2011)

Eliminating expression of erucic acid-encoding loci allows the identification of “hidden” QTL contributing to oil quality fractions and oil content in Brassica juncea (Indian mustard) - Arun Jagannath; Yashpal Singh Sodhi; Vibha Gupta; Arundhati Mukhopadhyay; Neelakantan Arumugam; Indira Singh; Soma Rohatgi; Pradeep Kumar Burma; Akshay Kumar Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2011)

Pyramiding of two bacterial blight resistance and a semidwarfing gene in Type 3 Basmati using marker-assisted selection - Deepak Rajpurohit; Rahul Kumar; Mankesh Kumar; Priyanka Paul; Anjali Awasthi; P. Osman Basha; Anju Puri; Tripta Jhang; Kuldeep Singh; Harcharan Singh Dhaliwal (Euphytica, 2011)

Celtisanin, a novel sulphonated phenolic from Celtis australis L. fruits - Ruchi Badoni; Deepak Kumar Semwal; Usha Rawat; Gur Jas Preet Singh (Natural Product Research, 2010)

A candidate gene OsAPC6 of anaphase-promoting complex of rice identified through T-DNA insertion - Mankesh Kumar; P. Osman Basha; Anju Puri; Deepak Rajpurohit; Gursharn Singh Randhawa; Tilak Raj Sharma; Harcharan Singh Dhaliwal (Functional & Integrative Genomics, 2010)

The polyembryo gene (OsPE) in rice - Anju Puri; P. Osman Basha; Mankesh Kumar; Deepak Rajpurohit; Gursharn S. Randhawa; Shahryar F. Kianian; Anantharama Rishi; Harcharan S. Dhaliwal (Functional & Integrative Genomics, 2010)

Molecular mapping reveals two independent loci conferring resistance to Albugo candida in the east European germplasm of oilseed mustard Brassica juncea - Priya Panjabi-Massand; Satish Kumar Yadava; Pankaj Sharma; Arvinder Kaur; Amarendra Kumar; N. Arumugam; Yashpal Singh Sodhi; Arundhati Mukhopadhyay; Vibha Gupta; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2010)

Evaluation of anti-fertility activity of Tabernaemontana divaricata (Linn) R.Br. leaves in rats - Sachin Jain; Avijeet Jain; Lokesh Deb; K.R. Dutt; Deepak Kumar Jain (Natural Product Research, 2010)

Protective Role of Thiol Chelators Against Dimethylmercury Induced Toxicity in Male Rats - Deepmala Joshi; Deepak Kumar Mittal; Sadhana Shrivastava; Sangeeta Shukla (Bulletin of Environmental Contamination and Toxicology, 2010)

Evaluation of wound-healing activity of Acorus calamus Linn. - Nilesh Jain; Ruchi Jain; Arti Jain; Deepak Kumar Jain; H.S. Chandel (Natural Product Research, 2010)

Analysis of promoter activity in transgenic plants by normalizing expression with a reference gene: anomalies due to the influence of the test promoter on the reference promoter - Simran Bhullar; Suma Chakravarthy; Deepak Pental; Pradeep Kumar Burma (Journal of Biosciences, 2009)

A metabolic and functional overview of brain aging linked to neurological disorders - Najma Z. Baquer; Asia Taha; Pardeep Kumar; P. McLean; S. M. Cowsik; R. K. Kale; R. Singh; Deepak Sharma (Biogerontology, 2009)

Inactivation of a transgene due to transposition of insertion sequence (IS136) of Agrobacterium tumefaciens - Preeti Rawat; Sanjeev Kumar; Deepak Pental; Pradeep Kumar Burma (Journal of Biosciences, 2009)

Effect of dehydroepiandrosterone (DHEA) on monoamine oxidase activity, lipid peroxidation and lipofuscin accumulation in aging rat brain regions - Pardeep Kumar; Asia Taha; Deepak Sharma; R. K. Kale; Najma Z. Baquer (Biogerontology, 2008)

Effect of dehydroepiandrosterone (DHEA) on monoamine oxidase activity, lipid peroxidation and lipofuscin accumulation in aging rat brain regions - Pardeep Kumar; Asia Taha; Deepak Sharma; R. K. Kale; Najma Z. Baquer (Biogerontology, 2008)

A passage through in vitro culture leads to efficient production of marker-free transgenic plants in Brassica juncea using the Cre–loxP system - N. Arumugam; Vibha Gupta; Arun Jagannath; Arundhati Mukhopadhyay; Akshay K. Pradhan; Pradeep Kumar Burma; Deepak Pental (Transgenic Research, 2007)

Negative effect of chromosome 1A on dough strength shown by modification of 1D addition in durum wheat (Triticum durum) - Monika Garg; Harcharan Singh Dhaliwal; Parveen Chhuneja; Deepak Kumar; Quan-Wen Dou; Hiroyuki Tanaka; Hala M. M. Elamein; Hisashi Tsujimoto (Theoretical and Applied Genetics, 2007)

Use of the transposable element Ac/Ds in conjunction with Spm/dSpm for gene tagging allows extensive genome coverage with a limited number of starter lines: functional analysis of a four-element system in Arabidopsis thaliana - Priya Panjabi; Pradeep Kumar Burma; Deepak Pental (Molecular Genetics and Genomics, 2006)

Captive breeding of endangered fish Chitala chitala (Hamilton-Buchanan) for species conservation and sustainable utilization - Uttam Kumar Sarkar; Prashant Kumar Deepak; Raje Singh Negi; Shriprakash Singh; Dhurendra Kapoor (Biodiversity and Conservation, 2006)

Molecular characterization of a gender-linked DNA marker and a related gene in Mercurialis annua L. - Deepak Kumar Khadka; Ali Nejidat; Moshe Tal; Avi Golan-Goldhirsh (Planta, 2005)

Tryptophan residue is essential for immunoreactivity of a diagnostically relevant peptide epitope of A. fumigatus - Neel Kamal; Shantanu Chowdhury; Taruna Madan; Deepak Sharma; M. Attreyi; Wahajul Haq; Seturam Bandacharya Katti; Anil Kumar; P. Usha Sarma (Molecular and Cellular Biochemistry, 2005)

Antral and duodenal disaccharidases in patients of duodenal ulcer and non-ulcer dyspepsia - Saroj Kant Sinha; Satya Vati Rana; Deepak Kumar Bhasin; Kusum Joshi (Indian Journal of Clinical Biochemistry, 2005)

Biotreatment of Simulated Textile Dye Effluent Containing malachite green by an Up-Flow Immobilized Cell Bioreactor - Deepak Kumar Sharma; Harvinder Singh Saini; Manjinder Singh; Swapandeep Singh Chimni; Bhupinder Singh Chadha (World Journal of Microbiology and Biotechnology, 2004)

Recognition of Human Anti-DNA Autoantibodies by Secretory Antigen 85 Complex of Mycobacterium Tuberculosis H37Rv - Deepak Kumar Garg; Moinuddin; Najmul Islam; Rashid Ali (World Journal of Microbiology and Biotechnology, 2004)

High Frequency Regeneration of Brassica napus Varieties and Genetic Transformation of Stocks Containing Fertility Restorer Genes for Two Cytoplasmic Male Sterility Systems - Sanjay Kumar Phogat; Pradeep Kumar Burma; Deepak Pental (Journal of Plant Biochemistry and Biotechnology, 2000)

A four-element based transposon system for allele specific tagging in plants—Theoretical considerations - Sanjay Phogat; Pradeep Kumar Burma; Deepak Pental (Journal of Biosciences, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)